Compositions comprising surface-modified spherical nanoparticles
By using a composition with a core-shell nanoelement structure, including water-insoluble CSSCs and non-covalently bonded fatty amines, the problem that the skin composition in the prior art is difficult to penetrate the skin barrier and solvent residue, achieving efficient and safe transdermal delivery and anti-aging effects.
Patent Information
- Application Number
- CN202380051331.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-22
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-18
AI Technical Summary
Existing skin compositions are difficult to effectively penetrate the skin barrier when penetrating the skin, and solvent residues in conventional methods may be toxic to the skin, affecting the stability and efficacy of the composition.
A composition consisting of core-shell nanoelements, which contains water-insoluble collagen synthetic stimulating compounds (CSSCs), and the shell contains non-covalently bonded water-insoluble fatty amines. The nanoelements are dispersed in polar carriers to ensure the stability of the composition and the effective penetration of high molecular weight molecules.
Effective transdermal delivery of high molecular weight molecules is achieved, reducing solvent residues, improving the safety and efficacy of the composition, and is particularly suitable for anti-aging treatments.
Smart Images

Figure CN119654381A_ABST
Abstract
Description
Related Applications
[0001] This application claims Paris Convention priority to UK application No. 2210308.9 filed on July 13, 2022 and UK application No. 2217477.5 filed on November 22, 2022. It is related to the commonly owned application International Publication No. WO 2022 / 243899 published on November 24, 2022, the contents of which are incorporated herein by reference in their entirety as if fully set forth herein. Technical Field
[0002] The present disclosure relates to compositions particularly useful for dermatological purposes, including achieving both cosmetic and non-cosmetic effects. Methods of making these compositions are also disclosed. Background Art
[0003] The skin plays an important role in protecting the body from external environmental hazards. It also shows the most visible signs of aging, such as loss of elasticity, tone and firmness leading to sagging, and superficial blemishes or lesions ranging from fine lines to deep wrinkles.
[0004] Skin changes due to both intrinsic and extrinsic factors. Intrinsic aging factors include genetics, cellular metabolism, hormones, and metabolic processes. These factors lead to a decrease in the production of collagen and elastin, proteins that are widely present in the skin to ensure its structural integrity, as well as a decrease in the production of glycosaminoglycans (GAGs), which are water-binding molecules that together with elastin and collagen make up the skin matrix. Weakened sweat and oil gland function is another intrinsic process that can also cause the skin to become thinner and more fragile with age. Extrinsic factors include long-term light exposure, smoking, pollution, ionizing radiation, chemicals, toxins, etc. They usually lead to thickening of the outermost skin layer (stratum corneum), precancerous lesions that may lead to skin cancer, the formation of freckles and sun spots, and excessive loss of collagen, elastin, and GAGs. Together or individually, these processes cause the skin to appear deeply wrinkled, uneven skin tone, roughness, and thinning of the skin. Collagen, elastin, and GAGs can be referred to as structural skin polymers that not only provide the mechanical properties of the skin but also fulfill biological functions in both healthy and pathological conditions.
[0005] There are many ways to reduce or slow down skin aging, from mild topical treatments to more extreme surgical procedures. Early signs of aging can be treated with topically applied cosmetic products, including, for example, retinoids, vitamin C, and alpha hydroxy acids. Chemical peels, microdermabrasion, microneedling, ultrasonic energy devices, or laser resurfacing may be options for moderate to severe skin damage. Deeper facial wrinkles can be treated invasively, such as through injections of botulinum toxin, dermal fillers, or skin polymers such as collagen itself that are depleted by the aging process and whose size prevents their transdermal delivery. Surgical procedures, such as facelifts, brow lifts, or eyelid cosmetic surgeries, are more extreme measures for wrinkles and sagging skin.
[0006] Another approach used in anti-aging skin treatment involves increasing collagen synthesis in situ. There are many agents that can be administered orally, topically, or parenterally that are known to induce this synthesis. Oral agents include food supplements such as vitamin C, ginseng, and nutritionally derived antioxidants (e.g., blueberries, cinnamon, certain herbs, etc.). Aloe vera gel and retinol are two substances known to increase collagen synthesis when applied topically to the skin. Hydroxyapatite, on the other hand, can only achieve this effect when administered by injection.
[0007] Compared to compositions administered parenterally (involving pain and risk of infection) or orally (where first-pass metabolism should be overcome to maintain efficacy), topical compositions are considered more convenient to apply and safer, and are generally more effective in covering large areas. Thus, while injectable compositions with improved efficacy are still sought, topical compositions, such as those described above, are more desirable, especially for anti-aging treatments.
[0008] However, in order to be able to penetrate the skin, the cosmetic active agent (i.e., cosmeceutical) or medical active agent (e.g., drug) in such topical compositions should be small enough, typically having a molecular weight (MW) of 500 g / mol or less, to be able to penetrate the skin barrier and achieve a satisfactory transdermal administration effect. Such agents are preferably in the form of nanomaterials, such as nanofibers, nanoemulsions, nanospheres, nanocapsules, nanocrystals, dendritic polymers, liposomes, nanotubes, etc., as described in Souto E.B. et al., "Nanomaterials for Skin Delivery of Cosmeceuticals and Pharmaceuticals"; Applied Sciences, 2020, Vol. 10 (5), 1594.
[0009] In addition to the above exemplary compounds known to promote the synthesis of skin structural proteins, polymers (including proteins and their fragmented / shorter forms called peptides) are reported to promote the production of collagen, elastin, GAGs or other such molecules involved in maintaining the integrity of skin structure and function. Other polymers (or the same polymer) can (alternatively or additionally) inhibit processes or enzymes (e.g., proteases) that lead to the degradation of natural skin proteins. For example, some peptides are reported to promote the new synthesis of collagen, while others can inhibit collagenase (the enzyme responsible for collagen degradation).
[0010] Regardless of the type of biological activity, such materials (whether polymeric or not) may be able to positively stimulate the new synthesis of structural skin proteins and / or negatively inhibit the down-regulation of such skin proteins, the end result of which may include reducing or delaying the reduction of skin protein content, maintaining its level, or even increasing its presence. Such agents may be referred to herein as collagen synthesis stimulating compounds (CSSCs), or specifically as collagen synthesis stimulating polymers (CSSPs), and the activity of these agents on collagen (and / or other structural skin proteins) includes not only stimulating its new synthesis, but also alternatively or additionally preventing its degradation.
[0011] Various conventional methods for preparing nanomaterials (e.g., polymers) that are considered suitable for skin penetration are described in the literature. However, solvents are often residually trapped in the particles prepared by these methods. When the solvents used are volatile organic compounds (VOCs), there are known to be many disadvantages, because despite their relative volatility, these solvents cannot be completely removed, exceeding a non-negligible residual level. First, the presence of VOCs in the particles, even at residual levels, may be toxic to the skin, and therefore, regulatory guidelines require very limited amounts of residual VOCs, which are impossible to obtain by conventional methods. Secondly, since VOCs may gradually evaporate over time until they reach their residual levels, the structure or properties of the particles may change during this period, thereby affecting their efficacy. Although cumbersome methods have been developed to solve the residual entrapment of undesirable solvents, the methods reported so far cannot provide nanoparticles or even microparticles with a narrow size distribution, and / or when active ingredients are additionally required, they cannot form stable dispersions, or their low encapsulation efficiency, and may lack commercial viability in view of their complexity.
[0012] Since dermatological pharmaceutical or cosmetic products are always needed to restore or maintain the integrity (function and / or structure) of the skin for as long as possible, there is still a need to provide dermatological compositions that solve at least some of the above-mentioned problems. Advantageously, the novel compositions will allow the deposition within the skin layers or even the transdermal transfer of molecules with high molecular weight, which molecules would require injection for conventional delivery. Summary of the invention
[0013] Various aspects of the present invention relate to skin compositions comprising core-shell nanoelements consisting of a core and a shell, wherein the core comprises a water-insoluble collagen synthesis stimulating compound (CSSC), such as a collagen synthesis stimulating polymer (CSSP), and the shell comprises at least one fatty amine, wherein the core-shell nanoelements are dispersed as nanoparticles or nanodroplets in a polar carrier. It is noteworthy that the CSSC or CSSP molecules (which can be functionalized to enhance any of their desired properties) can have a molecular weight of 0.6 kDa or higher. The nanoelements can also include a second shell formed by an active cosmetic or pharmaceutical agent, which surrounds the fatty amine (first) shell. Methods for preparing core-shell nanoelements are also disclosed. Compositions generally comprising at least one surfactant and nanoelements (CSSC and / or (multiple) shells), a carrier or both, in addition to the CSSC or CSSP, can optionally further include at least one active agent in the core, as described below.
[0014] Although these dermal compositions have been developed to overcome at least some of the disadvantages associated with current delivery of CSSCs (e.g., CSSPs) and / or specific active agents to the skin, transdermal delivery via topical administration is preferred, not excluding their parenteral administration by subcutaneous injection into the skin treatment area (e.g., as a dermal filler).
[0015] As used herein, transdermal delivery of CSSC and / or active agent refers to the ability of these compounds to remain on the surface of the skin and / or penetrate into the skin layers to reach a target site within or just below the skin. In some embodiments, this route of administration of the skin composition according to the present invention can further allow the compound to be delivered through the skin for systemic distribution. Methods of preparing such topical or injectable skin compositions and uses thereof are also disclosed.
[0016] In a first aspect of the present disclosure, there is provided a skin composition comprising core-shell nanoelements (i.e., nanoparticles or nanodroplets) consisting of:
[0017] a) a core comprising at least one water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; and
[0018] b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC;
[0019] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
[0020] In a second aspect of the present disclosure, a skin composition is provided, comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements are composed of:
[0021] i. a core comprising at least one water-insoluble CSSC and a non-volatile liquid, wherein the CSSC has an average molecular weight of 0.6 kDa or more;
[0022] ii. a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC;
[0023] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
[0024] The non-covalent association of the shell with the core is believed to advantageously preserve the original activity of each molecule of the core and the shell, with none of their parts participating in covalent bonding through electron sharing that could reduce or alter their respective contributions to the efficacy of the composition. In addition, the fact that the fatty amines are not covalently bonded to the CSSC allows them to migrate to the outer surface of the nanoelement to form a shell thereon.
[0025] In some embodiments, CSSC has a temperature of 50°C and 10 sec. -1 The shear rate was measured at 10 7 Millipascal-second (mPa·s) or lower, 10 6 mPa·s or lower, 10 5 mPa·s or lower, 10 4 mPa·s or less or 10 3 mPa·s or lower natural viscosity.
[0026] In other embodiments, the CSSC, typically the CSSP, has a day hot viscosity of greater than 10 under the aforementioned measurement conditions. 7 mPa·s, e.g. up to 10 11 mPa·s, in which case the CSSC may be combined with at least one plasticizer.
[0027] In some embodiments, fatty amines, in addition to their role in forming the shell of the nanoelement, can also be used as plasticizers that can reduce the natural viscosity of the CSSC of the core and facilitate its processing and incorporation into the composition of the present invention as nanoelement. In other embodiments, if desired, the reduction of the viscosity of the CSSC is achieved by adding a non-volatile liquid as a plasticizer to the core.
[0028] Therefore, in some embodiments, the fatty amine contained in the composition and the non-volatile liquid optionally added as a plasticizer for CSSC are each present in respective amounts such that the viscosity of the nano-element formed therefrom is 0.0447 W / m at 50° C. and 10 sec. -1 The shear rate does not exceed 10 7 mPa·s. The viscosity of the bulk CSSC may be referred to as the first viscosity of the CSSC, while the viscosity of the nanoelement containing at least the CSSC and the fatty amine may be referred to as the second viscosity. More generally, a property characterizing the bulk CSSC contained in the core may be referred to as a "first" property, while a similar property measured on the nanoelement may be referred to as a "second" property, which may have the same or different value compared to the native CSSC.
[0029] In some embodiments, at a temperature of 50°C and 10 sec. -1 The nanoelements comprising CSSC in their core which has been optionally plasticized with fatty amines and / or non-volatile liquids showed a shear rate of 5×10 6 mPa·s or lower, 10 6 mPa·s or lower, 5×10 5 mPa·s or lower, 10 5 mPa·s or lower, 5×10 4 mPa·s or lower, 10 4 mPa·s or lower, 5×10 3 mPa·s or less, or 10 3 The second viscosity is mPa·s or less.
[0030] When the viscosity measured on nanoelements isolated from the composition decreases compared to the first viscosity of the bulk CSSC, the core of the nanoelement is considered plasticized, and the CSSC of the core may be referred to as a "plasticized" or "swollen" CSSC.
[0031] In some embodiments, the nanoelements comprised in the compositions of the invention (and / or obtained by the methods of the invention) contain less than 2 wt%, less than 1.5 wt%, or less than 1 wt% volatile organic compounds (VOCs) or blends thereof, based on the weight of the nanoelements.
[0032] In some embodiments, the CSSC (and / or core-shell nanoelements comprising the same, optionally as plasticized CSSC) is characterized by at least one, at least two, or at least three of the following structural properties:
[0033] i. The CSSC and / or the core-shell nanoelement is insoluble in a polar carrier;
[0034] ii. the CSSC and / or the core-shell nanoelement is biodegradable and / or biocompatible;
[0035] iii. the CSSC and / or the core-shell nanoelement has at least one of a melting temperature (Tm), a softening temperature (Ts) or a glass transition temperature (Tg) of at most 300°C, at most 250°C, at most 200°C, at most 180°C, at most 150°C or at most 120°C, the temperature being the first (i.e., native) Tm, Ts or Tg of the CSSC, or the second Tm, Ts or Tg of the nanoelement, or both;
[0036] iv. the CSSC and / or the core-shell nanoelement each have a first and / or second Tm of at least 0°C, at least 10°C, at least 20°C, at least 30°C, at least 40°C, at least 50°C or at least 60°C, respectively;
[0037] v. the CSSC and / or the core-shell nanoelements each have a first and / or second Tm between 0°C and 300°C, between 10°C and 300°C, between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 180°C, or between 50°C and 150°C, respectively;
[0038] vi. the CSSC and / or the core-shell nanoelement each have a first and / or second Tg or Ts of -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 20°C or higher, 30°C or higher, 40°C or higher, 50°C or higher, or 60°C or higher, respectively;
[0039] vii. the CSSC and / or the core-shell nanoelements each have a first and / or second Tg or Ts between -75°C and 300°C, between -50°C and 250°C, between -25°C and 200°C, between 0°C and 180°C, between 20°C and 180°C, or between 30°C and 150°C, respectively;
[0040] viii. The CSSC and / or the core-shell nanoelement each have a temperature of 50°C and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or less, 5x10 6 mPa·s or less, 10 6 mPa·s or less, 5x10 5 mPa·s or less, 10 5 mPa·s or less, 5x10 4 mPa·s or less, 104 mPa·s or less, 5x10 3 mPa·s or less or 10 3 mPa·s or less first viscosity and / or second viscosity;
[0041] ix. the CSSC has a molecular weight of 0.7 kDa or more, 0.8 kDa or more, 0.9 kDa or more, 1 kDa or more, 2 kDa or more, or 5 kDa or more;
[0042] x. the CSSC has a molecular weight of 500 kDa or less, 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less; and
[0043] xi. The CSSC has a molecular weight between 0.6 kDa and 500 kDa, between 0.7 kDa and 300 kDa, between 0.8 kDa and 200 kDa, between 1 kDa and 100 kDa, or between 2 kDa and 80 kDa.
[0044] In some embodiments, at least one structural property satisfied by at least one of the CSSC and the core-shell nanoelements (optionally including plasticized CSSC) is: property i) listed above; property ii) listed above; property iii) listed above; property iv) listed above; property v) listed above; property vi) listed above; property vii) listed above; property viiii) listed above; property ix) listed above; property x) listed above; or property xi) listed above.
[0045] In some embodiments, at least two structural characteristics satisfied by at least one of the CSSC and the core-shell nanoelement are: characteristics i) and ii) listed above; characteristics i) and v); characteristics i) and vii); characteristics i) and viii); characteristics i) and xi); characteristics ii) and v); characteristics ii) and vii); characteristics ii) and viii); characteristics ii) and xi); characteristics v) and xi); characteristics vii) and xi); or characteristics viii) and xi).
[0046] In some embodiments, at least three structural characteristics satisfied by at least one of the CSSC and the core-shell nanoelement are: characteristics i), ii) and iii) listed above; characteristics i), ii) and v); characteristics i), ii) and vii); characteristics i), ii) and viii); characteristics i), ii) and xi); characteristics i), v) and vii); characteristics i), v) and viii); characteristics i), vii) and viii); characteristics i), v) and xi); characteristics i), vii) and xi); or characteristics i); or viii) and xi).
[0047] In a particular embodiment, the CSSC is a CSSP, the compound being a polymer formed from repeating structural units, the monomers being identical (forming a homopolymer) or different (forming a random or block copolymer). In another particular embodiment, the polymer of the CSSP is a thermoplastic polymer. While non-polymeric compounds typically have a molecular weight of up to 2 kDa, usually not exceeding 1 kDa, the CSSP can be a larger molecule of at least several kDa.
[0048] As used herein, the term "nano element" used for the core-shell structure containing (plasticized or non-plasticized) CSSC refers to a relatively solid (relatively solid) nanoparticle or a relatively liquid nanodroplet with an average diameter of 200nm or less, 150nm or less, 100nm or less, 75nm or less or 50nm or less, such structures (e.g., due to nanosizing) are dispersed in a uniform medium to form a nano suspension therein. Such core-shell nano elements typically have an average diameter of 2nm or greater, 5nm or greater, 10nm or greater, 15nm or greater, or 20nm or greater. In some embodiments, the average diameter of the core-shell nano elements of the composition according to the present teaching is between 2nm and 200nm, between 5nm and 150nm, between 10nm and 100nm, between 15nm and 75nm, or between 20nm and 50nm. The average diameter of the core-shell nanoelement may be determined by any suitable method, and may refer to the hydrodynamic diameter of the element as measured by dynamic light scattering (DLS), and is typically expressed by the number (D N 50) Identify 50% of the nanoelements.
[0049] Taking into account their intended use and / or preparation methods, CSSCs suitable for use in the present invention are advantageously, but not necessarily, relatively solid at room temperature (about 25° C.) and up to body temperature (e.g., about 37° C. for human subjects). These preferences extend to nanoelements and their cores comprising optionally plasticized CSSC, which further take into account the presence of fatty amines and / or non-volatile liquids and their relative amounts, or any other materials that affect the thermal behavior of the product. As will be understood by those skilled in the art, since CSSC can be a thermoplastic polymer, the "relative solid" of such materials at any particular temperature or the fact that such materials are "relatively solid" refers to the fact that they are not necessarily solid but rather exhibit viscoelastic behavior. Without wishing to be bound by any particular theory, this characteristic of CSSC should ensure that, to the necessary extent, nanoelements prepared therefrom are relatively non-sticky, thereby facilitating their uniform distribution in the composition according to the present teachings. From the perspective of skin penetration required for transdermal delivery, it is believed that the relatively malleable / deformable nature of the core (whether intentionally plasticized or not having a suitable viscosity as disclosed herein) facilitates the transfer of the nanoelements across the skin, where the pathway through the stratum corneum or down to the hair follicles or sweat glands is often narrow and tortuous.
[0050] The composition of the present invention is in the form of a nanosuspension. Depending on the Tm or Ts of the CSSC (plasticized in the core of the nanoelement or having the desired viscosity in its native form), the composition can be in the form of a nanodispersion at room temperature (i.e., if the Tm or Ts is above 20°C, for example between 25°C and 80°C), the core-shell nanoelement is a relatively solid nanoparticle, or the composition can be in the form of a nanoemulsion at room temperature (i.e., if the Tm or Ts is below 20°C), the core-shell nanoelement is a relatively liquid nanodroplet.
[0051] CSSC (e.g. CSSP) can be a natural compound, even if it is artificially synthesized, or a synthetic compound that does not occur naturally. In certain cases, some compounds suitable for the teachings of the present invention can be assembled to form larger molecules, which are then considered polymers. Before such connection is made, such compounds should be referred to as polymerizable.
[0052] In some embodiments, the polymerizable CSSC is a natural compound selected from the group consisting of resins, gums, gum-resins, and combinations thereof. In a specific embodiment, the polymerizable CSSC is shellac or rosin.
[0053] In other embodiments, the CSSC is non-polymerizable, such as a quinone, particularly ubidecarenone, also known as 1,4-benzoquinone or coenzyme Q10 (CoQ10).
[0054] In other embodiments, the CSSC is a CSSP, which may also be of synthetic or natural origin. In some embodiments, the thermoplastic polymer is a biodegradable polymer selected from the group of polymer families including: aliphatic polyesters such as polycaprolactone (PCL), polylactide (PLA), poly(L-lactide) (PLLA), poly(D-lactide) (PDLA), poly(D,L-lactide) (PDLLA), polyglycolic acid (PGA), poly(lactic-co-glycolic acid) (PLGA), and poly(p-dioxanone) (PPDO); polyhydroxyalkanoates such as polyhydroxybutyrate (PHB), poly-3-hydroxy-butyrate (P3HB), poly-4-hydroxybutyrate (P4HB), polyhydroxyvalerate (PHV), poly(3-hydroxybutyrate) ... Poly(butylene succinate-co-3-hydroxyvalerate) (PHBV), polyhydroxyhexanoate (PHH) and polyhydroxyoctanoate (PHO); poly(olefin dicarboxylates), such as poly(butylene succinate) (PBS), poly(butylene succinate-adipate) (PBSA) and polyethylene succinate (PES); polycarbonates, such as poly(trimethylene carbonate) (PTMC), polypropylene carbonate (PPC) and poly[oligo(tetramethylene succinate)-co(tetramethylene carbonate)]; aliphatic-aromatic copolyesters, such as poly(ethylene terephthalate) (PET) and poly(butylene adipate-terephthalate) (PBAT); isomers thereof, copolymers thereof and combinations thereof. Although some of the above polymers have natural counterparts, these exceptions are usually commercially available almost exclusively in artificially prepared forms, so that the entire group is generally considered to be representative of synthetic polymers.
[0055] Alternatively, the thermoplastic polymer may be a non-biodegradable synthetic polymer, such as polyamide (PA), polyethylene (PE), ethylene-acrylic acid copolymer (PEAA), ethylene-methacrylic acid copolymer (PEMAA), ethylene-n-butyl acrylate copolymer (PEBA), ethylene-vinyl acetate copolymer (PEVA), polymethyl methacrylate (PMMA), polypropylene (PP), polysiloxane, polystyrene (PS), polytetrafluoroethylene (PTFE), polyurethane (PU) or polyvinyl chloride (PVC). In a specific embodiment of this type, the CSSC as a non-biodegradable CSSP is selected from PA, PE, PEAA, PEMAA, PEBA, PEVA, substituted or modified forms thereof, ionomers thereof, and combinations thereof.
[0056] In other embodiments, the CSSP is a natural biodegradable polymer selected from the group consisting of polysaccharides, lignin, and combinations thereof.
[0057] In a specific embodiment, the CSSC is a biodegradable material, such as CoQ10, shellac, rosin, or a CSSP that is an aliphatic polyester. In a further specific embodiment, the aliphatic polyester of the CSSP is selected from polycaprolactone, polylactic acid, lactic acid-glycolic acid copolymer, butylene succinic acid-adipic acid copolymer, isomers thereof, copolymers thereof, and combinations thereof.
[0058] In some embodiments, the non-volatile liquid that can be added to the CSSC to reduce at least one of its first (native) viscosity, Tm, Tg, and Ts is selected from the group consisting of monofunctional and multifunctional aliphatic esters, fatty esters, cyclic organic esters, aromatic lipids, fatty acids, terpenes, aromatic alcohols, aromatic ethers, aldehydes, and combinations thereof. In some embodiments, the non-volatile liquid is an aliphatic or aromatic fatty ester. In a specific embodiment, the non-volatile liquid is selected from the group consisting of dibutyl adipate, dibutyl sebacate, triethyl citrate, C 12 -C 15 Alkyl benzoate and dicaprylyl carbonate.
[0059] In other embodiments, when the polymer is a non-biodegradable synthetic polymer, the non-volatile liquid may be additionally selected from the group comprising: mineral oil, natural oil, vegetable oil, essential oil, synthetic oil, and combinations thereof, provided that they meet the requirements of the present invention. Non-limiting examples of synthetic oils include synthetic isoparaffins (e.g., Isoparaffins, TM M and Isopra TM V) and C 12 -C 15 Alkyl ethylhexanoate, C 12 -C 15 alkyl benzoate or isononyl isononanoate, to name a few. Non-limiting examples of suitable vegetable oils include castor oil, corn oil, pomegranate seed oil, or avocado oil, to name a few. Non-limiting examples of essential oils include clove leaf oil, lavender oil, or oregano oil, to name a few. In some embodiments, the water-insoluble fatty amine is a primary, secondary, tertiary, or quaternary C8-C 22 A linear, branched or cyclic saturated or unsaturated aliphatic or aromatic, alkyl or aryl amine, including combinations thereof. A comprehensive list of fatty amines can be found in the Chemical Database, and the following compounds are only used to illustrate each class. 18 H 39 N) is an example of a straight-chain, saturated aliphatic primary alkylamine (general formula R-NH2), isostearylamine is its branched counterpart, and oleylamine (C 18 H 37N) in that an unsaturated bond is included in the alkyl chain of the same length. Dinonylamine is a secondary amine (general formula R1-NH-R2), and trioctylamine is a tertiary amine (N-R1, R2, R3). The fatty quaternary ammonium can be a quaternary ammonium salt or a cationic fatty imidazoline, the latter of which includes heterocyclic fatty amines. In some embodiments, the water-insoluble fatty amine is a primary, secondary, tertiary or quaternary C8-C 20 In a specific embodiment, the water-insoluble fatty amine is selected from oleylamine, octylamine, bis(2-hydroxyethyl)oleylamine, dodecyldimethyl tertiary amine (DMDA), hexadecyltrimethylammonium chloride (CTAC)) and combinations thereof.
[0060] In some embodiments, the polar carrier in which the core-shell nanoelement containing CSSC can be dispersed includes water, glycols (e.g., propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2-ethyl-1,3-hexanediol and 2-methyl-2-propyl-1,3-propanediol), glycerol, its precursors and derivatives, collectively referred to herein as "glycerols", (e.g., acrolein, dihydroxyacetone, glyceric acid, tartronic acid, epichlorohydrin, glycerol tert-butyl ether, polyglycerol, glycerol esters, glycerol carbonate) and combinations thereof. In specific embodiments, the polar carrier comprises, consists of or is water.
[0061] In some embodiments, the chemical identity of the material constituting the core and the material constituting the shell and the medium in which they are dispersed and the respective amount are set so that the core-shell nano element formed thus has a positive charge of +5mV or higher, +10mV or higher, +20mV or higher, +30mV or higher or +40mV or higher. In other embodiments, the core-shell nano element has a negative charge between -60mV to -5mV, between -50mV to -5mV, between -40mV to -5mV, between -30mV to -5mV or between -20mV to -5mV. In other embodiments, a charge close to neutrality is formed on the core-shell nano element, which is between -5mV to +5mV. The above-mentioned charge is measured in the presence of room temperature and water.
[0062] As known to those skilled in the art of measuring the charge and zeta potential of compositions, it is emphasized that in this particular context, the aqueous polar carrier need only contain water in an amount sufficient to promote protonation of the fatty amine of the shell (e.g., ≥ 5 wt%). These values, which can be measured with any suitable equipment, can be determined in the composition "as is" or in a diluted sample thereof. Depending on the nature of the amine group of the fatty amine, the pH that provides the most ideal charge can vary, and the aforementioned (e.g., positive) charge of the nanoelement can be observed at at least one pH in the range of pH 1 to pH 10, as can be initially estimated with suitable pH test strips and confirmed with a pH meter.
[0063] In some embodiments, in addition to the role of the fatty amine in forming the shell and optionally as a plasticizer, the fatty amine can also be used as a surfactant to stabilize the core-shell nanoelement in the nanosuspension. In this case, the composition may not require the addition of a surfactant in a polar carrier to stabilize the core-shell nanoelement in the liquid medium. This may be advantageous when the composition is applied to a surface such as the skin that may be sensitive to the presence of a surfactant.
[0064] In other embodiments, the skin (e.g., topical) composition further comprises at least one surfactant selected from an emulsifier and a hydrotrope. The surfactant (e.g., if CSSC-miscible and polar carrier-insoluble surfactant) may be present in the CSSC in the core of the core-shell nanoelement, or (e.g., if polar carrier-soluble surfactant) may also be present in the liquid phase containing the polar carrier, or (e.g., if intermediate emulsifier) may be present in both.
[0065] In some embodiments, the skin (eg, topical) composition further comprises at least one skin penetration enhancer. Such agents are typically present in the liquid phase in which the CSSC-containing nanoelements are dispersed.
[0066] In some embodiments, the skin (e.g., topical) composition further comprises an active agent within the core comprising the CSSC, the active agent being miscible with the CSSC and being substantially insoluble in the polar carrier (hence, a "carrier-insoluble active agent"). The carrier-insoluble active agent can be a mixture of different agents, each having the same or different activity.
[0067] In some embodiments, the skin (e.g., topical) composition further comprises an active agent that forms a second shell on the surface of the core-shell nanoelement, the active agent being soluble in the polar carrier (hence, referred to as a "carrier-soluble active agent"). In some embodiments, the second shell consists of at least one layer of carrier-soluble active agent. Nanoelements comprising a CSSC core (optionally comprising a CSSC miscible / polar carrier-insoluble surfactant and / or active agent), a first shell of a fatty amine, and at least one second shell of a carrier-soluble active agent can be referred to as core-multiple shells or core-multi-shell nanoelements.
[0068] Advantageously, the first shell of the core-multi-shell nanoelement, which is positively charged in the aqueous polar carrier of the composition, promotes the non-covalent formation of the second shell, for example by electrostatic interaction with the carrier-soluble active agent, which is negatively charged in the polar carrier. In this case, the nanoelement, which previously had a single shell of a fatty amine and was positively charged in the medium under consideration, can become less positively charged, electrostatically neutral or negatively charged. Additionally or alternatively, the first shell of the fatty amine can form a covalent bond with the second shell of the carrier-soluble active agent, thereby promoting their indirect attachment to the core.
[0069] Preferably, the second shell is covalently or non-covalently wrapped around the first shell such that the size of the nanoelements does not increase beyond the size range disclosed herein as being suitable when transdermal delivery is intended.
[0070] In some embodiments, the core-shell nanoelement has a first surface zeta potential (ζ1) and the carrier-soluble active agent has a second zeta potential (ζ2), whereby the absolute value of the zeta potential difference (Δζ) defined as Δζ=|ζ2-ζ1| is at least 5 mV, as measurable in the presence of water. These values can be determined as described for the charge of the core-shell nanoelement, with the conditions (e.g., equipment, temperature, and pH) selected for the measurement being the same for the nanoelement and the carrier-soluble active agent.
[0071] As used herein, a material is considered insoluble in a liquid carrier, e.g., a "polar carrier-insoluble active agent" (or "carrier-insoluble active agent"), if its solubility in the carrier in which it is immersed is less than 5 wt % (and more typically, less than 4 wt %, less than 3 wt %, less than 2 wt %, less than 1 wt %, or less than 0.5 wt %) at a temperature of 20°C based on the weight of the polar carrier.
[0072] Conversely, a material is considered soluble in a liquid carrier, e.g., a "polar carrier-soluble active agent" (or "carrier-soluble active agent"), if its solubility in the carrier in which it is immersed at a temperature of 20°C is 5% by weight or more (and more typically 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, or 10% by weight or more) based on the weight of the polar carrier. As will be appreciated by those skilled in the art, some materials having the sought activity may be polar carrier-insoluble in one chemical form and polar carrier-soluble in another chemical form, and salts of the material generally increase its solubility.
[0073] In some embodiments, the dermatological (e.g., topical) composition includes more than one active agent in addition to the CSSC, which are in the same phase or in different phases. For illustrative purposes, a first active agent that is carrier-insoluble can be contained within the core of the nanoelement, and a second active agent that is carrier-soluble can form a second shell surrounding the first shell of the fatty amine.
[0074] The active agents that can be incorporated into the core-shell nanoelements of the present disclosure can have cosmetic or pharmaceutical purposes, for example, having one or more activities selected from the group including: analgesia, anesthetic, anti-acne, anti-aging, anti-arthritis, anti-bacterial, anti-dandruff, anti-fungal, anti-inflammatory, antioxidant, anti-parasitic, anti-rheumatic, anti-viral, immunomodulatory, promotion or inhibition of hair growth, skin bleaching or tanning, and any similar cosmetic or therapeutic activity that is beneficial to the skin or the treatment of skin conditions on the skin surface, in the skin layer or under the skin.
[0075] As used herein, the term "treatment" and its grammatical variants include preventing, ameliorating, attenuating, slowing or arresting the progression and curing the condition being treated; or the efficacy of a co-administered treatment for the same condition may be increased. For example, if a subject receives an autologous or allogeneic skin graft, a xenograft, or a synthetic skin substitute for the treatment of a skin wound, the composition of the present invention may improve the value of such treatment by promoting new synthesis of skin proteins in the transplanted area and / or by providing an immunosuppressant locally to promote the acceptance of the graft. In some embodiments, the extent of treatment or co-treatment as exemplified above may be assessed by the reduction of symptoms associated with the condition being treated.
[0076] Advantageously, the skin (e.g., topical) compositions of the present invention can have a relatively high concentration (e.g., 1 wt % or more) of CSSC (e.g., CSSP) and / or a relatively high concentration of an optional active agent (e.g., retinol or HA) compared to conventional topical compositions comprising such ingredients, and / or the CSSC and / or the optional active agent can have a relatively high molecular weight. Without wishing to be bound by theory, a relatively high loading of the CSSC and / or the optional active agent and / or its relatively high potency (when dependent on MW) is expected to provide a higher concentration gradient, facilitating transdermal delivery and ultimately cosmetic or pharmaceutical efficacy.
[0077] Notably, the inventors unexpectedly discovered that nanoparticles or nanodroplets of CSSC having a particle size within the size range disclosed herein are successful because CSSC in this form, especially if plasticized CSSP, would be expected to aggregate together given its expected viscosity.
[0078] In a third aspect of the present disclosure, there is provided a method for preparing a composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelement composition comprising a water-insoluble CSSC in the core, the method comprising the following steps:
[0079] a) providing at least one water-insoluble CSSC, wherein the or each CSSC:
[0080] i. having a molecular weight of at least 0.6 kDa;
[0081] ii. having at least one of a first Tm, Ts, or Tg of 300°C or less; and
[0082] iii. having optionally more than 10 7 The first viscosity in mPa·s, such as at 50°C and 10 sec -1 Measured at a shear rate of
[0083] b) mixing the at least one CSSC with at least one water-insoluble fatty amine and a non-volatile liquid miscible with the CSSC, the mixing being carried out at a mixing temperature equal to or higher than at least one of the first Tm, Ts or Tg of the CSSC, thereby forming a homogeneous mixture comprising the fatty amine and the plasticized CSSC, the mixture having a second Tm, Ts or Tg lower than the corresponding first Tm, Ts or Tg, and a second viscosity lower than the first viscosity, the second viscosity being 0.0447 W / m at 50°C and 10 sec -1 The shear rate was measured at 10 7 mPa·s or lower;
[0084] c) combining the mixture of step b) with a polar carrier; and
[0085] d) nanosizing the combination of step c) by applying shear at a shear temperature equal to or higher than at least one of said second Tm, Ts or Tg to obtain a nanosuspension, whereby core-shell nanoelements consisting of a core comprising a plasticized CSSC and a shell comprising at least a hydrophilic part of a water-insoluble fatty amine surrounding said core are dispersed in a polar carrier;
[0086] The nanoelements have an average diameter (e.g., D N 50).
[0087] The materials mixed with the CSSC in step b) should be miscible with it (and any other ingredients constituting the mixture). If they are intended to be introduced into the core of the nanoelement of the present invention, they are generally insoluble in polar carriers to avoid their leaching when not desired. However, if release of the ingredients from the core is expected, or if their expected leaching can be prevented by including a certain amount of ingredients that produce a blocking gradient in the liquid phase, this former property of the ingredients is not necessary. A material is said to be CSSC miscible if it is able to form a homogeneous mixture with the CSSC without causing phase separation or any other similar changes in the mixture due to the formation of a continuous core.
[0088] In some embodiments of the third aspect, the second Tm, Ts or Tg of the plasticized CSSC is at least 5°C, at least 10°C, at least 15°C, at least 20°C, at least 25°C, at least 30°C, at least 35°C, at least 40°C, at least 45°C or at least 50°C lower than the respective first Tm, Ts or Tg of the CSSC.
[0089] In some embodiments of the third aspect, the mixing temperature in step b) is 5°C or more, 10°C or more, 20°C or more, 30°C or more, or 40°C or more above at least one of the first Tm, Ts, or Tg of the CSSC, as long as the mixing is performed at a temperature at which only a negligible portion of the fatty amine and the non-volatile liquid are evaporated. Assuming that the fatty amine has a boiling temperature Tb at the pressure of the mixing step a , and the non-volatile liquid has a boiling temperature Tb l , then in some embodiments, the mixing temperature may be further below the boiling temperature Tb of the fatty amine. a and the boiling temperature Tb of the non-volatile liquid l When the duration of mixing is short enough and / or the amount of fatty amine and / or non-volatile liquid is in excess, the mixing temperature may alternatively be the boiling temperature Tb. a , Tb l or higher.
[0090] In a fourth aspect of the present disclosure, there is provided a method for preparing a composition comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements comprise water-insoluble CSSC in the core, the method comprising the following steps:
[0091] a) providing at least one water-insoluble CSSC, wherein the or each CSSC:
[0092] i. having a molecular weight of at least 0.6 kDa;
[0093] ii. having at least one of a first Tm, Ts, or Tg of 300°C or less; and
[0094] iii. With 50℃ and 10sec -1 The shear rate was measured at 10 7 a first viscosity of mPa·s or less;
[0095] b) mixing the at least one CSSC with at least one water-insoluble fatty amine at a mixing temperature equal to or greater than at least one of a first Tm, Ts or Tg of the CSSC, thereby forming a homogeneous mixture comprising the CSSC and the fatty amine;
[0096] c) combining the mixture of step b) with a polar carrier; and
[0097] d) nanosizing the combination of step c) by applying shear at a shear temperature equal to or higher than at least one of the first Tm, Ts or Tg of the CSSC to obtain a nanosuspension, thereby dispersing core-shell nanoelements consisting of a core comprising the CSSC and a shell comprising at least a hydrophilic part of a water-insoluble fatty amine, said shell surrounding said core in a polar carrier;
[0098] The nanoelements have an average diameter (e.g., D N 50).
[0099] Advantageously, the aforementioned method does not require the water-insoluble CSSC to be dissolved in a solvent that is a VOC, nor does it require the addition of VOCs for any other reason, so that the nanoelements obtained by the present method can, in some embodiments, have a relatively low VOC weight percentage content based on the weight of the nanoelements, as detailed for the composition.
[0100] In some embodiments of the third and fourth aspects, the CSSC provided in step a) is biodegradable and / or biocompatible.
[0101] In some embodiments of each of the third and fourth aspects, the shear temperature is 5°C or more, 10°C or more, 20°C or more, 30°C or more, or 40°C or more higher than the second Tm, Ts or Tg of the mixture including the plasticized CSSC (or higher than the first Tm, Ts or Tg in the case of the unplasticized CSSC), provided that the nanosizing is performed at a temperature or any other condition at which an insignificant portion of the polar carrier is evaporated. Assuming that the polar carrier has a boiling point Tb at the pressure of the nanosizing step c , then in some embodiments, the shear temperature may be further greater than the boiling point Tb of the fatty amine. a and / or the boiling point Tb of the non-volatile liquid (if added) l and / or a boiling point Tb of the polar support at the pressure at which the nanosizing step is performed.c 5°C or more, 10°C or more, 20°C or more, 30°C or more, or 40°C or more lower. When the duration of nanosizing is short enough and / or the polar carrier is in excess, the nanosizing temperature may alternatively be the boiling temperature Tb c or higher.
[0102] In some embodiments of each of the third and fourth aspects, the resulting nanosuspension is a nanoemulsion, and the method includes an additional step in which the resulting nanoemulsion is cooled to a temperature below at least one of the first or second Tm, Ts or Tg of the CSSC or a mixture containing the CSSC. Although such cooling can occur passively when nanosizing is terminated, the temperature of the nanosuspension naturally decreases to room temperature (or, if desired, a lower storage temperature) over time, in some embodiments, the cooling is performed by actively reducing the temperature of the nanoemulsion by any suitable cooling method. Additionally or alternatively, the cooling is performed under continuous shear or any other method while maintaining the stirring of the composition. Although the composition can remain a nanoemulsion after active or passive cooling, in some embodiments, the composition can subsequently form a nanodispersion.
[0103] In some embodiments of the third and fourth aspects, a surfactant is added during step b) and / or during step c), the surfactant being an emulsifier or a hydrotrope, as described herein.
[0104] In some embodiments of the third and fourth aspects, the polar carrier is not water, and the method further comprises the step of replacing at least a portion of the polar carrier with water.
[0105] In some embodiments of each of the third and fourth aspects, the method further comprises combining at least one CSSC miscible / polar carrier insoluble active agent with CSSC and a water-insoluble fatty amine (including optional non-volatile liquids and / or surfactants, if present), the combination being performed by a) simultaneously mixing the CSSC with the water-insoluble fatty amine and the non-volatile liquid and / or at least one surfactant (if applicable); b) by mixing the CSSC miscible / polar carrier insoluble active agent with plasticized CSSC (when applicable) prior to combining the CSSC with the polar carrier; or c) simultaneously mixing the CSSC (optionally plasticized) pre-combined with the fatty amine with the polar carrier, or nano-sizing the components of the composition, the polar carrier insoluble active agent being either in the nanoelements (if added as in a) or b)) or separately dispersed in the polar liquid phase (if added as in c)).
[0106] In some embodiments of each of the third and fourth aspects, the method further comprises adding at least one polar carrier-soluble active agent to the nanosuspension of the core-shell nanoelement obtained in step d) and mixing the two, thereby forming a second shell comprising a carrier-soluble active agent on the surface of the core-shell nanoelement. Such nanoelement may be referred to as an active agent-coated core-shell nanoelement, a core-multiple shell nanoelement or a core-multiple shell nanoelement. Depending on the tolerance of the active agent to the temperature, mixing or shear conditions applied in the intended step, the addition of these active agents may be performed at various steps during the preparation of the composition. Relatively resistant active agents may be added a) while being combined with a polar carrier, CSSC and a fatty amine mixture (optionally including additional CSSC miscible components, such as non-volatile liquids); or b) while nanosizing the composition components to obtain a core-shell nanoelement comprising CSSC and a water-insoluble fatty amine. Alternatively, a polar carrier-soluble active agent (particularly if shear sensitive) may be added to the resulting nanosuspension, and relatively heat-sensitive agents are preferably combined with a nanoemulsion or nanodispersion after cooling.
[0107] In some embodiments of the third and fourth aspects, the formation of the second shell requires that the core-shell nanoelement be positively charged so that the negatively charged polar carrier soluble active agents can be electrostatically attracted to them, thereby arranging around and encapsulating the core-shell nanoelement.
[0108] When the negative charge or positive charge of the core-shell nanoelement in the polar carrier is insufficient to attract the compound with the opposite charge due to the formation of the second shell, the method may further include adding a pH adjuster in an amount suitable for increasing the charge of the core-shell nanoelement (e.g., increasing the positive charge) while maintaining the negative charge of the carrier-soluble active agent. The pH adjuster can be an acid or a base according to the functional groups present on the fatty amine molecules of the first shell, and an acidic pH adjuster is generally preferred.
[0109] Regardless of the number of shells present or to be formed on the core, it may be desirable to adjust the charge of the nanoelements in the skin composition according to the present teachings. Without wishing to be bound by any particular theory, it is expected that the charge of the nanoelements affects their distribution on the skin, thus affecting their relative efficacy. It is believed that relatively more positively charged nanoelements tend to remain on or near the skin surface, while relatively less positively or more negatively charged nanoelements may have a relatively higher tendency to penetrate the skin layer towards the lowermost boundary of the skin.
[0110] The charge of the nanoelements may depend on the materials from which they are composed, and in particular on the pH conditions they are in. In some embodiments, the pH adjusting agent is added in an amount that results in the composition having a pH between 1 and 10, between 1 and 9, between 1 and 8, between 2 and 7, or between 2 and 5. In specific embodiments, the pH adjusting agent is added in an amount that results in the composition having a pH of 7 or less, 6 or less, 5 or less, or 4 or less.
[0111] Although pH adjusting agents are typically added to the liquid carrier in which the nanoelements are dispersed, they may alternatively or additionally be added to the nanoelements, for example incorporated into their cores, regardless of the number of shells that may surround them. pH adjusting agents suitable for incorporation into the core (from which they will desirably leach within an appropriate time) should be miscible and compatible therewith.
[0112] In some embodiments of each of the third and fourth aspects, the method further includes combining a first active agent that is miscible with CSSC and insoluble in a polar carrier with CSSC and a fatty amine, the combination being performed as above, and adding a carrier-soluble second active agent as described above to the polar carrier, the composition thus prepared including the first active agent in the CSSC-containing core of the nanoelement and the second active agent forming a second shell of the nanoelement surrounding the first shell of the fatty amine.
[0113] In some embodiments of the third and fourth aspects respectively, the method further comprises adding a skin penetration enhancer to the polar carrier phase of the nanosuspension. The interpolation of this skin penetration enhancer can be carried out in each step in the preparation process of the skin composition, and is generally as described above, so as to be combined with an activating agent that is soluble in a polar carrier.
[0114] In some embodiments of each of the third and fourth aspects, the CSSC, water-insoluble fatty amine, polar carrier, and if necessary, non-volatile liquid, surfactant, skin penetration enhancer, carrier-insoluble active agent and carrier-soluble active agent used to prepare the composition are substantially as described above and in detail herein.
[0115] It should be noted herein that, although for simplicity, compounds have been classified according to their primary role in the present invention, particularly with respect to the preparation method, these functions are not mutually exclusive. For illustrative purposes, fatty amines that are typically used to form the first shell can also be used to plasticize CSSC, and fatty amines and / or non-volatile liquids can also be used as surfactants for nanoelements. Once the composition is applied to the skin, a polar carrier (e.g., diol) used as a liquid medium for dispersed nanoelements or a surfactant (e.g., urea) intended to increase the dispersibility of the nanoelements can also additionally act as a skin penetration enhancer. The advantage of one role over another may depend on the inherent effectiveness of the material in its respective field, but also on the relative presence of the material in the composition. For example, a material is considered to be a carrier if it constitutes a sufficiently large portion of the liquid phase (e.g., greater than 20% by weight), while if its amount is relatively low, it can be considered to achieve a unique function, and such an amount is more suitable for its secondary role.
[0116] In some embodiments, the skin compositions of the present invention may be prepared according to the methods disclosed herein, and may further comprise any additives conventionally found in such compositions.
[0117] Although for illustration, the compositions and methods of the present invention are described for skin compositions intended for activities related to the skin, such as products for improving skin appearance and / or health, this should not be construed as limiting. The skin compositions according to the present teachings can additionally be used for transdermal delivery of active agents targeting non-skin organs or non-skin specific disorders, or they can be used to protect the skin from external factors. These additional agents can also be incorporated into the compositions of the present invention, if relatively insoluble in water, in the core of the nanoelement, or if relatively soluble in water, in the shell. Therefore, the skin compositions of the present invention can be more broadly considered for the preparation of veterinary products for the treatment of non-human animals or drugs for the treatment of human subjects.
[0118] In addition, the surface that the present composition can be applied is not limited to the skin of living body. Considering that in some embodiments, the composition of the present invention can be used for delivering active agent by releasing from the core of its core-shell nano element, the surface processed with it can be inert object or can be the surface (except skin) of environment or living body subject in addition. In order to illustrate the previous situation, the composition can be applied to the surface of building (or its inert content, such as furniture or textiles), and the composition is for example used for releasing pesticide over time. In this case, the composition can be considered as industrial composition.
[0119] Alternatively, the active agent released from the composition of the present invention may be an agrochemical, in which case the treatable surface may be the external surface of a plant or pest, or soil or water in which the plant grows or the pest is present, and the composition may be considered an agrochemical composition. These agents may further be used to protect inanimate surfaces for industrial use.
[0120] All compositions, regardless of end use, and all surfaces that can be treated therewith according to the active agents present in the core and / or on the shell of the core-shell nanoelements are included.
[0121] In a fifth aspect of the present disclosure, there is provided a use of a composition of the present invention for the preparation of a medicament for use in a cosmetic, an agrochemical, an industrial product, a veterinary product, or a treatment of a human subject, the composition being applied externally to a surface to be treated therewith, the composition comprising core-shell nanoelements dispersed in a polar carrier according to the present teachings including the aspects and embodiments described herein.
[0122] In some embodiments, the product is a cosmetic, the surface treated with it is skin, and the composition is a cosmetic composition for achieving a cosmetic effect of improving skin appearance (especially by stimulating the nascent synthesis of skin structural proteins such as collagen, elastin or glycosaminoglycans, and / or for preventing their degradation) and / or for treating signs of skin aging, anti-wrinkles and fine lines, anti-skin dryness, anti-skin sagging, anti-skin thinning, anti-skin dullness, anti-skin pigmentation unevenness, or anti-skin elasticity and / or tension deficiency, and any similar skin conditions where CSSC and / or active agents are known to have beneficial cosmetic activity. The cosmetic effect can be derived from the presence of a cosmetic active agent in the core-shell nanoelement, and visually detectable activity is, for example, skin bleaching or tanning. Such cosmetics and their uses are generally intended to be applied to the skin of human subjects.
[0123] In other embodiments, the product is a veterinary product or a drug, the surface treated with it is the skin of a non-human animal or a human subject, respectively, and the composition is a pharmaceutical composition for achieving a pharmaceutical effect. The pharmaceutical effects include improving skin health (and often also improving skin appearance), including, but not limited to, treating chronic skin diseases, skin injuries, restoring skin integrity (optionally accelerating or providing skin nerve regeneration and / or angiogenesis), promoting wound or surgical incision healing, promoting skin grafts, reducing or treating at least one of local skin inflammation, skin irritation, skin infection, rash, skin pain, skin burns, skin swelling and / or skin allergies; promoting or inhibiting hair growth or dandruff; and any similar condition that directly or indirectly affects the skin for which CSSC and / or active agents are known to have beneficial therapeutic activity.
[0124] In alternative embodiments, the skin itself is not treated, but rather used as a substrate, and the core-shell nanoelement includes an agent that protects the skin from external factors, whether living, physical or chemical. To illustrate, the nanoelement may include an insect repellent, a UV sunscreen, or a protective agent for a neurotoxin. Such an agent may be considered a medicament.
[0125] Pharmaceutical composition of the present invention can also be used for treating organs except skin, and is delivered by skin simultaneously.In this case, core-shell nano element also contains the activating agent that is suitable for delaying, alleviating, preventing or treating transdermal treatable illness usually.In some embodiments, the effect that can be realized according to the activating agent present in the pharmaceutical composition can be such as ADHD relief effect, the neuroprotective effect (for example, activating agent effectively resists amyotrophic lateral sclerosis (ALS), Alzheimer's disease, Huntington's disease, Parkinson's disease and similar illness of nervous system) for treating neurodegenerative disease or its symptom, analgesic effect, anthelmintic effect, anti-addiction withdrawal effect, antianginal effect, antiarthritis effect, antidepressant effect, antiemetic effect, antipsychotic effect, antirheumatic effect, antiepileptic effect, anticonvulsant effect, blood pressure regulating effect, contraceptive effect, glaucoma relief effect, hormone replacement effect, thyroid regulation effect and the protective effect preventing nerve poisoning.
[0126] The skin to which the cosmetic or pharmaceutical composition may be applied may be found on any relevant part of the body, such as on the face, scalp, trunk, or extremities.
[0127] In other embodiments, the product is an agrochemical and / or industrial product, the surface treated therewith is an inert object, a plant or a pest surface, or soil or water in which a plant grows or a pest is present, and the composition is an agrochemical composition or an industrial composition. The effects that these compositions can achieve can be as acaricides, algaecides, insect repellents, moth repellents, avicides, bactericides, chemosterilants, fertilizers, fungicides, herbicides, insecticides including ovicides, insect repellents, insect pheromones, molluscicides, nematicides, nitrification inhibitors, insecticides, pest repellents, plant growth promoters, rodenticides, soil fertilizers, termiticides, virucides and plant wound protectants.
[0128] Additional objects, features and advantages of the present disclosure will be set forth in the following detailed description, and in part will be apparent to those skilled in the art from the description, or recognized by practicing the present disclosure as described in the written specification and its claims and the accompanying drawings. Various features and subcombinations of the embodiments of the present disclosure may be employed without reference to other features and subcombinations. BRIEF DESCRIPTION OF THE DRAWINGS
[0129] Some embodiments of the present disclosure will now be further described by way of example with reference to the accompanying drawings, in which like reference numerals or characters indicate corresponding or similar parts. Figure 1 The accompanying drawings are for the purpose of illustrative discussion and do not attempt to show the structural details of the embodiments in more detail than is necessary for a basic understanding of the present disclosure. For the sake of clarity and ease of description, some objects depicted in the accompanying drawings are not necessarily shown to scale.
[0130] In the attached picture:
[0131] Figure 1 depicts a simplified schematic diagram of a method for preparing a core-shell nanoelement according to an embodiment of the present teachings;
[0132] Figure 2 shows the particle size distribution of core-shell nanoelements prepared according to the present teachings, measured by dynamic light scattering (DLS) and expressed as number per;
[0133] Figure 3 Schematic representation of an uncharged core-shell nanoelement in a non-aqueous polar support;
[0134] Figure 4 A positively charged core-shell nanoelement surrounded by a shell formed by active agent molecules is schematically shown;
[0135] Fig. 5A CryoTEM images showing nanodispersions prepared according to the teachings of the present invention comprising core-shell nanoparticles surrounded by a second shell of a carrier soluble active agent;
[0136] Figure 5B CryoTEM image showing a nanodispersion comprising core-shell nanoparticles surrounded by a second shell that has undergone partial coalescence;
[0137] Fig. 6A is a histological photograph of a cross section of pig ear skin treated with the skin composition of the present invention taken with a fluorescence microscope at ×10 magnification, the test sample comprising a core-shell nanoelement containing a fluorescent marker in its core;
[0138] Figure 6B is a cross-sectional tissue diagram of pig ear skin treated with the skin composition of the present invention, wherein the test sample includes core-multi-shell nanoelements containing fluorescent markers in their cores, and the diagram is similar to Fig. 6A Shoot similarly;
[0139] Figure 6Cis a cross-sectional tissue image of pig ear skin treated with the skin composition of the present invention, the test sample comprising core-multi-shell nanoelements containing fluorescent markers in their cores, the image being taken at ×20 magnification; and
[0140] Fig.6D is a histopathological photograph of a cross section of pig ear skin treated with a control composition without a fluorescent marker, which is similar to Fig. 6A and 6B Shoot similarly. DETAILED DESCRIPTION
[0141] The present invention relates to a composition (e.g. for skin) comprising a core-shell nanoelement, such as a nanoparticle or a nanodroplet, comprising a core consisting of a water-insoluble compound (in short, CSSC or CSSP) capable of stimulating the new synthesis of structural skin proteins such as collagen, elastin or glycosaminoglycans and / or capable of inhibiting the processes leading to their degradation, and a shell of at least one fatty amine surrounding the core, the fatty amine interacting non-covalently with the CSSC, the nanoelement being dispersed as a nanosuspension in a polar carrier. Advantageously, the CSSC has a molecular weight of 0.6 kDa or more and can be plasticized or swelled, if desired, with a non-volatile liquid, which can also be referred to as a plasticizer or swelling agent. The core-shell nanoelement can provide the desired skin effect by itself, either due to the activity of the CSSC itself or due to its combination with a carrier-insoluble active agent in the core. The nanoelement may alternatively or additionally serve as an anchor or nanocarrier for other cosmetically or pharmaceutically active agents which are carrier soluble and which may form a second shell on the surface of the nanoelement surrounding the first shell of the fatty amine.
[0142] When applied to the skin, the nanoelement contained in the composition can remain on the surface of the skin or penetrate the skin barrier to varying degrees, and in particular provide an anti-wrinkle effect or any such effect that restores the appearance of the skin, which is at least partially due to the ability of the CSSC in the core of the nanoelement to maintain the presence of sufficient collagen in the skin. If an active agent added as part of the core and / or forming a second shell is selected as a cosmetic agent with a cosmetic effect similar to that of the core-shell, the initial cosmetic effect that the CSSC alone may provide (e.g., promoting an anti-wrinkle effect) can be enhanced. However, the cosmetic agent of the core (if the carrier is insoluble) or the second shell (if the carrier is soluble) can provide a different cosmetic effect, the effect of the core-(multi) shell nanoelement combining the core CSSC and the cosmetic agent (e.g., the second shell). As described above, the active agent can be used alternatively for a more therapeutic target and can be similarly added as part of the core or as a second shell.
[0143] The composition may include any other desired compound, such as any material miscible with the core or any shell of the core-(multi)shell nanoelement, to enable or increase the dispersibility of the nanoelement in the composition, to adjust their charge or to be suitable for increasing its stability over time and / or any other property that further enhances or changes the biological activity of the composition. Surfactants, activity modifiers and / or skin penetration enhancers may be present in the polar carrier (if soluble in the polar carrier). Methods for preparing such compositions and uses thereof (e.g., for cosmetic or pharmaceutical effects) are also disclosed.
[0144] Before explaining at least one embodiment in detail, it should be understood that the disclosure is not necessarily limited to the details of the construction and arrangement of the components and / or methods set forth herein in its application. The disclosure can have other embodiments or can be practiced or executed in various ways. The wording and terminology used herein are for descriptive purposes and should not be considered restrictive.
[0145] It should be understood that the foregoing general description and the following detailed description, including materials, methods, and embodiments, are merely exemplary of the disclosure and are intended to provide an overview or framework for understanding the nature and character of the invention and are not intended to be necessarily limiting.
[0146] Biological Activities of CSSC
[0147] The CSSC that can be used in the present invention is selected based on its ability to promote the formation of collagen (or any other skin structural protein) in the skin and / or prevent its degradation. Without wishing to be bound by any particular theory, it is believed that such compounds, when applied and penetrated into the skin, or injected into the skin, can trigger biological signals, ultimately leading to the new synthesis of skin structural proteins. These compounds can be biodegradable, such as biodegradable polymers, in which case the CSSC can be decomposed by certain biological mechanisms and cause local inflammation. This process may induce the formation of skin proteins such as collagen to heal the inflamed area, and this newly synthesized collagen also contributes to the firmness of the skin. Alternatively, the CSSC may be non-biodegradable, triggering a similar effect of skin protein (such as collagen) formation or protection, and subsequently healing the treated area without the need for compound degradation.
[0148] In view of its intended use, the CSSC is preferably biocompatible and generally biodegradable in a physiological environment, such as found after its application to the skin and its transdermal delivery. Suitable CSSCs may also be referred to as bioresorbable or bioabsorbable in general literature, depending on their fate in the body and their expected elimination from the body, but for simplicity, all such compounds are generally referred to as "biodegradable" herein. It is said that if the CSSC decomposes relatively quickly after achieving its purpose (e.g., by bacterial decomposition processes in the environment or by enzymatic or metabolic processes in the body) to produce natural byproducts, it is biodegradable. Biodegradable CSSCs are known, and new CSSCs are being developed. Their relative biodegradability in various environments can be evaluated by a variety of methods, and procedures based on standards such as ASTM F1635 or modified according to these standards can be adopted according to the conditions of interest.
[0149] Although it tends to decompose naturally under appropriate physiological conditions, a biodegradable CSSC suitable for the present invention should be sufficiently stable and durable for its intended use during storage and application, which may be particularly challenging if such use involves conditions that enhance biodegradability. For example, spreading a topical composition containing CSSC on the skin as a thin layer is expected to form a high surface area, which may increase the exposure of the resulting film to factors that promote degradation of the CSSC (e.g., light, chemicals, or microorganisms) before the CSSC is able to penetrate the skin and reach its target, and therefore, the selection of a suitable CSSC for the skin (e.g., topical) composition of the present invention should take these factors into consideration.
[0150] Since the compounds encompassed by the term CSSC may additionally be used for delivery or release on surfaces in connection with non-dermatological (e.g., agrochemical or industrial) products other than skin active agents, it should be understood that in such a context no actual promotion of the synthesis of skin structural proteins is contemplated. The term CSSC should then be understood more generally to refer to thermoplastic compounds satisfying the characteristics described in the context of CSSC, which are more particularly suitable for the skin.
[0151] Insoluble
[0152] In addition to their possible biodegradability, the CSSCs are preferably substantially insoluble in the liquid phase of the composition comprising the polar carrier (eg water) in which they are dispersed as nanoelements.
[0153] As used herein, the solubility of a material (e.g., CSSC, fatty amine, nonvolatile liquid, or active agent) refers to the amount of such component that can be introduced into a liquid (e.g., polar) carrier while maintaining clarity of the liquid medium. The solubility of a particular component of a composition in any particular liquid is typically assessed in the polar carrier alone, in the absence of any other possible components of the composition, but may alternatively be determined relative to the final composition including the liquid phase of the carrier.
[0154] CSSC (or any other material of interest in the present invention) is considered insoluble if its solubility in a polar carrier or in a liquid phase containing a polar carrier is 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, or 0.1% or less by weight of the carrier or liquid phase. For illustrative purposes, a material insoluble in a polar carrier will dissolve in an amount of no more than 5 g in 100 g of the carrier. This significant insolubility, while typically measured at room temperature, should preferably apply to any temperature at which these ingredients are mixed and processed, i.e., the solubility of these compounds in the polar carrier should remain within the desired range even at relatively elevated temperatures. Materials that meet these conditions may be referred to as "polar carrier insoluble" materials.
[0155] This insolubility of the material is expected to prevent or reduce the leaching of one or more CSSCs (or any other component of the core of the nanoelement) into its surrounding medium. If the material is soluble in the polar carrier, such leaching may affect the relative proportions of the components of the nanoelement, their size or any other such parameter that may ultimately adversely affect the efficacy of the composition.
[0156] Regardless of the composition of the polar liquid phase including the polar carrier in which the nanoelements are dispersed, CSSC can be characterized first as being insoluble in water (ie, typically having a solubility in water of less than 5 wt % at room temperature).
[0157] Molecular weight
[0158] Advantageously, the present invention allows for the delivery of core-shell nanoelements comprising CSSCs having relatively high molecular weights compared to compounds that can typically penetrate the skin barrier sufficiently to exhibit any efficacy. CSSCs suitable for the compositions, methods and uses of the present invention may have a molecular weight (MW) of 0.6 kDa or greater, 0.7 kDa or greater, 0.8 kDa or greater, 0.9 kDa or greater, 1 kDa or greater, with CSSPs also exhibiting molecular weights of 2 kDa or greater, 5 kDa or greater, or 10 kDa or greater. Typically, if the compound is not a polymer, although polymerizable compounds may be larger, their molecular weight does not exceed 2 kDa, with CSSPs reaching MWs of up to 500 kDa, and typically 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less. In another embodiment, the molecular weight of CSSC is 0.6 kDa to 500 kDa, 0.7 kDa to 300 kDa, 0.8 kDa to 200 kDa, 1 kDa to 100 kDa, or 2 kDa to 80 kDa.
[0159] The term "molecular weight" (or "MW") as used herein refers to the actual molecular weight that can be calculated for a non-polymeric CSSC, which can also be expressed in grams per mole, or to the weight average molecular weight of a polymerizable CSSC or CSSP, which can be a blend of polymers each containing slightly different numbers of repeat units, the weight average molecular weight of the polymers typically being expressed in Daltons.
[0160] The molecular weight of CSSC can be provided by its supplier and can be independently determined by standard methods including, for example, gel permeation chromatography, high pressure liquid chromatography (HPLC), size exclusion chromatography, light scattering or matrix-assisted laser desorption / ionization time-of-flight mass spectrometry MALDI-TOF MS, some of which are described in ASTM D4001 or ISO 16014-3.
[0161] These general rules regarding molecular weights exemplified for CSSC can be applied to any other component of the composition, whether polymeric or not, and in some embodiments, the active agent added to the core and / or shell of the nanoelement can also be a relatively large molecule having a MW of 0.6 kDa or higher, as well as any other values specifically recited for CSSC.
[0162] Characterization temperature
[0163] While most non-polymeric compounds can be characterized by a melting temperature (Tm), the temperature at which they transition from a solid to a liquid phase, polymeric compounds may additionally or alternatively be defined by a glass transition temperature (Tg) in the case of amorphous, purely amorphous polymers lacking a Tm. Purely crystalline polymers may be characterized by their Tm, and semi-crystalline polymers typically exhibit two characteristic temperatures (e.g., Tg and Tm), reflecting the respective proportions of the amorphous and crystalline parts of the molecule. Such polymers may also be defined by their softening temperature, Ts, in the middle of the logarithmic step of melting. Since the glass transition temperature describes the transition from the glassy to rubbery state, and the softening temperature is the intermediate inflection point in thermal analysis of materials, they are usually associated with a range of temperatures or the temperature at which this process is first observed.
[0164] Therefore, depending on the chemical properties of the CSSC, the temperature that can characterize its thermal behavior can be at least one of Tm, Ts and Tg. Therefore, when a CSSC (or nanoelement) is defined as appropriately having at least one of the first (or second) Tm, Ts and Tg within a specific range, the temperature considered is related to the material. Certain compounds can be identified by two such characteristic temperatures, in which case, performing a method step at a temperature higher than any one of the two temperatures can be higher than the lowest temperature of the two temperatures (which will extend the step) or the highest temperature of the two temperatures (which will accelerate the step). Conversely, performing a method step at a temperature lower than any one of the two temperatures can be lower than the highest temperature of the two temperatures or the lowest temperature of the two temperatures. Taking a semi-crystalline polymer as an example, it can be characterized by all three temperatures Tm, Ts and Tg (in descending order of value), and heating to above Tg (i.e., higher than at least one) may not be enough to reach Ts or Tm, and when heated to above Ts (i.e., at least higher than 2), it may not be enough to reach Tm. Only heating to above Tm will ensure that the heating temperature is higher than all three temperatures that can characterize such exemplary polymers.
[0165] In some embodiments, CSSC suitable for use in the compositions of the present invention is characterized by at least one of a first (natural) melting temperature (Tm), a softening temperature (Ts), or a glass transition temperature (Tg) of at most 300°C, at most 250°C, at most 200°C, at most 180°C, at most 150°C, or at most 120°C.
[0166] In some embodiments, the first Tm of the CSSC is at least 0°C, at least 10°C, at least 20°C, at least 30°C, at least 40°C, at least 50°C, or at least 60°C, and in some embodiments, the first Tm of the CSSC is between 0°C and 300°C, between 10°C and 300°C, between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 150°C, or between 50°C and 120°C.
[0167] In some embodiments, the CSSC is characterized in that at least one of the first Ts and the first Tg is -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 25°C or higher, or 50°C or higher. In some embodiments, at least one of the first Ts and the Tg of the CSSC is between -75°C and 300°C, between -50°C and 250°C, between -25°C and 200°C, between 0°C and 180°C, between 20°C and 180°C, or between 30°C and 150°C.
[0168] The characteristic temperature (Tm, Ts or Tg) of a CSSC may be referred to as a "first" Tm, Ts or Tg when referring to a natural / unmodified compound, and may be referred to as a "second" Tm, Ts or Tg when referring to a CSSC modified to constitute the core of the core-shell nanoelement of the present invention. In some embodiments, the second Tm, Ts or Tg measured for a blend obtained after mixing a CSSC with a fatty amine and optionally with a non-volatile liquid or any other desired ingredient and / or a core-shell nanoelement containing the same may be similar to the first respective Tm, Ts or Tg of the CSSC. Alternatively, the second Tm, Ts or Tg may be lower than the respective first characteristic temperature of the CSSC, in which case the CSSC is considered to be plasticized or expanded.
[0169] This general rule about suitable thermal behavior exemplified by CSSC can be applied to any other component of the core of the nanoelement that can display or affect the characteristic temperature as described herein. Therefore, in some embodiments, the composition of the core composed of CSSC alone or CSSC in combination with all other materials (except CSSC) can meet the above ranges due to the formation of the core (e.g., active agent, surfactant, etc.). In other words, the aforementioned thermal properties of the bulk, natural CSSC (e.g., the first Tm, the first Ts or the first Tg and the values they should preferably meet) can be considered to be similarly applied to core-shell nanoelements and their respective second Tm, second Ts or second Tg.
[0170] Such thermal properties of CSSC or any other component may be provided by its manufacturer, or may be determined independently by standard methods, particularly for core-shell nanoelements. Thermal analysis methods, such as differential scanning calorimetry (DSC), are described in, for example, ASTM 3418, ISO 3146, ASTM D1525, ISO 11357-3 or ASTM E1356. Such measurements may be performed on raw materials (e.g., bulk CSSC) or on intermediate products (e.g., mixtures) or final products (e.g., nanoelements) containing CSSC. For this purpose, core-shell nanoelements containing CSSC may be separated from polar carriers and other reagents present therein. The separation of nanoelements from their liquid medium may be performed according to standard methods, such as by drying (e.g., in a vacuum oven) or freeze-drying to evaporate the carrier, or by making the composition unstable (e.g., by changing the pH value) to precipitate the nanoelements. The nanoelements separated from their samples by any suitable method may be additionally rinsed (e.g., with water) to remove residues that may affect the expected measurement, and then the nanoelements are separated from the rinsing liquid. For example, nanoelements precipitated from their initial medium can be separated by centrifugation, and the precipitate can be repeatedly rinsed and centrifuged again until separated and ideally rinsed nanoelements are obtained.
[0171] Aggregate and non-aggregate CSSC
[0172] In some embodiments, the collagen synthesis stimulating compound (CSSC) used in the compositions, methods and uses of the present invention is a collagen synthesis stimulating polymer (CSSP). Since CSSP is expected to be suitable for biodegradation once applied to its target surface, such as delivered to the physiological environment of the skin (e.g., on, in or under it), such polymers generally contain hydrolyzable or enzymatically cleavable sites. However, the presence of hydrolyzable or cleavable sites is not required, and polymers that are considered non-biodegradable may lack them.
[0173] In some embodiments, the CSSC (or CSSP) can be non-reactive to establish more complex interactions, only capable of biodegradation, such as PCL. In other embodiments, the CSSC (or CSSP) can be biodegradable and have reactive moieties capable of interacting with other different molecules such as PLA or other identical molecules such as polymerizable natural resins having, for example, aldehyde moieties.
[0174] Similarly, when the CSSC is a non-biodegradable thermoplastic compound, these materials may also be reactive or non-reactive. Non-reactive, non-biodegradable synthetic thermoplastic polymers are, for example, polyethylene or polypropylene polymers, while polymers containing reactive groups may be, for example, ethylene-acrylic acid or ethylene-methacrylic acid copolymers.
[0175] Suitable CSSPs may be of natural or synthetic origin, thermoplastic in nature, their shape being capable of reversible changes upon appropriate heating and cooling. Suitable CSSPs may also be plasticized with suitable non-volatile liquids, such optional treatment of the CSSPs facilitating their nano-sizing to the extent of accelerating the transdermal delivery of dispersed core-shell nanoelements, when this is their intended use.
[0176] The synthetic CSSP may be biodegradable and selected from the group consisting of aliphatic polyesters, polyhydroxyalkanoates, poly(olefin dicarboxylates), polycarbonates, aliphatic-aromatic copolyesters, enantiomers thereof, copolymers thereof, and combinations thereof.
[0177] To the extent that the monomers forming the CSSP have chiral centers, all enantiomers and stereoisomers are contemplated. For example, lactic acid (2-hydroxypropionic acid, LA) exists in two enantiomeric forms, L-lactic acid and D-lactic acid, and thus PLA has stereoisomers, such as poly(L-lactide) (PLLA), poly(D-lactide) (PDLA), and poly(DL-lactide) (PDLLA). Thus, the CSSP may be a mixture of isomers of the same molecule or a specific stereoisomer (or stereo copolymer).
[0178] In some embodiments, the CSSP is biodegradable and is selected from the group consisting of aliphatic polyesters such as polycaprolactone (PCL), polylactide (PLA), poly(L-lactide) (PLLA), poly(D-lactide) (PDLA), poly(D,L-lactide) (PDLLA), polyglycolic acid (PGA), poly(p-dioxanone) (PPDO), and poly(lactic-co-glycolic acid) (PLGA); polyhydroxyalkanoates (PHA), including polyhydroxybutyrates (PHB) (e.g., poly-3-hydroxy-butyrate (P3HB), poly-4-hydroxybutyrate (P4HB)), polyhydroxyvalerate (PHV), poly(3-hydroxybutyrate) (PHB), poly(4-hydroxybutyrate) (PHB), poly(5-hydroxybutyrate) (PHB), poly(6-hydroxybutyrate) (PHB), poly(7-hydroxybutyrate) (PHB), poly(8-hydroxybutyrate) (PHB), poly(9-hydroxybutyrate) (PHB), poly(10-hydroxybutyrate) (PHB), poly(11-hydroxybutyrate) (PHB), poly(12-hydroxybutyrate) (PHB), poly(13-hydroxybutyrate) (PHB), poly(14-hydroxybutyrate) (PHB), poly(15-hydroxybutyrate) (PHB), poly(16-hydroxybutyrate) (PHB), poly(17-hydroxybutyrate) (PHB), poly(18-hydroxybutyrate) (PHB), poly(19-hydroxybutyrate) (PHB), poly(20-hydroxybutyrate) (PHB), poly(21-hydroxybutyrate) (PHB), poly(22-hydroxybutyrate) (PHB), poly(23-hydroxybutyrate) (PHB), poly(24-hydroxybutyrate) (PHB), poly(25-hydroxybutyrate) (PHB), poly(26-hydroxyvalerate) (PHV Poly(butylene succinate-co-3-hydroxyvalerate) (PHBV), polyhydroxycaproate (PHH) and polyhydroxyoctanoate (PHO); poly(olefin dicarboxylates), such as poly(butylene succinate) (PBS), poly(butylene succinate-adipate) (PBSA) and polyethylene succinate (PES); polycarbonates, such as poly(trimethylene carbonate) (PTMC), polypropylene carbonate (PPC) and poly[oligo-(tetramethylene succinate)-co(tetramethylene carbonate); aliphatic-aromatic copolyesters, such as poly(ethylene terephthalate) (PET) and poly(butylene adipate-terephthalate) (PBAT); isomers thereof, copolymers thereof and combinations thereof.
[0179] In a specific embodiment, the biodegradable CSSP is or comprises an aliphatic polyester, an isomer thereof, a copolymer thereof, and a combination thereof. In yet another specific embodiment, the CSSP is PCL. In another further specific embodiment, the CSSP is PLA. In another specific embodiment, the CSSP is PLGA. In another specific embodiment, the CSSP is PBSA.
[0180] The natural biodegradable CSSP may be selected from polysaccharides (eg, cellulose, starch, chitin and chitosan), lignin, and combinations thereof.
[0181] In some embodiments, the CSSP is non-biodegradable and is selected from polyamide (PA), polyethylene (PE), ethylene-acrylic acid copolymer (PEAA), ethylene-methacrylic acid copolymer (PEMAA), ethylene-n-butyl acrylate copolymer (PEBA), ethylene-vinyl acetate copolymer (PEVA), polymethyl methacrylate (PMMA), polypropylene (PP), polysiloxane, polystyrene (PS), polytetrafluoroethylene (PTFE), polyurethane (PU) or polyvinyl chloride (PVC). In a specific embodiment, the non-biodegradable CSSP is selected from PA, PE, PEAA, PEMAA, PEBA, PEVA, substituted or modified forms thereof, ionomers thereof, and combinations thereof.
[0182] The above polymers can be identified by their respective characteristic functional groups, which can be detected by standard methods known to those skilled in the art, for example by Fourier transform infrared (FTIR) spectroscopy.
[0183] Non-polymeric CSSCs suitable for use in the compositions, methods and uses of the present invention may also be natural or synthetic. Under appropriate conditions, some natural CSSCs may react in a polymerization reaction to produce CSSPs.
[0184] The polymerizable natural CSSC may be selected from: natural resins (e.g., shellac, rosin, dammar, copal, sandar, amber, frankincense, and manila); natural gums (derived from gum-producing trees such as babul, khair, kullu, dhawra, palas, semal, lenia, and neem, or from plant seeds such as guar, tamarind, and cassia); natural gum-resins (e.g., asafetida, myrrh, salai, and commiphora); and combinations thereof. In a particular embodiment, the natural polymerizable CSSC is shellac or rosin.
[0185] The non-polymerizable CSSC comprises a quinone. In a specific embodiment, the non-polymerizable CSSC is coenzyme Q10 (CoQ10).
[0186] In addition, the CSSC can be a blend of different compounds, whether polymerized or not, polymerizable or not, the properties of the mixture (e.g., characteristic temperature, viscosity, etc.) meet the ranges set for suitable individual compounds. For example, a CSSC or CSSP whose Tm, Ts or Tg is outside the range previously considered suitable can be combined with a CSSC or CSSP whose Tm, Ts or Tg is suitable for "correcting" the characteristic temperature of the obtained mixture to be suitable for the purposes of the present invention. For illustrative purposes, the CSSC can be a blend of polymers or a copolymer including at least one of the aforementioned CSSPs, such copolymers can contribute to the biocompatibility, biodegradability, and mechanical and optical properties of the nanoelement.
[0187] The composition of the present invention can include core-shell nanoelements each prepared using various types of CSSC. For example, the composition can include a combination of nanoelements prepared using one type of CSSC and nanoelements prepared using different types of CSSC. Alternatively or additionally, the composition of the present invention can contain core-shell nanoelements with different functions, for example, each type of nanoelement includes different optional active agents.
[0188] Viscosity
[0189] Alternatively (or additionally) the viscosity of the CSSC may be selected to initially accommodate the shearing thereof in the method of the invention for preparing the composition. A CSSC suitable for the present method may typically have a viscosity of no more than 10 11 The viscosity is measured in millipascal seconds (mPa"s, equivalent to centipoise), and the viscosity is usually 5x10 10 mPa〃s or less, 10 10 mPa〃s or less, 5x10 9 mPa〃s or less, 10 9 mPa〃s or less, 5x10 8 mPa〃s or less, 10 8 mPa〃s or less, 5x10 7 mPa〃s or less, 10 7 mPa〃s or less, or 5x10 6 or less, such as at 50°C and 10 sec -1 Measured at shear rate.
[0190] In order for effective shearing to occur, the viscosity of the CSSC is maintained at a temperature of 50°C and for 10 sec. -1 The shear rate should preferably be 10 7 mPa"s or less. This viscosity may relate to the natural properties of isolated, unmodified CSSC, in which case it may be referred to as the "first viscosity", or it may refer to the viscosity of a CSSC modified by mixing with a material miscible therewith, in which case it may be referred to as the "second viscosity" of a mixture comprising CSSC. For illustrative purposes, the second viscosity may be a CSSC plasticized with a suitable plasticizer (e.g., a non-volatile liquid and / or a fatty amine). The viscosity of a material at any temperature (or range thereof) of interest (whether or not modified by the presence of other substances) may be determined by conventional thermorheological analysis, such as described in ASTM D3835 or ASTM D440.
[0191] The natural viscosity of CSSC can be reduced by fatty amines (which are added to form the shell of the core-shell nanoelement), but alternatively non-volatile liquids can also be added to CSSC or CSSP regardless of their intrinsic viscosity. When a more significant viscosity reduction than that achieved by the presence of fatty amines alone is desired (e.g., when CSSC is heated at 50°C and 10 sec -1 The first viscosity is relatively high at a shear rate of, for example, higher than 10 7mPa 〃 s, however the first viscosity is optionally lower), such dedicated plasticizing materials are generally used in the compositions or methods of the present invention. Non-volatile liquid (which may also be referred to as plasticizing liquid) is contained in the core of the nanoelement, which liquid is generally adsorbed or otherwise retained by the CSSC.
[0192] This "plasticization" or "swelling" generally results in an increase in weight and / or volume relative to the mass or volume of the CSSC itself in its native form. This plasticization of the CSSC makes the plasticized CSSC softer and more ductile, as demonstrated by a decrease in its viscosity (i.e., the second viscosity is less than the first viscosity), facilitating their subsequent nanosizing (along with any other materials mixed therewith).
[0193] Advantageously, the reduced viscosity should be suitable for the shearing process (e.g., shearing equipment, shearing temperature, etc.) selected to nanosize the plasticized CSSC (e.g., plasticized CSSP) mixed with the other materials miscible in the core and the fatty amine intended to form the first surrounding shell. For example, the non-volatile liquid and its ratio relative to the CSSC can be selected to reduce the viscosity of the CSSC by at least half a log, or at least one log, etc., as may be desired. For illustration purposes, if the CSSC has 10 8 mPa·s, then the plasticizer and its dosage will make the second viscosity of CSSC 5×10 7 mPa·s, thereby reducing by half a log, or (if the dosage is higher or a more effective agent is selected) making the CSSC thus plasticized at 50°C and 10 sec -1 The shear rate was measured at 10 7 The second viscosity of mPa·s can be reduced by 1 logarithm.
[0194] In some embodiments, the first viscosity of CSSC or the second viscosity of plasticized CSSC (and / or core-shell nanoelement comprising the same) is 50° C. and 10 sec. -1 The shear rate was measured at 10 2 mPa〃s to 10 7 mPa〃s, 5x10 2 mPa〃s to 10 6 mPa〃s, 5x10 2 mPa〃s to 10 5 mPa〃s, between 10 3 mPa〃s and 5x10 4 mPa〃s, or between 10 3 mPa〃s and 10 4 mPa"s. Viscosity can be measured using any suitable rheometer equipped with a spindle appropriate for the expected viscosity range at the appropriate shear rate.
[0195] However, viscosity is not only related to the preparation method of core-shell nanoelement. It is believed that the above viscosity (i.e., not more than 10 7 mPa·s) are relatively stretchable, and this deformability is expected to accelerate transdermal delivery of core-shell nanoelements when this is their intended use.
[0196] Plasticization of CSSC
[0197] Although the effects of non-volatile liquids that may be combined with the CSSC in the core of the nanoelement on the viscosity of the CSSC are mentioned above, they may perform additional functions when reducing it to the desired extent. Plasticization, particularly of the CSSP, may be visually observed when the swollen polymer is at a temperature below melting. At higher temperatures, the effects of the non-volatile liquid or fatty amine may be detected by its plasticizing activity, including its ability to reduce at least one of the temperatures that characterize the native CSSC.
[0198] Lowering the characteristic temperature of the CSSC allows a corresponding reduction in the processing temperature at which the composition can be prepared. For illustrative purposes, although the CSSC may have a first (natural) Tm, Ts or Tg of 200°C or less in the absence of a suitable non-volatile liquid, the addition of such a plasticizer may produce a plasticized CSSC having a second (modified) Tm, Ts or Tg below the first temperature, for example 95°C or less. The temperature drop provided by the presence of the plasticizer need not be as significant as shown, obviously depending on the value of the first Tm, Ts or Tg of the native CSSC, and also on the value of the second Tm, Ts or Tg, as it may be necessary to facilitate the preparation of the composition and / or the subsequent penetration of the core-shell nanoelements, preferably depending on the boiling point (Tb) of the liquid that will remain present in the composition (but not necessarily if the steps are brief enough and / or the liquid is too much to prevent some from being boiled off), and / or depending on the concentration of the plasticizer relative to the compound being plasticized.
[0199] Typically, the second Tm, Ts or Tg of the plasticized CSSC (together with any other components miscible with the CSSC) is at least 5°C, at least 10°C, at least 15°C, at least 20°C, at least 25°C, at least 30°C, at least 35°C, at least 40°C, at least 45°C or at least 50°C lower than the corresponding first Tm, Ts or Tg of the bulk CSSC.
[0200] The characteristic temperature of CSSC can be satisfactorily lowered only by the fatty amine used to form the shell. Alternatively, a non-volatile liquid can be additionally combined with the CSSC to further lower at least one of its characteristic temperatures.
[0201] If the mixture of CSSC and plasticizer further includes ingredients that may affect the softening properties of the resulting combination due to the form or interior of the nanoelements (e.g., rheology modifiers, surfactants, preservatives, or any similar material that may have a plasticizing effect), then additionally or alternatively, the thermal properties considered suitable for the present invention will apply to the entire mixture.
[0202] Thus, in some embodiments, at least one of the second Tm, Ts or Tg of the core-shell nanoelement is at most 290°C, at most 250°C, at most 200°C, at most 190°C, at most 180°C, at most 170°C, at most 150°C or at most 120°C.
[0203] In some embodiments, the core-shell nanoelement comprising a CSSC in its core has a second Tm of 0°C or more, 10°C or more, 20°C or more, 30°C or more, 40°C or more, 50°C or more, or 60°C or more. In some embodiments, the second Tm of the core-shell nanoelement is in the range of 0°C to 290°C, 10°C to 290°C, 20°C to 290°C, 10°C to 250°C, 20°C to 250°C, 20°C to 200°C, 30°C to 190°C, 50°C to 170°C, 50°C to 150°C, 30°C to 180°C, 40°C to 150°C, 50°C to 170°C, 50°C to 150°C, or 50°C to 120°C.
[0204] In some embodiments, the core-shell nanoelement has at least one of a second Ts and a second Tg, wherein the second Ts and the second Tg are -75°C or higher, -50°C or higher, -25°C or higher, -20°C or higher, -10°C or higher, 0°C or higher, 10°C or higher, 20°C or higher, 25°C or higher, 30°C or higher, 40°C or higher, 50°C or higher, or 60°C or higher. In other embodiments, at least one of the second Ts and Tg measured for the core-shell nanoelement is in the range of -75°C to 290°C, -50°C to 290°C, -25°C to 290°C, -20°C to 290°C, -10°C to 290°C, 0°C to 290°C, 10°C to 250°C, 20°C to 200°C, 30°C to 190°C, 30°C to 180°C, 40°C to 180°C, 50°C to 170°C, 50°C to 150°C or 50°C to 120°C.
[0205] Such thermal properties and characterization temperatures can be evaluated when preparing the plasticized CSSC or a mixture comprising it, or when the process for preparing the composition is complete, ie on core-shell nanoelements which can be isolated therefrom.
[0206] Non-volatile plasticizing liquid
[0207] While the presence of a non-volatile liquid may have a role in the efficacy of delivering nanoelements containing a CSSC core that cannot be ignored, the selection of such a material is primarily considered to improve the processability of the CSSC, thereby facilitating the preparation and dispersion of the core-shell nanoelements in the polar carrier phase. Particularly suitable non-volatile liquids can both reduce the viscosity of the CSSC and reduce at least one of its Tm, Ts and Tg, as previously discussed separately. Advantageously, suitable non-volatile liquids improve the processability of the CSSC under conditions suitable for shearing it into nanoparticles, the shear temperature initially resulting in the formation of nanodroplets.
[0208] Firstly, as their names suggest, agents suitable for plasticizing CSSC according to the invention are liquid at the temperature at which the CSSC is processed, i.e. at least at one of the temperature of mixing with the CSSC and the temperature of shearing. Such liquid agents may also be liquid at room temperature.
[0209] In order to ensure that its effect is long-lasting, the plasticizing liquid is preferably non-volatile. As used herein, the term "non-volatile", as used with respect to the liquid of plasticizable CSSC, refers to a liquid exhibiting a low vapor pressure, for example, less than 40 Pascals (Pa, also Newtons per square meter) at a temperature of about 20°C, in some embodiments, a non-volatile liquid (or any other component preferably of low volatility) may have a vapor pressure of 20Pa or less, 5Pa or less, 1Pa or less, 0.1Pa or less, or 0.01Pa or less, as measured at about 20°C. Such vapor pressure values are usually provided by the manufacturer of the liquid, but can be independently determined according to the range of vapor pressure by standard methods such as ASTM D2879, E1194 or E1782 described. If necessary, the low volatility or substantially zero volatility of the non-volatile liquid that can be used for plasticizing CSSC should preferably be maintained at the highest temperature for processing plasticizing CSSC. The use of such non-volatile liquids allows the CSSC to be maintained in its plasticized or swollen state without risk of evaporation or elimination of the liquid, even at the elevated temperatures at which the composition is prepared according to the process of the invention.
[0210] Suitable nonvolatile liquids are also characterized by having a boiling point (Tb) above room temperature, above body temperature, and above the elevated temperatures required to prepare the composition. l ), since preferably the CSSC liquid used to plasticize the present invention does not substantially evaporate during or after the preparation of the composition. Having said that, some boiling evaporation may be tolerated if the mixing step of the non-volatile liquid plasticizing the CSSC is short enough to ensure the desired residual presence, and / or if a sufficient excess of non-volatile liquid is added to compensate for any partial boiling evaporation that may occur.
[0211] For similar reasons as to the CSSC being ideally held together to be plasticized with it and retained in the nanoelements comprising it, the non-polar liquid should preferably not be able to migrate to the polar carrier phase. Thus, suitable non-volatile liquids are substantially immiscible in such polar carriers (e.g., water), their solubility in the pure polar carrier or in the liquid phase comprising it being as previously detailed for the CSSC, i.e., 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, or 0.1 wt % or less, based on the weight of the carrier or the phase containing the carrier.
[0212] Such non-volatile liquids need to be compatible with the CSSC of the composition (i.e., able to plasticize it: for example, reduce its Tm, Ts or Tg, and / or reduce its viscosity). The non-volatile liquid suitable for a particular CSSC can be selected accordingly by routine experimentation. For example, given a particular CSSC, various non-volatile liquids can be mixed with it in one or more relative concentrations, and optionally at an elevated temperature to facilitate plasticization, and their effect on the plasticizing CSSC monitored by thermorheology (detecting their ability to reduce viscosity with temperature) and thermal analysis (e.g., by DSC, detecting their ability to reduce the Tm, Ts or Tg of the native CSSC). The most effective non-volatile liquid for a particular CSSC can be selected accordingly.
[0213] Fundamentally, if a material or chemical composition does not hinder the activity of another material or chemical composition or does not reduce it to a degree that significantly affects the intended purpose, then this material or chemical composition is compatible with another material or chemical composition. This compatibility can be viewed from a chemical point of view, for example, sharing similar functional chemical groups or every kind of material has a corresponding part that can interact with each other desirably. This compatibility can be shown by forming a uniform mixture rather than being separated into a composite material of different phases. If the material degrades, then this material is incompatible with another kind, and for illustration, if dissolving the nano elements, making them unstable, improperly making them charged with an electric charge incompatible with their intended use, etc., then the polar liquid phase will be incompatible with the nano elements.
[0214] The materials should also be compatible with the process used to prepare the composition, not be adversely affected by any step to which the materials will be subjected in the process, and not volatilize (or otherwise be eliminated) at the temperature at which they are incorporated into the composition. It will be appreciated that these materials also need to be compatible with their intended use, which in the present case may include, for example, biocompatibility, non-irritation, non-immunogenicity, and any such characteristics as to provide them with regulatory approval at concentrations suitable for use in the effective cosmetic or pharmaceutical compositions disclosed herein.
[0215] The materials should also be compatible with the process used to prepare the composition, not be adversely affected by any steps to which the materials will be subjected in the process, and not be volatile (or otherwise eliminated) at the temperature at which they are introduced into the composition. It will be appreciated that the materials also need to be compatible with their intended use, which in the case of the present invention may include, for example, biocompatibility, non-irritation, non-immunogenicity, and any such characteristics that provide for their regulatory approval at concentrations suitable for effective cosmetic or pharmaceutical compositions disclosed herein.
[0216] Although compatibility between the CSSC and the nonvolatile liquid is desired, dissolution of the CSSC in the nonvolatile liquid is undesirable, and therefore the nonvolatile liquid does not act as a solvent for the CSSC but remains therein as a plasticizer.
[0217] It is believed that the solvent, which is usually composed of relatively small molecules, is able to enter between the CSSC molecules and separate them from each other to the extent that the CSSC is easily dissolved in the solvent, forming a homogeneous solution even at room temperature. As used herein, the term "solvent" refers to a liquid in which more than about 5% by weight of CSSC can be dissolved at room temperature.
[0218] In contrast, non-volatile (e.g., plasticizing) liquids are generally large in size compared to solvent molecules and do not readily separate the CSSC molecules at room temperature to form a solution in which they can provide at most an initial swelling. An elevated temperature is required to move the CSSC molecules sufficiently away from each other to allow sufficient non-volatile liquid to enter the gaps formed. Even under such favorable conditions, mixing may be required to uniformly form the plasticized CSSC. Such elevated temperature may be equal to or above at least one of the first Tm, Ts, and Tg of the CSSC.
[0219] The non-volatile liquid suitable for the present invention can be selected from: monofunctional or polyfunctional aliphatic esters (such as dimethyl glutarate, dimethyl maleate, dimethyl glutarate, dipropylene glycol dibenzoate and isoamyl lactate); fatty esters (such as 2-ethylhexyl lactate, benzyl benzoate, butyl lactate, C12-C15 alkyl benzoate, octyl caprate and a mixture of octyl caprylate, decyl oleate, dibutyl adipate, dicaprylyl carbonate, dibutyl maleate, dibutyl sebacate, diethyl succinate, ethyl oleate, glyceryl monooleate, glyceryl monocaprylate, glyceryl tricaprylate, glyceryl tricaprylate; trioctanoate), isopropyl myristate, isopropyl palmitate, L-menthyl lactylate, lauryl lactylate, n-amyl benzoate, PEG-6 caprylic / capric glycerides, propylene glycol monolaurate, propylene glycol monocaprylate, triacetin, triethyl citrate, acetyl triethyl citrate, tri(2-ethylhexyl) o-acetyl citrate, tributyl o-acetyl citrate, and tributyl citrate; cyclic organic esters (e.g., decanoic acid, gamma-decanoic acid, menthyl lactylate, and menthyl lactylate); undecanolide); aromatic esters (such as diethyl phthalate); fatty acids (such as caprylic acid, cyclohexanecarboxylic acid, isostearic acid, lauric acid, linoleic acid, linolenic acid, myristic acid, oleic acid, palmitic acid and stearic acid); terpenes (such as citronellol, eugenol, farnesol, hinokitiol, linalool, menthol, menthone, nerol, terpineol and thymol); aromatic alcohols (such as benzyl alcohol); aromatic ethers (such as phenoxyethanol); aldehydes (such as cinnamaldehyde); and combinations thereof.
[0220] In some embodiments, the non-volatile liquid that can be used to plasticize the CSSC disclosed herein is a multifunctional aliphatic ester (PFAE), which is a diester derivative of common dicarboxylic acids: namely, adipic acid (C6), azelaic acid (C9), and sebacic acid (C10), the alcohol portion of the diester generally falling within the C3-C20 carbon number range, including straight chain and branched even and odd alcohols. In a specific embodiment, the non-volatile liquid is a PFAE, selected from dibutyl adipate (e.g., as B), dibutyl sebacate, triethyl acetyl citrate (e.g. as AII commercially available), C 12 -C 15 Alkyl benzoates (e.g. 256 commercially available) and dioctyl carbonate (e.g., available as CC commercially available).
[0221] When the CSSC is non-biodegradable and / or when the surface to which the composition is to be applied is not the skin, an additional non-volatile liquid may be used. This additional liquid may be a mineral oil, a natural oil, a vegetable oil, an essential oil, a synthetic oil, and combinations thereof, provided that they preferably meet the present requirements.
[0222] Fatty amines
[0223] The fatty amine suitable for forming the shell (or first shell) surrounding the CSSC core of the nanoelement first needs to be miscible with the CSSC, being able to form a homogeneous mixture when combined therewith.
[0224] Suitable fatty amines are primary, secondary, tertiary or quaternary C8-C 22 Amines having hydrophobic straight chain, branched chain or cyclic saturated or unsaturated aliphatic or aromatic alkyl or aryl chains. Combinations of these fatty amines may also be used. In some embodiments, the hydrophobic chain of the fatty amine is C8-C 20 or C8-C 18 Aliphatic alkyl chain. Preferably, the fatty amine is liquid at room temperature, however this is not required. Typically, primary, secondary and tertiary fatty amines may be liquid at room temperature, i.e. have a melting temperature of at most 25°C, at most 20°C, at most 15°C or at most 10°C, while quaternary amines often have a melting temperature above 25°C.
[0225] Alkyl or aryl chains of this length (e.g. C8-C 22 、C8-C 20 or C8-C 18 ) produces a fatty "tail" connected to the amine "head". Thus, the amine molecule contains a hydrophobic portion (i.e., the fatty tail) and a hydrophilic portion (i.e., the amine head). The arrangement of amine molecules within the core-shell nanoelement will be discussed further below.
[0226] The hydrophobic tail renders the fatty amine insoluble in water, i.e., having a solubility of 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, or 0.1 wt % or less (similar to CSSC) based on the weight of the polar carrier.
[0227] The fatty amines are not intended to remain completely within the core when they are thoroughly mixed with the CSSC at elevated temperatures to form a homogeneous mixture, in the presence or absence of a non-volatile liquid (or any other ingredient miscible with the CSSC and the blend formed therewith). Instead, it is believed that they migrate toward the outer surface of the nanoelement, exposing their hydrophilic heads to the polar carrier surrounding the nanoelement, while their hydrophobic tails tend to remain in the water-insoluble environment of the core. This phenomenon leads to the formation of a shell, which can be confirmed by a change in the charge of the nanoelement. Although the core of the CSSC without a shell of fatty amines will show a negative charge in an aqueous polar liquid (e.g., in water), the formation of a shell of fatty amines obtained by the above-mentioned method masks the core, reduces its negative charge, and can even provide a positive charge to the core-shell nanoelement, depending on the respective charge density and amount of the core and shell materials and the liquid environment (e.g., pH) that can regulate the charge.
[0228] It is noteworthy that the fatty amine forming the shell of the nanoelement of the present invention is not covalently bonded to the CSSC of the core, so that the fatty amine can migrate to the core surface to form the shell, and the materials of the core and shell maintain their respective original effectiveness.
[0229] Primary amines are advantageous in terms of the charge they provide to the shell compared to secondary and tertiary amines. Without wishing to be bound by any particular theory, it is believed that when seeking transdermal delivery of nanoelements having only a single fatty amine shell, secondary and tertiary amines are advantageous because they have a lower tendency to form reactive nitrogen hydrides (e.g., NH3 + ) tendency. Such secondary and tertiary amines can be selected from: oleyl bis-(2-hydroxyethyl)amine (e.g. The quaternary amine may be a quaternary ammonium salt, such as hexadecyltrimethylammonium chloride. In a specific embodiment, the fatty amine is selected from the group consisting of oleylbis-(2-hydroxyethyl)amine, N,N-dimethyldodecylamine, oleylamine, octylamine and hexadecyltrimethylammonium chloride.
[0230] At high temperatures, fatty amines may be prone to degradation, resulting in amine loss (amidation due to oxidation of the amine). This degradation analysis can be performed by placing the fatty amine at a test temperature for a sufficiently long time, such as 24 hours, and then using a standard method to measure the amine value by conventional analysis, such as described in ASTM D 2074-07. As a non-limiting example, the amine value can be evaluated by titrating the fatty amine (which has been subjected to the test temperature) with hydrochloric acid, and the amine value corresponds to the volume of 0.1N HCl (ml) required for neutralizing 10g of the product. The results are then compared with the amine values provided by the manufacturer in the natural, non-heated form of the same fatty amine, or can be measured independently as described above. Any reduction in the amine value of the heated fatty amine may indicate that the amine degrades at the test temperature (such a temperature is referred to as the "degradation point" of the fatty amine). Therefore, the temperature for preparing the core-shell nanoelement of the present invention should preferably be lower than the degradation point so that the amine group is substantially maintained in a reduced / non-oxidized state.
[0231] As mentioned above, in addition to forming the shell, some fatty amines (such as oleylamine) can act as plasticizers for the core, and their addition reduces the viscosity of the CSSC used therewith, an effect described, for example, in Example 1.
[0232] Alternatively or additionally, fatty amines (e.g., oleyl bis-(2-hydroxyethyl)amine) may also act as surfactants, which are suitable for stabilizing core-shell nanoelements in polar supports. In some embodiments, the fatty amine moieties exposed in the shell may charge the core-shell nanoelements to such an extent that in the absence of a dedicated surfactant provided externally in the liquid phase, the elements may remain stably dispersed in the composition (e.g., as demonstrated in Examples 1 and 2). In this case, the core-shell nanoelements may be considered "self-emulsifying" or "self-emulsified".
[0233] Alternatively or additionally, the fatty amine may further act as a polar insoluble active agent, not only forming the shell of the core-shell nanoelement, but also exerting its own activity (eg, as a pesticide).
[0234] Polar media
[0235] The liquid medium that forms the continuous phase of the nanoelement that is dispersed with the core made of CSSC is polar. In some embodiments, the liquid phase is basically composed of polar carriers, and in other cases, there are additional components in the polar carriers. For illustration purposes, such additional components can be surfactants, carrier-soluble active agents or skin penetration enhancers as described in detail herein, or any other conventional additives present in the composition (for example, for skin use). Polar carriers suitable for the present invention can be selected from water, glycols (for example, ethylene glycol, propylene glycol, dipropylene glycol and 1,2-butylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2-ethyl-1,3-hexanediol and 2-methyl-2-propyl-1,3-propylene glycol), glycerols (for example, acrolein, dihydroxyacetone, glyceric acid, tartronic acid, epichlorohydrin, glycerol tert-butyl ether, polyglycerol, glyceride and glycerol carbonate) and combinations thereof.
[0236] The polar medium may be formed from one or more suitable polar carriers, and when water is the primary polar carrier, the resulting liquid is often referred to as an aqueous solution (or aqueous phase). In some cases, liquids that are not considered sufficiently polar themselves (e.g., fatty alcohols) may be present in the liquid phase in addition to the polar carrier, provided that the liquid that is not sufficiently polar to form the entire liquid polar phase is a) soluble in the primary polar carrier (e.g., has a water solubility of 5 wt.% or more) so as to form a distinct liquid phase therewith; and b) maintains the overall polarity of the liquid phase. The resulting liquid phase may have a polarity index of 3 or more, 4 or more, or 5 or more, and for reference, the polarity index of water is 9-10.
[0237] Since the polarity index of a solvent refers to its relative ability to dissolve in a test solute, a liquid may additionally or alternatively be classified as polar or non-polar according to its dielectric constant (εr). Liquids having a dielectric constant of less than 15 are generally considered to be non-polar, while liquids having a higher dielectric constant are considered to be polar, the relative polarity of the liquid increasing with the value of the dielectric constant. Preferably, a polar carrier suitable for the composition of the present invention has a dielectric constant of 20 or more, 30 or more, 40 or more, 50 or more, or 60 or more, determined at room temperature. For ease of illustration, the dielectric constant of propylene glycol is 32, the dielectric constant of glycerol is 46, and the dielectric constant of water is 80. Although for simplicity, the guidance is provided for a pure polar carrier, this should actually preferably apply to the entire polar liquid phase prepared therefrom (e.g., including additional polar soluble materials and / or consisting of a mixture of liquid carriers). It is worth noting that the liquid polar phase can be composed of a formally polar solvent (e.g., having εr ≥ 15) and a formally non-polar solvent (e.g., having ε r <15), as long as their individual volumes allow the entire liquid phase to be polar (e.g., with ε r≥ 15). The dielectric constant of a liquid is typically provided by the manufacturer but may be independently determined by any suitable method, such as that described in ASTM-D924.
[0238] As discussed, the composition of the polar liquid phase should be such that the core-shell nanoelements comprising a CSSC core in its core and a fatty amine in its first shell can remain substantially insoluble and stably dispersed therein without significant leaching of the contents of the nanoelements into their surrounding medium (when undesirable). In addition, the polar liquid phase should also enable the nanoelements to be appropriately charged, for example, to achieve a desired distribution for their delivery and efficacy on or across the layers of the skin.
[0239] Because the polar medium may contain additional liquid and / or material dissolved therein, the polar carrier may comprise at least 50 weight percent, at least 60 weight percent, at least 70 weight percent, at least 80 weight percent, or at least 90 weight percent of the weight of the liquid phase.
[0240] In some embodiments, the polar carrier comprises water (e.g., 45 wt % water, 45 wt % propylene glycol, and 10 wt % fatty alcohol), consists of water (e.g., comprises 51 wt % to 80 wt % water), consists essentially of water (e.g., comprises 81 wt % to 99 wt % water), or is water.
[0241] Surfactants
[0242] Some CSSCs can remain nanodispersed in the composition due to their inherent chemical properties, the nanoelements for example having a charge sufficient to ensure particle repulsion, thus ensuring their stable dispersion. Other CSSCs can alternatively or additionally remain nanodispersed because they are plasticized to a sufficient degree by a non-volatile liquid that is additionally used as a surfactant. Fatty amines can also be used as surfactants to help disperse the nanoelements in polar carriers.
[0243] In this case, and regardless of the underlying principle, the nanoelements can be considered to be self-emulsifying (e.g., remaining as discrete individual nanoelements in a liquid medium in the absence of a surfactant for that purpose). The core-shell nanoelements are considered to be dispersed when the particles reach a desired size (and / or particle size distribution (PSD)), and the core-shell nanoelements are considered to be "stably dispersed" when the particles can maintain the desired size (or PSD) over time. The original size and PSD can be determined upon completion of the preparation of the core-shell nanoparticles or at any other desired time point. Since size measurements may differ between repeated measurements at the same time point, the size or PSD at a subsequent time point is considered to be substantially similar to the value obtained at the previous time point if it is within 10% or 5% of the previously determined value. Therefore, if the measured values of the size and / or size distribution of the particles do not change by more than 10% or 5% over at least 1 day, at least 2 days, or at least 3 days, the particles are considered to be stably dispersed. When accelerated stability testing is desired, such stability can be assessed under any desired storage conditions, at room temperature, at cooler temperatures (eg, 4-8°C), or conversely at higher temperatures (eg, 30-40°C).
[0244] Although the compositions of the present invention may be stable due to the components of the core-shell nanoparticles and / or their environmental conditions (e.g., the pH of the liquid medium), in some embodiments, the compositions may further comprise at least one (specialized) surfactant to keep the core-shell nanoelements stably dispersed (and therefore also within their intended size range).
[0245] Surfactants suitable for the purposes of the present invention reduce the surface tension between the core-shell nanoelements comprising a CSSC in their core and a fatty amine in their first shell and the environment in which they are immersed. Depending on their chemical formula (and on the CSSC and polar support considered), the surfactants may be miscible with the CSSC (but able to diffuse to its outer surface) or with the polar support forming the nanosuspension.
[0246] Surfactants suitable for use in the compositions and methods of the present invention are generally amphiphilic, containing a polar or hydrophilic portion and a non-polar or hydrophobic portion. Such surfactants are characterized by a hydrophile-lipophile balance (HLB) value in the range of 1 to 35, wherein HLB values generally indicating compatibility with aqueous systems are generally provided on the Griffin scale.
[0247] Suitable surfactants for the purposes of the present invention may be anionic, cationic, amphoteric or nonionic surfactants.
[0248] When it is desired that the core-shell nanoelements of the present invention be positively charged in an aqueous environment, for example to facilitate the attachment of an additional shell made of a material with an opposite charge (e.g., an active agent) in the same medium or to prolong the retention of the nanoelements on the skin surface, cationic surfactants may be suitable for the purpose of maintaining and even increasing the positive charge of the nanoelements. Nonionic or amphoteric surfactants, or even anionic surfactants, are more likely to reduce the positive charge of the core-shell nanoelements, so when necessary, their concentration should be adjusted to keep the overall charge sufficiently positive. In some embodiments, when nonionic, amphoteric, or anionic surfactants are used, they are added in a weight ratio of up to 1:1 relative to the weight of the fatty amine.
[0249] When the surfactants are relatively water soluble, or for simplicity of preparation regardless of solubility, the surfactants can be added to the liquid phase in which the core-shell nanoelements are present. When the surfactants are relatively water insoluble, they can instead be incorporated into the core of the nanoelement along with the CSSC.
[0250] Cationic surfactants can be selected from quaternary ammonium compounds, most of which are readily soluble in water (e.g., benzalkonium chloride, trimethylammonium methyl sulfate). Quaternary ammonium compounds that are relatively insoluble in water and meet the other requirements set forth herein for fatty amines (e.g., hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride) can be considered as fatty quaternary amines, and such amines can therefore be used as cationic surfactants in addition to forming a shell for the amine head that can be positively charged.
[0251] The nonionic surfactant may be selected from the group consisting of: fatty alcohols (e.g., cetearyl alcohol); ethoxylated fatty alcohols (e.g., C8-C 18ethylene oxide (EO) / propylene oxide (PO) copolymers; alkylphenol ethoxylates (e.g., octylphenol polyglycol ether and nonylphenol polyglycol ether); alkyl glucosides and polyglucosides (e.g., lauryl glucoside); fatty alkanolamides (e.g., lauramide diethanolamine and cocamide diethanolamine); ethoxylated alkanolamides; ethoxylated fatty acids; sorbitol derivatives (e.g., polysorbates, sorbitan laurate, sorbitol, 1,4-sorbitol, isosorbide and 1,4-sorbitan triester, PEG-80); alkyl carbohydrate esters (e.g., sucrose esters); fatty acid monoesters); amine oxides; cetearyl alcohol polyether; oleyl alcohol polyether; alkyl amines (other than fatty amines); fatty acid esters (e.g., ascorbyl palmitate, glycol stearate, polyglyceryl-6 esters, polyglyceryl-6 pentaoleate, polyglyceryl-10 pentaoleate, and polyglyceryl-10 pentaisostearate); polyoxyglycerol esters (e.g., oleoyl polyoxylglyceryl-6 glyceride); natural oil derivatives; carboxylic acid esters (e.g., D-α-tocopheryl polyethylene glycol succinate (vitamin E TPGS)); and urea.
[0252] The amphoteric surfactant may be selected from betaines (e.g., cocamidopropyl betaine); alkylamphopropionates (e.g., cocoamphopropionate); alkylimino-propionates (e.g., sodium lauryl aminopropionate); and alkylamphoacetates (e.g., cocoamphocarboxyglycinate).
[0253] The anionic surfactant may be selected from the group consisting of alkyl sulfates (e.g., sodium lauryl sulfate, ammonium lauryl sulfate, and ammonium laureth sulfate); sulfosuccinates (e.g., disodium lauryl sulfosuccinate, disodium lauryl polyoxyethylene ether sulfosuccinate); The invention also includes the following: sodium sulfosuccinate, sodium dioctyl sulfosuccinate, sodium dioctyl sulfosuccinate, and mixtures thereof with sulfonic acids and lauramidopropyl betaine; alkylbenzene sulfonates (e.g., sodium toluene sulfonate, cumene sulfonic acid, toluene sulfonic acid, xylene sulfonic acid, cumene sulfonic acid, and salts thereof (e.g., sodium, potassium, calcium, ammonium)); acyl methyl taurates (e.g., sodium methyl lauroyl taurate and sodium methyl cocoyl taurate); acyl sarcosinates (e.g., sodium lauroyl sarcosinate, sodium cocoyl sarcosinate, and sodium myristoyl sarcosinate); isethionates (e.g., sodium butyl isethionate, sodium capryloyl isethionate, and sodium lauroyl isethionate); propyl peptide condensates; monoglyceride sulfates; ether sulfonates and fatty acid salts (e.g., sodium stearoyl lactylate).
[0254] According to their mechanism of action, these surfactants can be divided into emulsifiers and hydrotropes. Emulsifiers easily form micelles (and are therefore characterized by critical micelle concentration (CMC) values) and are believed to increase the dispersibility of CSSC (or plasticized CSSC) when subsequently combined with polar carriers to produce nanosuspensions. In general, emulsifiers generally refer to surfactants that ensure that one liquid is dispersed into another liquid, the liquids having opposite polarities, while dispersants refer to surfactants that ensure that solids are dispersed into liquids. Since the present method can provide nanoemulsions and nanodispersions, the surfactants referred to as emulsifiers in the step where the nanosuspension becomes an emulsion can actually become dispersants, to the extent that the initial nanoemulsion subsequently produces a nanodispersion at a lower temperature. Therefore, as used herein, the term "emulsifier" also includes surfactants, also referred to as dispersants.
[0255] Emulsifiers that are lipophilic in nature, i.e., contain relatively large hydrophobic parts, are more suitable for combination with CSSC (and any other materials that are immiscible with polar carriers, such as fatty amines or non-volatile liquids), and can therefore be referred to as polar carrier-insoluble emulsifiers (or surfactants in general). Therefore, such relatively hydrophobic emulsifiers are expected to be located in the core of the nanoelement of the composition. The HLB values of these relatively hydrophobic emulsifiers are generally 9 or less, 8 or less, 7 or less, or 6 or less on the Griffin scale. The behavior of such surfactants can be considered to be similar to that of fatty amines, because the hydrophobic parts of the surfactants turn to the core and are embedded therein, and their hydrophilic parts turn to the shell, and can even be part of the shell that includes the amine head.
[0256] Emulsifiers that are more hydrophilic in nature have a relatively large hydrophilic portion and will be more compatible with the polar phase of the composition, and thus may be referred to as polar carrier soluble emulsifiers (or surfactants in general). Such relatively hydrophilic emulsifiers typically have an HLB value of 11 or more, 13 or more, 15 or more, 17 or more, or 20 or more.
[0257] Emulsifiers with HLB values in the range of 9 to 11 are considered "intermediate" emulsifiers, which have a fairly balanced hydrophobic and hydrophilic portion. Such intermediate emulsifiers can be added to the CSSC or polar carrier in the present method, and thus can be found in the nanoelement or its medium, and the ability of a portion of this surfactant to migrate between the two phases is also envisioned.
[0258] Surfactants as emulsifiers are selected from alkyl sulfates, sulfosuccinates, alkylbenzene sulfonates, acylmethyltaurates, acylsarcosinates, isethionates, propeptide condensates, monoglyceride sulfates, ether sulfonates, ester carboxylates, fatty acid salts, quaternary ammonium compounds, betaines, alkylamphopropionates, alkyliminopropionates, alkylamphoacetates, fatty alcohols, ethoxylated fatty alcohols, poly(ethylene glycol) block copolymers; ethylene oxide (EO) / propylene oxide (PO) copolymers, alkylphenol ethoxylates, alkyl glucosides and polyglucosides, fatty chain alkanolamides, ethoxylated fatty acids, sorbitan derivatives, alkyl sugar esters, amine oxides, cetearyl ether, oily ether, alkylamines (other than fatty amines), fatty esters, polyoxyethylene-glycerides, natural oil derivatives and carboxylic acid esters.
[0259] In a specific embodiment, the emulsifier is selected from: vitamin ETPGS, polyethylene glycol block copolymers, a mixture of type I polyethylene glycol 6 stearate, ethylene glycol stearate and type I polyethylene glycol 32 stearate (for example, commercially available from Gattefossé, France). 63), a mixture comprising an olive oil derived extract (e.g. commercially available under the brand name of Medolla Iberia from Spain) ), ascorbyl palmitate, polyglyceryl-10 pentaoleate, polyglyceryl-10 pentaisostearate, oleoyl polyoxylglyceryl-6 glycerides (commercially available, for example, from Gattefossé, France M1944CS), disodium laurethsulfosuccinate, disodium lauryl sulfosuccinate, disodium lauryl sulfosuccinate, C 14 -C 16 A mixture of sodium olefin sulfonate and lauroyl amide propyl betaine (commercially available from Colonial Chemical Company, USA, for example) Det EQ-154) and a mixture of olive oil and glutamic acid (e.g. commercially available from Kalichem, Italy glutamate).
[0260] While surfactants acting as emulsifiers are generally sufficient to stabilize the nanoelements of the compositions of the invention, the inventors have found that when CSSC is present at relatively high concentrations, as allowed by the invention, the addition of another type of surfactant, a hydrotrope, helps achieve satisfactory stability.
[0261] Hydrotropes are also amphiphilic molecules, but in contrast to emulsifiers, they contain relatively short lipophilic chains. Since the lipophilic portion of a hydrotrope is usually too short to form micelles, a hydrotrope can alternatively dissolve the hydrophobic compound in a polar carrier and allow co-emulsification with an emulsifier. In general, a hydrotrope is primarily miscible in the polar carrier phase (e.g., aqueous phase) of a nanosuspension and is characterized by having an HLB value of 10 or greater, 12 or greater, 15 or greater, or 18 or greater.
[0262] Suitable hydrotropes may be selected from the group comprising: sodium dioctyl sulfosuccinate, urea, sodium toluene sulfonate, adenosine triphosphate, cumene sulfonate, toluene sulfonic acid, xylene sulfonic acid, cumene sulfonic acid and salts thereof. In a specific embodiment, the hydrotrope is selected from: sodium dioctyl sulfosuccinate, urea and xylene sulfonate, such as ammonium xylene sulfonate.
[0263] Active Agent
[0264] Although the compositions of the present invention are biologically active due to the presence of CSSC itself, especially when the compositions are skin compositions for use on the skin to promote the synthesis of skin structural proteins, their use can be enhanced and / or modified by including active agents with similar functions, thereby enhancing efficacy, and / or including active agents with different functions, thereby expanding the scope of efficacy. In this case, the core-shell nanoelement can be considered as a nanocarrier for other active agents for topical application.
[0265] In some embodiments, the (e.g., skin-use) composition further comprises one or more active agents that are insoluble in polar carriers. Such carrier-insoluble active agents are typically contained in the core of the core-shell nanoelement because they are miscible with the components (i.e., CSSC) and the optional non-volatile liquid contained therein and the hydrophobic tail of the fatty amine embedded in the core. When forming a single phase, the components of the core are miscible with each other.
[0266] These activating agents that are expected to improve skin appearance and health when used alone or in combination with CSSC are known, and are only illustrated below. Information about other compounds known to have activity that is conducive to skin beauty care can be found in the list of recognized safe cosmetic ingredients (GRAS) disclosed on the FDA website, in the list provided in the European cosmetic ingredient database (COSING), or in any similar authoritative list issued by professionals related to the cosmetics industry. Activating agents suitable for drug therapy can be found in any similar authoritative list issued by professionals related to the pharmaceutical industry, such as the Drugs@FDA database of the FDA, the European Public Assessment Report (EPRRs) database of the European Medicines Agency (EMA), or in any similar authoritative list issued by professionals related to the pharmaceutical industry. Activating agents suitable for agricultural chemicals or industrial compositions can be found in the pesticide product information system (PPIS) maintained by the U.S. Environmental Protection Agency (EPA), in the EU pesticide database maintained by the European Commission Health and Food Safety Headquarters Committee (DG SANTE), or in any similar authoritative list issued by professionals related to the agricultural chemicals industry.
[0267] Although selected based on the activity they provide to the composition, CSSC-miscible / polar carrier-insoluble active agents may have a secondary function and, for example, optionally act as a plasticizer when capable of reducing the viscosity of the CSSC in the core.
[0268] In some embodiments, and similar to the CSSC and non-volatile liquids described above, the optional CSSC miscible / carrier-insoluble active agent should have a solubility of 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, or 0.1 wt % or less, based on the weight of the polar carrier or the liquid phase containing it.
[0269] CSSC-miscible / carrier-insoluble active agents incorporated into the nanoelements of the composition for skin use may include, but are not limited to, albendazole, benzoyl peroxide, bakuchiol, castor oil, ceramides, erythromycin, finasteride, ibuprofen, ketoconazole, lidocaine, macrolides, mebendazole, neem oil, retinol, salicylic acid, tadalafil, tetracyclines, tretinoin, vitamin A, vitamin D, and vitamin K. In particular embodiments, the carrier-insoluble active agent is bakuchiol, castor oil or retinol (e.g., for cosmetic uses), benzoyl peroxide or tadalafil (e.g., for therapeutic uses), and neem oil (e.g., as an insect repellent in humans).
[0270] In some embodiments, the (e.g., dermatological) composition further comprises one or more polar carrier-soluble active agents that will surround the first shell of the fatty amine to form a second shell. The second shell may consist of more than one layer of carrier-soluble active agents. As described above, non-covalent (e.g., electrostatic) interactions between the fatty amine and the carrier-soluble agent of the first shell, or covalent bonding between the two, facilitate the formation of such a second shell. Excess polar carrier-soluble active agents may additionally be present in dissolved form in the polar carrier.
[0271] Exemplary active agents that are soluble in the carrier and that can form the second shell of the nanoelement in the composition for skin use can be selected from the group consisting of azelaic acid, biotin, clindamycin, collagen, elastin, famciclovir, folic acid, hyaluronic acid (HA), niacin, pantothenic acid, riboflavin, thiamine, vitamin B12, vitamin B6, and vitamin C. In a particular embodiment, the carrier-soluble agent is a cosmetically active HA, which is a type of glycosaminoglycan.
[0272] It is known that when formulated into topical compositions, high molecular weight (HMW) carrier soluble active agents cannot be transferred across the skin. When dissolved in an aqueous environment, such HMW compounds tend to unfold and form expanded structures, which are unlikely to pass through any pathways present on the skin. Therefore, when not completely washed off from the skin, HMW molecules are expected to remain on the outer surface of the skin. On the contrary, the purpose of the nanoelement of the present invention is to penetrate into the skin, wherein they can especially serve as collagen synthesis stimulators, but more generally serve as nanocarriers. The core-shell structure of the nanoelement allows the HMW active agent to be arranged into an outer (second) shell, and is therefore transported to the skin in a compact manner. Therefore, it is expected that the core-multi-shell structure can be transdermally delivered even with an active agent of HMW, so that they can show their activity in their respective target sites.
[0273] In some embodiments, the carrier soluble active agent that can be combined with the core-shell nanoelement of the present invention is hyaluronic acid, and low molecular weight (LMW) (i.e., MW less than 600kDa) HA and high molecular weight (HMW) (i.e., MW greater than 600kDa) HA can be used. In some embodiments, HA is a LMW HA with a MW of 500kDa or less, 400kDa or less, 300kDa or less, 200kDa or less, or 100kDa or less. In specific embodiments, the molecular weight of LMW HA does not exceed 50kDa, does not exceed 25kDa, or does not exceed 10kDa.
[0274] In some embodiments, the (eg, dermatological) composition can include a carrier-insoluble active agent and a carrier-soluble active agent.
[0275] Plant-based products and extracts as active agents can also be added to the composition, and can be carrier-insoluble or carrier-soluble. As used herein, the term "plant extract" refers to a natural fraction separated from any relevant part of any suitable plant (e.g., flower, fruit, herb, leaf, skin, root, seed, stem, etc.), and refers to a synthetic form of an active agent of a natural extract. Plants, whose natural products or extracts are traditionally used for beauty or therapeutic effects when applied to the skin, are known to technicians and are too many to be listed comprehensively. For example, plant products or extracts containing active agents suitable for the present invention can be separated or obtained from apple, bergamot, cauliflower, hemp, coffee, corn, turmeric, fennel, angelica, ginseng, grapefruit, honey tree, Japanese red pine, kale, orange, red pepper, passion fruit, raspberry, Louis Boss tea, soybean, spinach, tea and tomato. These plant extracts are known to have anti-acne, antioxidant, anti-inflammatory and / or anti-aging activities. In a specific embodiment, the plant-based active agent used in the composition is curcumin.
[0276] The carrier-insoluble and / or carrier-soluble active agents optionally added to the skin composition of the present invention can have cosmetic functions, for example, have skin filling effects, or can themselves enhance collagen synthesis (and / or reduce its degradation). Considering the ability of CSSC or CSSP in the core of nanoelement to stimulate collagen synthesis independently, adding this active agent that can play a similar purpose can produce combined activity, thereby providing even higher collagen formation or existence in the skin. For example, the CSSC of the core can promote the new synthesis of collagen, elastin and / or glycosaminoglycan (and / or reduce their degradation), and the core-shell nanoelement can also include collagen, elastin, hyaluronic acid or its fragment as the water-soluble active agent on the nanoelement shell. No matter how the exact cosmetic effect of the active agent, the resulting skin composition can be considered to be "cosmetic activity".
[0277] Alternatively, the active agent (either carrier soluble or carrier insoluble) can be used for pharmaceutical purposes, making the composition "pharmaceutically active". All active agents, especially if already used in existing topical formulations for therapeutic purposes exemplified herein, are included. For example, the agent capable of treating skin disorders (e.g., having analgesic, anti-inflammatory and / or anti-arthritic activity) can be any known corticosteroid drug (e.g., ancicosin, betamethasone, clobetasol, desonide, dexamethasone, fluticasone, hydrocortisone, methylprednisolone, mometasone, etc.) or any known non-steroidal drug (e.g., diclofenac, etodolac, flurbiprofen, ibuprofen, indomethacin, ketoprofen, ketorolac, meloxicam, nabumetone, naproxen, piroxicam, sulindac, etc.).
[0278] Thus, in addition to their collagen synthesis capabilities, core-shell nanoelements can be used as nanocarriers for cosmetic or pharmaceutical agents to be administered to the skin of a subject.
[0279] Although above mainly for the activity related to skin described activating agent, but this should not be construed as limiting the purposes of the skin composition according to this teaching. Drugs that are delivered transdermally by conventional methods and target other organs or diseases can also be incorporated into the composition of the present invention, if relatively insoluble in water, then incorporated into the core of the nanoelement, or if relatively soluble in water, then incorporated into the shell. Such activating agents that are usually intended to be used in medicines for human subjects can be used for a variety of purposes, for example, as antidepressant, blood pressure regulation, contraception and pain relief.
[0280] Although based on Example 12, it is expected that the core-shell nanoelement of the present invention can carry active agents that cannot be delivered transdermally by conventional methods at present, such as active agents with a molecular weight of 600 g / mol or higher, it is understood that they can carry active agents that are known to be delivered transdermally. Some active agents that can be delivered transdermally are illustrated below, but other such compounds may be reported in future clinical studies or sales authorizations.
[0281] Non-limiting examples of such active agents include amitriptyline, apomorphine, asenapine, buprenorphine, capsaicin, clonidine, deutetrabenazine, ensam, estrogen, fentanyl, gabapentin, granisetron, ketamine, nicotine, methimazole, methylphenidate, nitroglycerin, oxybutynin, physostigmine, pramipexole, progestins, riluzole, rivastigmine, rotigotine, scopolamine, selegiline, sumatriptan, and testosterone.
[0282] Most of the active agents listed above that illustrate uses associated with treatment of human subjects can also be used in veterinary products for treating non-human animals. Compositions for dermatological use for veterinary use may additionally contain different active agents that are appropriate to the physiology of the animal to be treated, to the effect to be obtained (e.g., increasing meat, milk or wool production), and / or to the particular condition of the animal. For example, active agents that are more suitable for veterinary products and uses include agents that increase livestock productivity or protect animals (e.g., various pesticides, such as methoxychlor and carbaryl; anti-infective agents, such as isoflurane; and antibacterial agents, such as thiostrepton; to name a few).
[0283] In addition, the core-shell nanoelements of the present invention can be used to deliver active agents to surfaces other than the skin of living animals. In this case, the active agents can be considered as agricultural chemicals and / or industrial agents that can be incorporated into the CSSC nanoelements for use in these areas. Nanoelements containing these agents can be used as at least acaricides, algaecides, animal repellents, anthelmintics, moth repellents, avicides, bactericides, chemosterilants, fertilizers, fungicides, herbicides, insect pheromones, anthelmintics, insecticides, molluscicides, nematicides, nitrification inhibitors, ovicides, plant growth activators, rodenticides, termiticides and virucides.
[0284] Although attempts have been made to classify active agents according to the composition that a particular active agent may supplement or the specific activity that they may contribute to in a cosmetic, veterinary or human pharmaceutical product, agrochemical, or industrial product, as previously mentioned, there is overlap. For example, a fungicide may be used as a preservative in a cosmetic composition, as an active agent for treating fungal infections on the skin of a living subject, as a transdermally deliverable active agent for treating systemic fungal infections in animals, as an active agent for treating fungal infections in plants, or as an active agent for preventing the growth of mold on an inert surface.
[0285] Regardless of their activity and intended use, the active agents can be CSSC miscible / carrier-insoluble (in which case they are incorporated in the core of the core-shell nanoelement) or carrier-soluble (in which case they can be incorporated as a second shell surrounding the core-shell nanoelement).
[0286] Skin penetration enhancers
[0287] While a polar carrier may be sufficient to enable adequate retention of the CSSC nanoelements on and delivery through the skin, and some surfactants (if present) can facilitate it, in some embodiments, the topical composition also includes a skin penetration enhancer.
[0288] Suitable skin penetration enhancers can be selected from the group comprising: C1-C22 alcohols (e.g. short chain alcohols: ethanol, isopropanol and hexanol, and fatty alcohols: octanol, decanol, lauryl alcohol, myristyl alcohol, oleyl alcohol and octyldodecanol); amides, such as 1-dodecylazacycloheptane-2-one (also known as laurocapram and commercially available) and their analogs; N-alkyl-azepan-2-ones, wherein the alkyl group has the general formula CxH2x+1, X is an integer selected from 1, 3-10 and 14, branched and / or unsaturated chain N-substituted azepan-2-ones, N-acylazepan-2-ones, substituted 2-(2-oxoazepan-1-yl)alkanoic acids and esters thereof, N-alkyl-azepan-2-thiones, N-alkyl-azepanones, 4-alkyl-1,4-oxazacyclo-5,7-diones; cyclic amines having an alkyl group of the general formula CxH2x+1, X is an integer selected from 10-12, 14, 16 and 18; long chain N-acylazepanes, dehydroazepane derivatives, six-membered ring analogs, for example: azepanadiene, N-substituted piperidin-2-ones, derivatives of six-membered ring analogs of, 2-(2-oxopiperidin-1-yl)acetic acid esters, N-substituted derivatives of 6-oxopiperidin-2-carboxylic acid, N-1-(2-alkylthioethyl)-piperidine-3-carboxylic acid, (thio)morpholine, morpholinedione derivatives, long-chain N-acylmorpholines, long-chain N-morpholinyl enones, five-membered ring analogs: long-chain N-acylmorpholines and morpholineethanol derivatives, 1-piperazin-1-yl-alkane-1-ones and 1-(4-methylpiperazin-1)-yl)-alkane-1-ones; aromatic esters (e.g., octyl salicylate and isooctyl p-dimethylaminobenzoate; ether alcohols (e.g., 2-(2-ethoxy-ethoxy)ethanol); ethylene glycol; pyrrolidones (e.g., 2-pyrrolidone, N-methyl-2-pyrrolidone); and sulfoxides (e.g., dimethyl sulfoxide (DMSO) and decylmethyl sulfoxide).
[0289] Typically, if a skin permeation enhancer is present, it is added to the polar liquid phase. To the extent that they will be provided instead within the core-shell nanoelement, it should be noted that the skin permeation enhancer (or any other additive), which may be considered a volatile agent, should preferably not exceed 2 wt % by weight of the nanoelement.
[0290] It may be noted that some of the materials defined above as skin penetration enhancers may otherwise serve as part of the liquid phase, provided that their association with the primarily polar carrier does not affect the overall polarity of the liquid and the lack of solubility of the nanoelements therein.
[0291] Volatile organic compounds
[0292] Methods for preparing nanomaterials are described in the literature in great quantities, and the main methods are applicable to hydrophobic compounds, such as materials for the present invention, including emulsification. Conventional emulsification methods suitable for this purpose include oil-in-water (O / W) emulsification or W / O / W emulsification, which are usually achieved by solvent evaporation or solvent displacement (e.g., by solvent diffusion or salting out). These methods are cumbersome and time-consuming, and to some extent commercially unfeasible. More importantly, they usually result in solvent residues (but not negligibly) trapped in the nanoparticles prepared by these methods, which may be particularly critical when the solvent used is a volatile organic compound (VOC) with a high vapor pressure and a low boiling point at room temperature.
[0293] As used herein, the term "volatile organic compound" ("VOC") refers to an organic compound having a vapor pressure of 0.1 kPa or greater measured at a temperature of about 20°C.
[0294] Typically, when nanoparticles are reported to be obtained after dissolution of a polymer in a volatile solvent and subsequent evaporation, it is understood that the authors do not report their actual VOC content, since it is difficult to completely eliminate it. When relatively low amounts of VOC are actually measured and reported, the particles obtained are at least microparticles (e.g., having a particle size of 2-100 micrometers (μm)) rather than nanoparticles.
[0295] Contrary to the methods commonly used to prepare micro- or nanoparticles, the present invention does not use emulsification techniques that require the addition of solvents (e.g., VOCs) and the dissolution of CSSCs (particularly CSSPs) therein and the subsequent removal of the solvent. When the volatile solvent is subsequently removed from the conventionally prepared particles (presumably by a lengthy and cumbersome process), several phenomena are observed. Removal of the solvent can produce porous and brittle particles, and further, since removal of the solvent can simultaneously require the removal of the medium in which the particles can be dispersed, the process inherently leads to the collapse of the dispersion and the drying of the particles, which can then become aggregates or agglomerates. In order to eliminate the solvent used to prepare the particles, once dried, it is believed that the particles as individual particles generally have poor dispersibility and, if any, poor ductility. Such particles prepared according to the methods of the art are considered to be ineffective for the purposes of the present invention.
[0296] Thus, according to the present invention, VOCs such as conventionally used acetone, acetonitrile, aniline, benzene, carbon tetrachloride, chloroform, cyclohexanone, dichloromethane, dioxane, dimethyl sulfoxide, ethyl acetate, hexafluoroisopropanol, methyl chloride, N,N-dimethylformamide, 2-nitropropane, 1,1,2,2-tetrachloroethane, tetrahydrofuran, 1,1,2-trichloroethane and toluene, whether as a single solvent or as a mixture of two or more VOCs, are substantially absent from the nanoelements.
[0297] In some embodiments, the nanoelement comprising a CSSC in its core comprises less than 2 wt.%, less than 1.5 wt.%, less than 1 wt.% VOC (or a blend thereof) by weight of the nanoelement. In specific embodiments, the nanoelement comprises less than 0.5 wt.%, less than 0.4 wt.%, less than 0.3 wt.%, less than 0.2 wt.%, or less than 0.1 wt.% VOC (or a blend thereof) by weight of the nanoelement. In other specific embodiments, the nanoelement comprises less than 0.09 wt.%, less than 0.08 wt.%, less than 0.07 wt.%, less than 0.06 wt.%, less than 0.05 wt.%, less than 0.04 wt.%, less than 0.03 wt.%, or less than 0.02 wt.% VOC (or a blend thereof) by weight of the nanoelement. In some embodiments, the nanoelements may contain up to 0.001 wt % (which corresponds to 10 parts per million ppm), up to 0.002 wt % (20 ppm), up to 0.003 wt % (30 ppm), up to 0.004 wt % (40 ppm), up to 0.005 wt % (50 ppm), up to 0.006 wt % (60 ppm), up to 0.007 wt % (70 ppm), up to 0.008 wt % (80 ppm), up to 0.009 wt % (90 ppm), or up to 0.01 wt % (100 ppm) of VOCs (or blends thereof), based on the weight of the nanoelements.
[0298] In particular embodiments, the nanoelements comprise between 0% and 0.5%, between 0.0001% and 0.5%, between 0.0002% and 0.4%, between 0.0003% and 0.3%, between 0.0004% and 0.2%, between 0.0005% and 0.1%, between 0.0001% and 0.09%, between 0.0002% and 0.08%, between 0.0003% and 0.07%, between 0.0004% and 0.06%, or between 0.0005% and 0.05% VOC (or blends thereof) by weight of the nanoelements.
[0299] It is emphasized that the aforementioned low concentrations of VOCs are provided relative to the nanoelements because the liquid phase in which they are dispersed can tolerate higher amounts of such materials, which may be permitted by the resistance of the nanoelements to dissolution and / or may be authorized by the relevant regulatory agencies governing the use of compositions for any purpose for which the compositions of the present invention are suitable.
[0300] The nature and amount of the postulated VOC in the nanoelements can be determined by conventional analysis, for example by removing the polar carrier and analyzing the nanoelements isolated therefrom by, for example, gas chromatography. Exemplary standard methods for determining VOC are described in ASTM D4526 or VDA 277.
[0301] Composition
[0302] The various components that can be used in the present composition (e.g., for skin use) are reviewed, and suitable concentrations or respective ratios are provided below. It should be noted that some components according to the present teachings can play more than one role. For example, fatty amines can have plasticizing and / or dispersing capabilities, some of which themselves provide activities that can be considered as cosmetics or drugs; and some non-volatile liquids, such as aliphatic esters (e.g., dimethyl glutarate); fatty acids (e.g., lauric acid, linoleic acid, linolenic acid, myristic acid, oleic acid, palmitic acid, stearic acid and isostearic acid); fatty acid esters (e.g., ethyl oleate, monoolein, monocaprin, tricaprylin, isopropyl myristate, isopropyl palmitate, propylene glycol monolaurate and monocaprylate); and terpenes (e.g., eugenol, D-limonene, menthol, menthone, farnesol and nerol); may also have the property of enhancing skin penetration. In another example, some polar carriers, such as water and certain glycols and glycerols, may also aid in skin penetration, or even act as surfactants. Thus, when referring to, for example, the concentration of a skin penetration enhancer in a composition, this information refers only to the dedicated compound intentionally added to perform that function, and does not include compounds that have a different primary function in the composition.
[0303] In some embodiments, the concentration of CSSC (or a combination thereof) in the nanoelement is in the range of 1 wt % to 99 wt %, 1 wt % to 90 wt %, 5 wt % to 80 wt %, 10 wt % to 50 wt %, or 15 wt % to 40 wt % based on the total weight of the nanoelement.
[0304] In some embodiments, the concentration of CSSC in the composition is 0.1 wt % to 30 wt %, preferably 0.5 wt % to 25 wt %, 1 wt % to 20 wt %, or 1.5 wt % to 15 wt %, based on the total weight of the composition. In other embodiments, the concentration of CSSC is at least 0.1 wt %, at least 0.5 wt %, at least 1 wt %, or at least 1.5 wt %, based on the total weight of the composition. In other embodiments, the concentration of CSSC is at most 30 wt %, at most 25 wt %, at most 20 wt %, or at most 15 wt %, based on the total weight of the composition.
[0305] In some embodiments, the concentration of the fatty amine (or combination thereof) in the nanoelements ranges from 1 wt % to 99 wt %, 1 wt % to 90 wt %, 5 wt % to 80 wt %, 10 wt % to 50 wt %, or 15 wt % to 40 wt % based on the total weight of the nanoelements.
[0306] In some embodiments, the concentration of the fatty amine in the composition is in the range of 0.1 wt % to 30 wt %, preferably in the range of 0.5 wt % to 25 wt %, 1 wt % to 20 wt %, or 1.5 wt % to 15 wt %, based on the total weight of the composition. In other embodiments, the fatty amine concentration is at least 0.1 wt %, at least 0.5 wt %, at least 1 wt %, or at least 1.5 wt %, based on the total weight of the composition. In other embodiments, the fatty amine concentration is at most 30 wt %, at most 25 wt %, at most 20 wt %, or at most 15 wt %, based on the total weight of the composition.
[0307] In some embodiments, the concentration of the non-volatile liquid (if present in the nanoelement) is in the range of 1 wt % to 98 wt %, preferably in the range of 5 wt % to 90 wt %, 10 wt % to 80 wt % or 20 wt % to 70 wt % based on the total weight of the nanoelement. In some embodiments, the concentration of the non-volatile liquid is at least 1 wt %, at least 5 wt %, at least 10 wt % or at least 20 wt % based on the weight of the nanoelement. In other embodiments, the concentration of the non-volatile liquid is at most 98 wt %, at most 90 wt %, at most 80 wt % or at most 70 wt % based on the weight of the nanoelement.
[0308] In some embodiments, the concentration of the non-volatile liquid (if present in the composition) is in the range of 1 wt % to 30 wt %, preferably in the range of 2 wt % to 30 wt %, 3 wt % to 25 wt %, or 5 wt % to 20 wt %, based on the total weight of the composition. In some embodiments, the concentration of the non-volatile liquid is at least 1 wt %, at least 2 wt %, at least 3 wt %, or at least 5 wt % based on the weight of the composition.
[0309] In other embodiments, the concentration of the non-volatile liquid is up to 30 wt %, or up to 25 wt %, or up to 20 wt %, based on the weight of the composition. When a non-volatile liquid (or combination thereof) is added, its concentration is up to 400 wt %, preferably in the range of 5 wt % to 350 wt %, 10 wt % to 200 wt %, 25 wt % to 150 wt %, 25 wt % to 100 wt %, or 50 wt % to 125 wt %.
[0310] In some embodiments, the concentration of the surfactant (if present in the nanoelement) is in the range of 1 wt % to 50 wt %, in the range of 5 wt % to 50 wt %, in the range of 10 wt % to 50 wt %, in the range of 15 wt % to 45 wt %, or in the range of 20 wt % to 40 wt %, based on the total weight of the nanoelement. These concentrations refer to dedicated surfactants that are intentionally added for this purpose and do not include the presence of any other materials that can also act as surfactants (e.g., some fatty amines).
[0311] In some embodiments, if a dedicated surfactant (including, for example, an emulsifier and / or a hydrotrope) is present in the composition, its combined concentration is in the range of 0.1% to 60% by weight, in the range of 0.5% to 50% by weight, in the range of 1% to 40% by weight, or in the range of 1% to 30% by weight by the total weight of the composition. In some embodiments, the combined concentration of surfactants is at least 0.1% by weight, at least 0.5% by weight, or at least 1% by weight of the total weight of the composition. In other embodiments, the combined concentration of surfactants is at most 60% by weight, at most 50% by weight, at most 40% by weight, or at most 30% by weight by the total weight of the composition. Alternatively, the composition is substantially free of dedicated surfactants, and the concentration of one or more surfactants is less than 0.1% by weight by the total weight of the composition.
[0312] In some embodiments, the polar carrier is present in the composition in a range of 10 wt % to 99.8 wt %, 20 wt % to 99 wt %, 30 wt % to 90 wt %, or 40 wt % to 85 wt % based on the total weight of the composition.
[0313] In some embodiments, the carrier-insoluble active agent (if present in the nanoelements) is added to the CSSC at a concentration of up to 50 wt % by weight of the CSSC, preferably in the range of 0.5 wt % to 35 wt %, 1 wt % to 20 wt %, 2.5 wt % to 15 wt %, or 0.5 wt % to 10 wt %, such concentration ranges also apply to the nanoelements formed therefrom.
[0314] In some embodiments, if a carrier-soluble active agent is present, it is added to the nanosuspension at a concentration of up to 200 wt % of the CSSC, preferably in the range of 0.1 wt % to 170 wt %, in the range of 1 wt % to 150 wt %, in the range of 5 wt % to 100 wt %, in the range of 5 wt % to 50 wt %, in the range of 5 wt % to 40 wt %, or in the range of 10 wt % to 20 wt %.
[0315] In some embodiments, the concentration of any one of the carrier-soluble or carrier-insoluble active agents in the composition, or if more than one, the concentration of all of them, is in the range of 0.01% to 15% by weight, preferably in the range of 0.05% to 15%, 0.1% to 13%, 0.5% to 11%, or 0.5% to 10% by weight. In some embodiments, the concentration of any one of the active agents is at least 0.01%, at least 0.05%, at least 0.1%, or at least 0.5% by weight, by the total weight of the composition. In other embodiments, the concentration of all active agents or a single active agent is at most 15%, at most 13%, at most 11%, or at most 10% by weight, by the total weight of the composition.
[0316] In some embodiments, the concentration of the skin penetration enhancer (if present in the skin composition) is 0.01 wt.% to 30 wt.%, 0.1 wt.% to 25 wt.%, 1 wt.% to 20 wt.%, 3 wt.% to 15 wt.%, or 5 wt.% to 15 wt.%, based on the total weight of the composition.
[0317] Preferably, when the composition is intended to be a composition for skin use, the aforementioned ingredients are approved for cosmetic or pharmaceutical use at the desired concentrations. For example, they do not irritate the skin, nor cause allergic reactions or any other acute or chronic side effects. In addition, all ingredients need to be compatible with each other, such compatibility being as described above. As will be readily appreciated, this compatibility principle is affected not only by the chemical properties of the materials, but also by their relative proportions according to the intended use, and should preferably guide the selection of all materials required for the compositions disclosed herein.
[0318] Similar principles may be followed for agrochemical or industrial compositions, in which case the ingredients are preferably of a chemical nature and in concentrations approved by the regulatory agency governing such products.
[0319] Preparation method
[0320] In another aspect of the invention, a method for preparing a composition (e.g., for skin use) is provided, the composition comprising nanoelements having a core made of a water-insoluble collagen synthesis stimulating compound (CSSC) and a shell made of a fatty amine, in a specific embodiment, the core comprises a water-insoluble collagen synthesis stimulating polymer (CSSP), the core-shell nanoelements being dispersed as a nanosuspension in a polar liquid. The properties and characteristics of the materials used in the method are as described above for each material. The steps of the method are briefly shown in Figure 1 In the examples, and described in further detail below, steps with dashed outlines are optional.
[0321] In a first step (S01) of the method, at least one CSSC (eg, at least one CSSP) is provided.
[0322] In the second step (S02) of the method, the CSSC is mixed with at least one fatty amine. As described in optional step S02', the CSSC may be additionally mixed with one or more non-volatile liquids, which may promote plasticization or swelling of the CSSC by the liquid. Addition of non-volatile liquids is optional, since the viscosity of the CSSC provided in S01 may be sufficiently low (e.g., 10 7 mPa·s or less, at a temperature of 50°C and 10 sec -1 ) or, if necessary, the fatty amine mixed therewith can fully plasticize the CSSC.
[0323] The mixing of the CSSC with the fatty amine and any other agents (such as the optional plasticizing liquid) can be carried out at any suitable mixing temperature and / or mixing pressure suitable for such compounding.
[0324] The temperature at which mixing is carried out (which may include plasticization of the CSSC) is generally selected according to the temperatures characterizing the substances involved in the process, for example by taking into account the Ts, Tm and / or Tg characterizing the CSSC and, optionally, the Tb of the aliphatic amine (referred to as Tb a ) and / or non-volatile liquid Tb (referred to as Tb l ) and / or the degradation point of the aliphatic amine. As previously mentioned, the mixing temperature will suitably be (e.g., by at least 5°C, at least 10°C, at least 15°C, or at least 20°C) above at least one of the characteristic temperatures of the CSSC and (e.g., by at least 5°C, at least 10°C, at least 15°C, or at least 20°C) below the lowest of the boiling temperature and / or the degradation point of the aliphatic amine and / or the boiling temperature of the non-volatile liquid at the pressure at which the mixing step is performed, but this upper limit is not required as long as the selected mixing temperature does not significantly cook off or degrade any material to be mixed with the CSSC to form the core of the nanoelement. Thus, in some cases, the mixing temperature may even be Tb a , Tb l , or if the step is short enough, and / or the non-volatile liquid is in sufficient excess, and / or the mixing is done in a sufficiently sealed chamber to limit its evaporation / favor its condensation back into the mixture, it can be the point of fatty amine degradation.
[0325] It can be easily understood that the change in the properties of the substance reflected by the drop in these temperatures from the first value to the second value can alternatively occur at a lower mixing temperature or at a higher mixing temperature, if the pressure in the sealed chamber responsible for the mixing process ensuring the plasticization of the CSSC is reduced or increased accordingly. Therefore, although in the description of the method suitable for preparing the composition according to the present teachings, reference may be made to specific temperatures and durations, assuming that the process is carried out at standard atmospheric pressure, such guidance should not be considered restrictive and covers all temperatures and durations that achieve similar results with respect to the behavior of the plasticized CSSC and / or the charge rate of the nanoelements taking into account the activity of the fatty amine.
[0326] It should be noted in this context that when the CSSC is a CSSP, while the Tm and / or Tg of a polymer may set relatively well-defined temperatures below and above which the polymer may behave differently, this does not generally apply to Ts. Due to its viscoelastic properties, a polymer or plasticized polymer may remain "sufficiently solid" even at temperatures slightly above its formal softening point.
[0327] The mixing or plasticizing can be performed under a variety of conditions, such as elevated temperature (i.e., 30° C. or higher, e.g., at 40° C. or higher, at 50° C. or higher, at 60° C. or higher, at 75° C. or higher, or at 90° C. or higher) and / or elevated pressure (i.e., 100 kPa or higher, e.g., at 125 kPa or higher, 150 kPa or higher, 175 kPa or higher, 200 kPa or higher, 250 kPa or higher, or 300 kPa or higher). Since the mixing step can usually achieve at least some plasticization of the CSSC, it can also be referred to as a plasticizing step, and the above temperature and / or pressure usually accelerates the plasticizing process (i.e., shortens the duration of the plasticizing cycle) or can achieve a boiling point Tb at which the non-volatile liquid or fatty amine may evaporate. a or Tb l The desired modification of Tb due to mixing under high pressure a and / or Tb l , the temperature range in which plasticization can be performed can be expanded accordingly. Conversely, plasticizing CSSC under conditions more unfavorable than the conditions set arbitrarily to evaluate the ability of CSSC to be plasticized by a specific agent, for example at a temperature below 50°C and / or a reduced pressure below 100 kPa, can prolong the plasticization process, if necessary. The ability of CSSC to be plasticized or swelled by a specific plasticizer can be evaluated under any of the above temperature or pressure conditions.
[0328] The plasticizing time can also be shortened by mixing the CSSC with the fatty amine and the optional non-volatile liquid by stirring the mixture, which stirring additionally ensures that all parts of the CSSC are plasticized in a relatively uniform manner, and the plasticized CSSC appears reasonably uniform with respect to the subsequent steps of the process and the results expected therefrom. If excess non-volatile liquid is used during the plasticizing process, it can optionally be removed before proceeding to the subsequent steps. When the viscosity of the material being plasticized is relatively high, the mixing step can also be referred to as ingredient mixing, and the mixing equipment can be selected accordingly.
[0329] The duration of plasticization depends inter alia on the CSSC being plasticized, the non-volatile liquid used, the plasticization conditions (such as temperature, pressure and / or stirring) and the desired degree of plasticization. The plasticization time may be at least 1 minute and at most 4 days.
[0330] In some embodiments, additional materials may be optionally introduced into the CSSC and added in the mixing step S02, depending on the requirements of the process and / or the final composition. These CSSC-miscible and generally polar carrier-insoluble materials may (as shown in step S02') be at least one polar carrier-insoluble surfactant that acts as an emulsifier, and / or at least one polar carrier-insoluble active agent that enhances or alters the biological activity of the composition, and / or at least one CSSC-miscible pH adjuster, or any desired additive. The mixing conditions may be adapted to the presence of these additional ingredients.
[0331] Mixing can be carried out by any method known to those skilled in the art, such as ultrasonic treatment, use of a double-jacketed planetary mixer or a high shear mixer, etc. When the materials being mixed have a relatively high viscosity, the mixing step can be carried out with a double-roll mill, a triple-roll mill, an extruder, and the like. In a specific embodiment, mixing is carried out by ultrasonic treatment.
[0332] In the third step (S03) of the method, a mixture of CSSC and fatty amine (optionally also containing at least one CSSC miscible material, such as a non-volatile liquid, a surfactant, a carrier-insoluble active agent and a pH adjuster) is mixed with at least one polar carrier. If desired, at least one surfactant, which is a relatively polar emulsifier or hydrotrope, may be added to the polar carrier in this step. Other materials soluble in the polar carrier may also be added in this step, but may likewise be introduced after the subsequent nanosizing step.
[0333] In a fourth step (S04) the mixture is nanosized to form a nanosuspension, whereby nanoelements having a core comprising CSSC and optionally containing other or CSSC miscible and / or polar carrier insoluble materials and a shell comprising a fatty amine (and optionally some surfactants or other materials having a hydrophobic tail and a hydrophilic head enabling the shell to bind to the amine portion of the fatty amine) are dispersed in a polar liquid comprising a polar carrier optionally combined with other polar materials.
[0334] The nanoemulsion thus produced may be "self-emulsifying", so that no dispersant needs to be added to obtain the sought dispersion of core-shell nanodroplets. Without wishing to be bound by theory, it is believed that the present method embeds at least a portion of the hydrophobic tail of the fatty amine (or the hydrophobic portion of any other carrier-insoluble material mixed with the CSSC), which is naturally oriented towards the hydrophobic core, while the amine head of the fatty amine (or the hydrophilic portion of another suitable material) is turned towards the polar carrier, forming a shell around the core. Therefore, the method allows the preparation of nanodroplets with a hydrophobic core of CSSC (optionally with a non-volatile liquid and / or a carrier-insoluble active agent, etc.), the hydrophobic core is surrounded by the amine heads pointing outwards, forming a first shell, and the nanodroplets are dispersed in the polar carrier. Since the amine groups of the shell can be charged by the polar liquid, similarly charged nanodroplets can repel each other and thus remain dispersed.
[0335] Since nanosizing is usually performed by applying shear at relatively elevated temperatures, the core-shell nanoelements including CSSC are usually nanodroplets in this step, and the resulting nanosuspension is a nanoemulsion.
[0336] Nanoemulsions can be obtained by nanosizing the mixture of the desired materials by any method capable of shearing the CSSC (whether plasticized or not, or containing additional compounds), the method of shearing being selected from the group consisting of: ultrasonic treatment, milling, attrition, high pressure homogenization, high shear mixing, and high shear microfluidization. In a specific embodiment, the nanosizing is performed by ultrasonic treatment.
[0337] The nanosizing is performed at a shearing temperature that is at least equal to at least one of the first Ts, Tm and Tg of the CSSC, and if plasticized, at least equal to at least one of the second Ts, Tm and Tg of the CSSC, and in some embodiments, may be at least 5°C higher, at least 10°C higher, or at least 15°C higher than the highest characteristic temperature of the sheared CSSC mixture. However, although this is not necessary if the shearing step is sufficiently brief and / or the polar liquid is sufficiently excessive, the shearing temperature should preferably prevent a significant amount of the liquid phase from being boiled off and avoid significant degradation of the fatty amine. In some embodiments, the nanosizing temperature at which shearing is performed does not exceed at least one of the boiling point of the liquid phase being sheared (or any other liquid whose evaporation should be prevented) and the degradation point of the fatty amine (or the temperature to which any other material whose thermal degradation (e.g., inactivation, destruction, etc.) should be prevented). Therefore, the shearing temperature is generally lower than the polar carrier Tb (referred to as Tb) at the pressure at which the nanosizing step is performed. c ) and the lowest value of the degradation point of the material mixed with CSSC. For example, when the polar carrier is water, the shear temperature can be selected to be below 95°C, below 90°C, below 85°C or below 80°C, assuming that the nanosizing is carried out at atmospheric pressure. However, if the nanosizing is carried out at elevated pressure, the Tb of the polar carrier is c will increase, and the shear temperature may increase accordingly. Still using water as an example, although its Tb is 100°C at about 100 kPa, the boiling point increases to 120°C at about 200 kPa, in which case the nanosizing temperature that should not be exceeded may be at most 115°C. As mentioned above, these upper limits, while preferred, are not essential, since any boiling or degradation of the moieties (e.g. polar carrier or fatty amine) may be prevented at even higher temperatures if the steps are sufficiently short, and / or the polar carrier is sufficiently in excess and / or the nanosizing is performed in a sufficiently sealed chamber to limit its evaporation / favor its condensation back into the nanosuspension.
[0338] At a shear temperature above Ts, Tm or Tg and optionally below Tb of the liquid carrier c Or within the degradation temperature range of suitable fatty amines, CSSC, especially CSSP can be completely melted, and the nano-sizing process can be considered as "melt nanoemulsification".
[0339] In the fifth step (S05) of the method, if necessary in the manufacture, the nanoemulsion can be optionally actively cooled to a temperature below the Tm, Ts or Tg of the CSSC (or plasticized CSSC) to accelerate the relative solidification of the core-shell nanoelement. This cooling can be actively achieved by refrigerating the nanosuspension (e.g., placed in a coolant with the required low temperature), by subjecting the nanosuspension to continuous stirring to accelerate heat dissipation (and incidentally maintaining their proper dispersion when the nanodroplets cool), or by combining these two methods. This step is optional because the nanoemulsion can be passively cooled without any stirring when nanosizing is terminated. When combined with water (pH-adjusted water) and / or a polar carrier soluble active agent in a subsequent optional step, the nanoemulsion can also be passively cooled, provided that they are at a sufficiently low temperature to allow the nanoemulsion to cool. Despite cooling, CSSC (or plasticized CSSC) can remain in liquid form as nanodroplets if performed during the manufacturing process, or can be easily converted back into nanodroplets once applied to a subject with a skin surface or body temperature exceeding 30°C, which temperatures in mammals are typically above 32°C and 35°C, respectively.
[0340] Figure 3 Schematically depicts a core-shell nanoparticle 300 in a non-aqueous polar carrier, the absence of water preventing the amine head of the fatty amine from being charged. The uncharged nanoelement comprises a core 310 composed of a CSSC and optionally a non-volatile liquid and / or a carrier-insoluble surfactant and / or a carrier-insoluble active agent, which captures at least a portion of the hydrophobic tail 314 of the fatty amine. The polar head 322 of the fatty amine (including primary, secondary, tertiary and quaternary amines) represented by a circle "N" points away from the surface 312 of the core, forming the shell 320 of the nanoelement.
[0341] In some embodiments, at least 50% (D N 50) or at least 50% by volume (D V 50) have the hydrodynamic diameter of 200nm at the most, 190nm at the most, 175nm at the most, 150nm at the most, 125nm at the most or 100nm at the most, 90nm at the most, 80nm at the most or 70nm at the most.In some embodiments, the median diameter of nano element is at least 5nm, at least 10nm, at least 15nm or at least 20nm.Advantageously, these values are determined by the quantity of core-shell nano element, usually measured at room temperature.
[0342] As will be readily appreciated, depending on the temperature at which the nanoelement material is characterized and / or the temperature at which measurements can be made, the core-shell nanoelement can be a relatively liquid nanodroplet or a relatively solid nanoparticle when the temperature is reduced. The size of the nanoparticle at room temperature is comparable to or slightly more compact than the size of the nanodroplet, with their median diameter being no more than 200 nm.
[0343] In some embodiments, the size of core-shell nanoparticles or nanodroplets is determined by microscopy techniques known in the art (e.g., by CryoTEM). In some embodiments, the size of the nanoelement is determined by dynamic light scattering (DLS). In the DLS technique, particles are approximated as spheres with equivalent behavior, and sizes can be provided based on hydrodynamic diameters. DLS can also assess the size distribution of a population of nanoelements.
[0344] The distribution results can be expressed as a hydrodynamic diameter for a given percent of the cumulative size distribution, expressed in terms of number of particles or volume, and are usually provided for the 10%, 50% and 90% cumulative size distributions. For example, D50 refers to the maximum hydrodynamic diameter below which 50% of the sample volume or number of particles (as appropriate) exist, and are interchangeably referred to as the median diameter per unit volume (D50), respectively. V 50) or unit number median diameter (D N 50), often more simply referred to as the mean diameter.
[0345] In some embodiments, the nanoelements of the present disclosure have a cumulative particle size distribution of D90 of 500 nm or less, or D95 of 500 nm or less, or D97.5 of 500 nm or less, or D99 of 500 nm or less, i.e., 90%, 95%, 97.5% or 99% of the sample volume or number of particles, respectively, have a hydrodynamic diameter of no greater than 500 nm.
[0346] In some embodiments, the cumulative size distribution of a population of core-shell nanoelements (eg, nanoparticles) is calculated based on the number of particles (expressed as D N ) or according to the sample volume containing particles with a given hydrodynamic diameter (denoted as D V ) to evaluate.
[0347] Any fluid dynamic diameter having a cumulative particle size distribution of 90%, or 95%, or 97.5%, or 99% of a particle population, whether based on the number of particles or the sample volume, may be referred to hereinafter as the "maximum diameter", i.e., the maximum fluid dynamic diameter of the particles present in the population under the respective cumulative particle size distribution.
[0348] It should be understood that the term "maximum diameter" is not intended to limit the scope of the present teachings to nanoparticles having a perfect spherical shape. As used herein, the term includes any representative size of particles at least 90%, such as 90%, 95%, 97.5% or 99% of the cumulative particle size distribution, or at any other intermediate value of the population distribution.
[0349] In some embodiments, the core-shell nanoparticles or nanodroplets may be uniformly shaped and / or within a symmetrical distribution relative to the median of the population and / or within a relatively narrow size distribution.
[0350] A particle size distribution is considered to be relatively narrow if at least one of the following conditions applies:
[0351] A) the difference between the hydrodynamic diameters of 90% of the nanoelements and the hydrodynamic diameters of 10% of the nanoelements is equal to or less than 250 nm, equal to or less than 200 nm, equal to or less than 150 nm, or equal to or less than 100 nm, which can be mathematically expressed as: (D90-D10)≤250 nm, etc.;
[0352] B) the ratio between a) the difference between the hydrodynamic diameters of 90% of the nanoelements and 10% of the nanoelements; and b) the hydrodynamic diameters of 50% of the nanoelements is no greater than 2.5, no greater than 2.0, no greater than 1.5, or even no greater than 1.0, which can be mathematically expressed as: (D90-D10) / D50≤2.5, etc.; and
[0353] C) The polydispersity index of the nanoelement is equal to or less than 0.5, equal to or less than 0.4, equal to or less than 0.3, or equal to or less than 0.2, which can be mathematically expressed as: PDI = σ 2 / d 2 ≤0.5, etc., where σ is the standard deviation of the particle size distribution, d is the average size of the particles, and PDI is optionally equal to 0.01 or greater, 0.05 or greater, or 0.1 or greater.
[0354] PDI information is generally readily available from instruments used to measure the hydrodynamic diameter of nanoparticles.
[0355] When the nanoelements are electrostatically charged, preferably positively charged, this facilitates their further coating by an outer shell of a carrier soluble active agent suitably having an opposite charge, and the resulting core-multishell forms a more moderately charged or even uncharged nanoelement. Moderately charged core-multishells can generally remain positively charged, but less than their respective core-shells lacking the second shell of the active agent. Alternatively, the core-multishell can become negatively charged, as long as the collapse of the composition can be avoided (e.g., by the aggregation of the nanoelements at their isoelectric points).
[0356] The skin surface is usually negatively charged, so the total charge of the nanoelement, especially contributed by the CSSC of the core, the fatty amine of the first shell and the active agent, can adjust the efficacy of skin penetration. It is believed that more positively charged nanoelement (regardless of the number of shells), although expected to be better retained on the skin surface, will have a slower transdermal delivery rate compared to less positively charged or even negatively charged nanoelement (e.g., core-multi-shell nanoelement that is usually fully surrounded by a negatively charged active agent). Negatively charged nanoelement may be slightly repelled when passing through the skin, and this phenomenon pushes them further "downward" through the skin.
[0357] Based on this theory, it is believed that the relative penetration of nanoelements into the skin can be controlled to a certain extent not only by their size and / or ductility (e.g., viscosity) but also by their charge (e.g., by the value of their positive charge). If the problem treated by the skin composition of the present invention occurs on the skin surface due to microbial infection, it may be beneficial to use core-shell nanoelements that additionally contain an active agent that can alleviate or treat the infection in its core and / or secondary shell. In this case, the nanoelements can carry sufficient positive charge to prolong their retention on or near the skin surface so that the active agent can act more quickly on the target site when released from the nanoelements. On the contrary, if the activity of the CSSC and / or the active agent it carries is targeted away from the skin surface, it may be beneficial to use core-shell nanoelements with a charge that promotes its transdermal delivery.
[0358] When a composition comprising charged core-shell nanoelements is repeatedly applied to the skin, for example for the treatment of chronic skin conditions (e.g. atopic dermatitis, psoriasis, etc.) or for accidental skin traumas that generally require long-term healing (e.g. skin burns, skin grafts, significant surgical incisions, etc.), it may be beneficial to retain the nanoelements applied in the first dose on the skin surface to be treated for as long as possible to prolong efficacy and / or delay the need for the next dose. However, it is possible to apply subsequent doses of nanoelements when the surface to be re-treated still includes "residues" of the previous dose. For example, assuming that the core-shell nanoelements of the first dose are positively charged, it is conceivable that at least a portion of the residue may remain on the negatively charged skin even after the surface to be re-treated is washed before subsequent applications. Without wishing to be bound by theory, it is believed that repeated application of such charged nanoelements may lead to electrostatic repulsion of newly applied doses with the same charge over time. In fact, the effect of such a dose may no longer be perceived by the surface to be treated. In the case of such long-term treatment, which may disadvantageously result in the disappearance of newly applied nanoelements of the same charge, it may be beneficial to change the charge of the core-shell nanoelements applied to the skin. In the present specification, core-shell nanoelements with negative charges can be used to overcome the repulsion of previously applied nanoelements of the same charge to positively charged elements. Negatively charged nanoelements can be composed only of a core that can be negatively charged under physiological conditions, or can be a core-multi-shell nanoelement with a negatively charged outer shell surrounding a positively charged first shell.
[0359] Without wishing to be bound by theory, it is believed that the charge of the nanoelement having only a single shell is primarily contributed by the amine head of the fatty amine. When exposed to an aqueous environment, the fatty amine head becomes positively charged due to protonation of the amine group at a suitable pH, with the protons being provided from the water. Therefore, when the polar carrier is an aqueous polar carrier (e.g., water or an aqueous mixture), the nanoelement can generate a positive charge.
[0360] However, when a non-aqueous polar carrier is used during the preparation of the nanoelement, it is believed that by forming a coordinate bond with the amine head, the polar carrier cannot protonate the molecules of the first shell, "masking" any positive charges that might otherwise potentially form on the surface of the core-shell nanoelement in the presence of a liquid capable of protonation. In this case, or when the positive charges detected in the liquid carrier are believed to be insufficient, unmasking of the charges or their increase can be performed by replacing at least part of the polar carrier with water (e.g., by combining the nanosuspension with water), thereby creating an aqueous environment in which the charges can be acquired or generated.
[0361] Although water itself is capable of creating an environment in which protons are available to some extent to produce a positive charge on the amine head, a pH adjuster, preferably an acid, can be added to further promote protonation. It is believed that the acid reacts with the polar carrier molecules (presumably through hydrogen bonding), moving them away from the shell surface of the nanoparticle and exposing the amine head to a proton-rich aqueous environment, thereby allowing a positive charge to form on the shell surface. Alternatively, a base can be added to the polar carrier to help the amine carry a positive charge, even if slightly less than the acidic agent. If added to the composition, an alkaline pH adjuster can optionally further help the carrier-soluble active agent carry a negative charge. This addition of an acid or base to the nanosuspension can be referred to as "acid doping" or "base doping", respectively.
[0362] The negative charge of the material resulting from the formation of the second shell, whether or not enhanced by doping, is expected to promote their attraction to the positively charged core-shell nanoelements, thereby promoting the formation of core-multi-shell nanoelements by non-covalent electrostatic charges. Alternatively or additionally, the active agent of the second shell can be selected to covalently bond to the material of the first shell (e.g., fatty amines, surfactants, etc.).
[0363] The amount of pH adjusting agent added to the composition should be controlled so as to create an environment that maintains a balance between the sufficient positive charge of the fatty amine and the sufficient negative charge of the carrier-soluble active agent, their respective opposite charges being sufficient to attract each other. For example, the amount of acidic agent should be high enough to allow for an optimal positive charge of the amine head, but low enough to keep the carrier soluble enough to be negatively charged.
[0364] As the particle size decreases, their specific surface area increases, and thus the amount of material that may be present on their outer surface increases. Since the nanoelements of the present invention are characterized in particular by a D of 200 nm or less, N 50. In some embodiments, the nanoelements may be small enough to achieve a high enough specific surface area to allow for sufficient amine head groups to exist within the shell to contribute to the desired positive charge of the nanodispersion. In this case, the use of a pH adjuster that can be used to further increase the charge may be superfluous (as demonstrated in Example 4 below).
[0365] Although the formation of core-shell nanoelements has been described, the core-shell nanoelements have a first shell including a positively chargeable amine portion of an aliphatic amine, such that a second shell may include a material that may be negatively chargeable under the same conditions, this should not be construed as limiting. The core-multishell nanoelements may alternatively be prepared using core-shell nanoelements having a first shell that includes a negatively chargeable portion of an aliphatic compound (e.g., a carboxylic acid portion of a fatty acid), such that a second shell that may be formed thereon may include a material that may be positively chargeable under the same conditions.
[0366] When the polar carrier added in step S03 for nanosizing is non-aqueous, the method may optionally include a sixth step ( Figure 1 S06), thereby replacing at least part of the polar carrier with water or pH-modified water. As mentioned above, when the polar carrier is water or a mixture thereof with a non-aqueous polar carrier, this replacement step may not be necessary.
[0367] Alternatively, in the third step of the method ( Figure 1 S03), a pH-adjusted aqueous solution of a polar carrier can be used so that hydrogen ions are present in the mixture, allowing the amine group of the fatty amine to be protonated, thereby at least partially avoiding a possible masking effect of the polar carrier.
[0368] In some embodiments, the pH adjuster is added in an amount such that the composition has a pH between 1 and 10, between 1 and 9, between 1 and 8, between 2 and 7, or between 2 and 5. In specific embodiments, the pH adjuster is added in an amount to provide a pH of 7 or less, 6 or less, 5 or less, or 4 or less.
[0369] In some embodiments, the core-shell nanoelements have a positive charge of +5 mV or more, +10 mV or more, +20 mV or more, +30 mV or more, or +40 mV or more when placed in an aqueous environment at room temperature.
[0370] In other embodiments, the core-shell nanoelements have a negative charge between -60mV and -5mV, between -50mV and -5mV, between -40mV and -5mV, between -30mV and -5mV, or between -20mV and -5mV when placed in an aqueous environment at room temperature.
[0371] In further embodiments, the core-shell nanoelements have a near-neutral charge of -5 mV to +5 mV when placed in an aqueous environment at room temperature, such as in the presence of a non-ionic surfactant.
[0372] The core-shell nanoelements described above can be formulated into skin compositions (e.g., creams, gels, etc.) and applied to the skin of a subject (e.g., a human or non-human animal, including but not limited to a mammal) to, inter alia, promote collagen synthesis or any other cosmetic or pharmaceutical effect that can be achieved by an optional active agent.
[0373] Alternatively, the core-shell nanoelement can be used as a nanocarrier for other active agents. Figure 1In S07), a carrier soluble active agent is added to the previously obtained core-shell nanoelement. The added active agent can coat the outer surface of the core-shell nanoelement to form a second shell. The second shell can be covalently and / or non-covalently connected to the first shell. This nanoelement can be called a core-multi-shell nanoelement, or a core-multiple shell nanoelement or an active agent coated core-shell nanoelement.
[0374] The amount of carrier-soluble active agent to be added to the nanosuspension (optionally a nanodispersion) may depend in particular on the particle size of the nanoelement and the corresponding surface area available for attachment. In addition, the respective zeta potentials of the core-shell nanoelement and the carrier-soluble active agent may also indicate their respective proportions in which they may be present in the composition to optimize the formation of core-multi-shell nanoelement, if necessary, avoiding the presence of excess active agent in the polar carrier. Although such excess is allowed, in particular as long as the stabilization of the second shell is promoted, if the molecules of the carrier-soluble active agent have a high molecular weight, too much unbound active agent may be superfluous, hindering their transdermal delivery (if necessary).
[0375] Due to the zeta potential difference between the zeta potential (ζ1) of the original core-shell nanoelement induced by the fatty amine of the first shell and the zeta potential (ζ2) of the active agent caused by the formation of the second shell, the connection of the carrier-soluble active agent to the core-shell nanoelement is allowed or promoted. In some embodiments, the absolute value of the zeta potential difference (Δζ) defined as Δζ=|ζ2-ζ1| is at least 5mV, at least 10mV, at least 15mV, at least 20mV, at least 25mV or at least 30mV, which can be measured in the presence of water or an aqueous polar carrier.
[0376] In some embodiments, the active agent-coated nanoelements of the present invention have an average hydrodynamic diameter D of 200 nm or less, 190 nm or less, 175 nm or less, 150 nm or less, 125 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less. N 50. In some embodiments, the D of the active agent-coated core-shell nanoelement is N 50 is 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more.
[0377] Figure 4 Such a core-multishell nanoparticle 400 coated with a carrier soluble active agent is schematically depicted in an aqueous environment.
[0378] Compared with the previous Figure 3Similar to the nanoparticle 300 described in , the nanoparticle 400 includes a core 410 in which at least a portion of the hydrophobic tail 414 of the fatty amine is embedded. Unlike the nanoparticle 300 dispersed in the non-aqueous polar carrier, the aqueous environment in which the nanoparticle 400 is dispersed allows the polar head 424 of the fatty amine to be positively charged, thereby forming a nanoparticle first shell 420 that is now positively charged and surrounds the surface 412 of the core. This charging of the first shell allows the carrier-soluble active agent molecule 432 to attach to the surface of the nanoparticle first shell 422, resulting in the formation of a second shell 430 including the active agent, wherein the Δζ between the active agent and the first shell of the nanoelement is as described above. The polar soluble active agent molecule can be negatively charged, resulting in a relatively large Δζ between the first shell 420 of the positively charged nanoparticle and the active agent molecule 432. Alternatively, the active agent molecule can be positively charged in the polar carrier, resulting in a relatively small Δζ and a relatively weak attraction compared to the negatively charged molecule. However, as long as Δζ is 5 mV or higher, the condition is sufficient to form the second shell 430. In certain embodiments, the carrier soluble active agent molecules are negatively charged. Figure 4 An exemplary first shell is described that surrounds the core, making it positively charged so that a carrier-soluble active agent suitable for forming a second shell thereon can be negatively charged, but the core-shell nanoelement can alternatively be negatively charged, thereby allowing the formation of a second shell made of a positively charged carrier-soluble active agent. A negatively charged core-shell can be obtained by adjusting the environment of the nanoelement, or by using an aliphatic compound with a negatively charged hydrophilic head instead of a positively charged aliphatic compound to form the first shell. For example, a fatty acid is used instead of a fatty amine.
[0379] Although in the above detailed methods, some ingredients have been described as being introduced (or optionally introduced) into the composition at a specific step, this should not be construed as limiting. For example, depending on the material from which they are selected, if intended for delayed leaching, the pH regulator can be added during the optional step S02' with the non-volatile liquid, or during the step S03 with the polar carrier, or added to the liquid polar phase of the nanoemulsion currently described in the optional step S06. Alternatively, these agents can be omitted, as long as the nanoelement including the CSSC core can be retained on the skin surface or delivered transdermally in an amount effective enough for the effect sought.
[0380] Therefore, the above steps can be modified, omitted (e.g., S02', S05, S06 or S07), and additional steps may be included. For example, the skin composition may contain any additive commonly used in cosmetics or pharmaceutical compositions, such as moisturizers, emollients, moisturizers, UV-protectants, thickeners, preservatives, antioxidants, bactericides, fungicides, chelating agents, vitamins and spices, or any other substances suitable for its preparation in a form suitable for its application on the skin. The properties and concentrations of each such conventional compound suitable for such a composition are known to those skilled in the art and do not need to be further described here. Additives may be added in the method steps already described or added by new steps. In addition, the composition may be further processed (e.g., sterilized, filtered, irradiated, etc.) according to health regulations to make it suitable for skin use, particularly on human skin.
[0381] Advantageously, regardless of the steps involved and the compositions prepared, the present methods do not seek to chemically modify the ingredients thereof, such as might be required to join them together. The absence of such modifications in the compositions of the present invention is expected to prevent the formation of large particles that are unable to pass the skin barrier, and / or is believed to prevent an undesirable reduction in the biological activity that these ingredients (assuming they successfully penetrate the skin) might provide in their native (unmodified) form.
[0382] Route and form of administration
[0383] The compositions of the present invention can be delivered by any route suitable for its intended use, depending on the object, subject and / or condition to be treated. Such modes of application or application to the surface are known. Considering the description of living subjects, it is known that for effects substantially limited to the site of application, local routes (e.g., skin, oral cavity, rectum, etc.) are used, while for systemic effects, systemic routes (i.e., enteral or parenteral, such as injection, oral, sublingual, inhalation, etc.) can be selected according to the intended use of the composition.
[0384] The main use of core-shell nanoelements according to the present teachings is for use in skin compositions for application to the skin, allowing transdermal delivery of CSSC (and any other active agents present in the composition) and their activity on the skin surface, within the skin layers, below the skin layers and / or even systemically. Advantageously, transdermal delivery generally occurs over a larger skin area than would be permitted by topical (e.g., subcutaneous) injection of the same product. Thus, the effect of the CSSC (or other active agent) so delivered is expected to be wider relative to the area being treated, generally providing a more uniform effect over a larger surface.
[0385] The composition can be applied topically to the skin, where it can be used as a cosmetic composition (e.g., to improve appearance, as an anti-aging treatment, skin protection treatment, skin filling treatment, skin smoothing treatment, etc.) or as a pharmaceutical composition (e.g., to alleviate or treat a condition).
[0386] Although for simplicity, the effects of the compositions of the present invention when considered cosmetics are referred to as "anti-aging", for delaying, reducing or preventing skin aging, this should not be construed as limiting, since processes similar to those that lead to natural, time-dependent skin aging are encountered in other contexts, such as degenerative conditions or benign and malignant neoplasms, to name just a few. Thus, although for the sake of brevity, the present invention details its cosmetic effects and improving skin appearance (or delaying and / or reducing deterioration in appearance), the compositions and preparation methods disclosed herein may have a broader beneficial impact on skin health, at least in the field of skin treatment where one or more structural skin proteins that can be restored by the compositions of the present invention are pathologically reduced.
[0387] Therefore, the use of a composition for skin application comprising the core-shell nanoelements of the present invention should be broadly understood as the use of a cosmetic or pharmaceutical composition to achieve any desired cosmetic or pharmaceutical improvement of the skin.
[0388] Usually, skin composition can be mixed with emulsion, foam, gel, lotion or ointment, and its preparation is known to the technician, and does not need to be described in detail at this.Composition can be applied to the skin by any known method, for example, can be applied once or repeatedly on the skin with any desired frequency, to realize the beauty or pharmaceutical activity sought and have no side effect.Skin composition of the present invention can also use any suitable dressing, as epidermal or transdermal patch, pad, gauze etc. send, when wishing to slowly release the activating agent that is incorporated in the nano element of the present invention, this approach is favourable, described composition is loaded in the dressing, for example is deposited in the reservoir of patch or impregnates cloth pad.Epidermal patch or skin patch are the medicated adhesive patches that are suitable for activating agent to be delivered to the skin, and transdermal patch sends activating agent through the skin and enters in the blood.
[0389] The composition of the present invention may also be an agricultural chemical composition, which is usually applied to a suitable target surface, such as soil or water where plants grow or pests exist, and the surfaces of plants and pests in the form of a solution, emulsion, powder, granule, pellet or aerosol, by spreading, dispersing or spraying the agricultural chemical composition on the surface to be treated.
[0390] When the composition is an industrial composition, it may be in the form of a paint, paste, varnish, lacquer, spray or powder for application to the surface of an inert object by spreading, spraying or dispersing the industrial composition on the inert surface.
[0391] use
[0392] By delivering an effective amount of the core-shell nanoelements of the present invention comprising CSSC and optionally an active agent to a target surface, cosmetic, therapeutic, agrochemical or industrial uses can be achieved, depending on the effect achieved.
[0393] Once the core-shell composition of the present invention is applied to the skin to be treated, the cosmetic effects of improving the skin appearance that can be achieved include anti-collagen or glycosaminoglycan degradation, promotion of new synthesis of collagen, elastin or glycosaminoglycans, anti-signs of skin aging, anti-wrinkles and fine lines, anti-skin dryness, anti-skin sagging, anti-skin thinning, anti-dull skin, anti-uneven skin pigmentation, anti-lack of skin elasticity and / or tension, and skin bleaching or tanning.
[0394] Once the core-shell composition of the present invention is applied to the skin to be treated therewith, the pharmaceutical effects that can be achieved include improving the appearance and / or health of the skin by treating chronic skin disorders, skin damage, restoring skin integrity, promoting the healing of wounds or surgical incisions, promoting skin grafts, alleviating or treating local skin inflammation (e.g., acne), skin irritation, skin infection, rash, skin pain, skin burns, skin swelling, skin allergies, and promoting or inhibiting hair growth or treating dandruff.
[0395] Alternatively, the non-cosmetic effect of the compositions of the invention is not directed towards the treatment of the skin itself, but towards the protection of the skin to which they are applied from external factors.
[0396] The core-shell skin composition of the present invention can be further used to deliver an active agent (CSSC miscible and present in the core, or water soluble and present as a second shell) to exert its pharmaceutical effect transdermally on organs other than the skin by delaying, alleviating, preventing or treating a transdermally treatable condition. Additional pharmaceutical effects that can be achieved by the core-shell composition of the present invention once delivered through the skin to the blood or the organ treated therewith include all activities known or to be discovered for such an active agent when delivered through the skin. These effects can be ADHD-relieving effects, amyotrophic lateral sclerosis (ALS), Alzheimer's disease, Huntington's disease or Parkinson's disease relieving effects (or similar effects for other neurodegenerative conditions), analgesic effects, anti-addiction withdrawal effects, anti-anginal effects, antidepressant effects, antiemetic effects, antipsychotic effects, anti-epileptic seizure effects, anticonvulsant effects, blood pressure regulating effects, contraceptive effects, glaucoma relief effects, hormone replacement effects, thyroid regulating effects, and protection from neurotoxic drugs.
[0397] Agricultural chemical and / or industrial effects can also be achieved by applying the core-shell composition of the present invention to the surface of an inert object, plant or pest, or to soil or water where plants grow or pests are present. Such agricultural chemical and / or industrial products can be used as acaricides, algaecides, insect repellents, moth repellents, avicides, bactericides, chemosterilants, fertilizers, fungicides, herbicides, insecticides including ovicides, anthelmintics, insect pheromones, molluscicides, nematicides, nitrification inhibitors, insecticides, pest repellents, plant growth promoters, rodenticides, soil fertilizers, termiticides, virucides and plant wound protectants.
[0398] Example
[0399] Material
[0400] The materials used in the following examples are listed in Table 1 below. The reported properties were retrieved from product data sheets provided by the respective suppliers or estimated by standard methods. Unless otherwise stated, all materials were purchased at the highest obtainable purity level. N / A indicates that specific information is not available.
[0401] Table 1
[0402] equipment
[0403] Oven: DFO-240 from MRC, Israel
[0404] Thermal rheometer: Haake Mars III from Thermo Scientific (Germany), with C20 / 1° spindle, 0.052 mm gap, and 10 sec -1 The shear rate
[0405] Ultrasound machine: VCX 750 from Sonics & Materials, USA
[0406] Dynamic light scattering and zeta potential measurements: MalvernZetasizer Nano ZS from Malvern Instruments Ltd., UK.
[0407] Conductivity meter: Eutech CON 700 from Thermo Fisher Scientific, USA
[0408] CryoTEM: Talos 200C from Thermo Fisher Scientific, USA, with Lacey grid
[0409] Fluorescence microscope: DP73 digital camera BX60 microscope from Olympus, Japan
[0410] Example 1: Reducing the viscosity of CSSC
[0411] In this study, the viscosity of CSSC, a polycaprolactone with a molecular weight of 14 kDa (PCL-14, referred to as PCL in this example), and its mixtures with nonvolatile liquids or fatty amines used as plasticizers were measured at different weight / weight ratios of polycaprolactone to plasticizer.
[0412] In a first series of experiments, viscosity was measured on blends of materials that form a homogeneous substance suitable for nanosizing by the method of the present invention. PCL and a non-volatile liquid or a fatty amine were mixed in glass vials in different weight / weight ratios and the sealed vials were placed in an oven preheated to 80°C, with PCL: non-volatile liquid tested in ratios of 1:1 and 1:2.33 and PCL: fatty amine tested in ratios of 1:0.1, 1:0.33, 1:0.5 and 1:1. After incubation for 1 hour under heating, the contents of the vial were mixed by hand for about 30 seconds until a clear solution was obtained. The samples were allowed to cool overnight (i.e., at least 12 hours) at room temperature to cure. None of the plasticizers so tested showed leaching from the cured polymer, indicating that they can be used in even higher ratios relative to PCL.
[0413] The solid samples were then transferred to a rheometer where their respective viscosities were measured at a ramp temperature of 10° C. / min as a function of temperature between room temperature and 70° C. The viscosities (or second viscosities) of the samples measured at 50° C. and 70° C. are summarized in Table 2A, including in the first row the first viscosity of a reference sample prepared from unplasticized PCL alone under the same conditions.
[0414] Table 2A
[0415] As can be seen from the table above, at temperatures of 50°C and 70°C, all materials tested as plasticizers (either non-volatile liquids for this purpose or fatty amines which themselves contribute to the effect) reduce the viscosity of PCL to less than 10% at the weight / weight ratios tested. 4 mPa·s. Different weight ratios, such as lower relative amounts of plasticizer or fatty amine to CSSC (e.g., 1:0.1 oleylamine), may be less effective, however, suitable ratios and agents capable of plasticizing a material can be readily determined by routine experimentation, as demonstrated herein.
[0416] Based on the above results or similar experiments, the PCL:plasticizer ratio was selected to provide 1×10 4 A dynamic viscosity of mPa·s or less (although higher viscosities are permitted) is useful for preparing core-shell nanoparticles to be used in topical compositions, as detailed in the Examples below.
[0417] In a second series of experiments, viscosity was measured at the other end of the process, on core-shell nanoelements isolated from compositions prepared as detailed in the examples below. Nanoparticles containing only PCL-14 were used as a reference and were mixed with nanoparticles containing either 1 wt % or 5 wt % of a fatty amine blended with PCL. O 020 Special (GenA2 in the table below) nanoparticles and 30 wt% PCL-14, 30 wt% GenA2 and additionally 40 wt% non-volatile liquid The viscosity was measured as a function of temperature (in °C) as before, but up to 85 °C, and the results in mPa·s are listed in descending order of temperature in Table 2B.
[0418] Table 2B
[0419] As can be seen from the table above, although the presence of even trace amounts of fatty amine (e.g., 1 wt. % GenA2) can be detected by the plasticizing effect of the fatty amine on CSSC at temperatures between 30°C and 85°C, at lower temperatures, detection of plasticizing effects requires a higher ratio of plasticizing fatty amine to CSSC. Interestingly, even small amounts of plasticizing fatty amine (e.g., 5 wt. % GenA2) provide a viscosity of less than 1×10 7 mPa·s core-shell nanoelement.
[0420] Example 2: Preparation of core-shell nanodispersions
[0421] 2g PCL-14, 2g fatty amine dodecyl dimethyl tertiary amine (DMDA) and 6g non-volatile liquid B (used as a dedicated plasticizer) was placed in a 20 ml glass vial. The vial contents were sonicated at about 70°C for 2 minutes until a clear CSSC / fatty amine premix containing a non-volatile liquid was obtained.
[0422] In a separate 20 ml glass vial, 8 g of glycerol was heated to about 70° C. using a sonicator, followed by the addition of 2 g of the hot premix prepared above, and the composition was sonicated for 5 minutes while maintained at 70° C. to obtain a nanoemulsion. The nanoemulsion was then allowed to cool to room temperature until a nanodispersion containing core-shell nanoparticles was obtained.
[0423] This nanodispersion (ND1) is reported in Table 3, which provides additional nanodispersions prepared according to similar methods, each containing different components in different amounts and prepared under different conditions specified in the table. Unless otherwise stated, the values reported herein and in the following tables describing the compositions and their preparation correspond to the concentration of each component expressed as a weight percentage (wt%) of the total weight of the nanodispersion, except for the values in the CSSC / fatty amine premix section, which correspond to the weight percentage of each component in a specific premix that may further include any other CSSC miscible ingredients (e.g., non-volatile liquids). Water refers to double distilled water.
[0424] The size of the nanoparticles prepared according to this example or similar following examples was measured by dynamic light scattering (DLS) on a sample of the composition diluted 1:100 in water, measuring the average diameter / number (D N 50) and the polydispersity index (PDI) are also listed in the table below. When measured, the number of particles below the maximum hydrodynamic diameter of 10% and 90% are also listed in the relevant tables (D N 10 and D N 90).
[0425] Table 3
[0426] As can be seen in Table 3, the present method is suitable for preparing nanosuspensions of core-shell nanoelements containing CSSC and fatty amines, the nanoelements having a D of no more than 200 nm. N 50, and for some of the nanosuspensions reported above, this value is even below 100 nm. The PDI of the core-shell nanoelement population is at most about 0.5.
[0427] Figure 2 Representative results of particle size distribution in ND3 samples are shown in , showing the percentage (per number) of PCL / DMDA core-shell nanoparticles with hydrodynamic diameters of 10-1,000 nm.
[0428] Example 3: Preparation of positively charged core-shell nanoparticles by acid doping
[0429] 8g of double distilled water is placed in a 20ml glass vial. Add 2g of the nanodispersion ND1 obtained in Example 2, shake the contents of the vial by hand for about 10 seconds, until a uniform mixture (called charged ND1 or cND1) is obtained. The zeta potential of the mixture is measured by Malvern Zetasizer Nano ZS, and it is found to be -14.7mV. Unless otherwise stated, all measurements (e.g., zeta potential and particle size distribution) performed with the instrument are performed on samples diluted in double distilled water at 1:100. All pH measurements reported in the present embodiment and the following examples are performed at least using pH test strips suitable for the relevant pH range, and are confirmed by using a suitable pH meter in some cases.
[0430] Then 1 drop of acetic acid was added to the mixture to obtain a pH of 5.5, and the vial was shaken by hand for about 10 seconds until a nanodispersion containing positively charged core-shell PCL / DMDA nanoparticles, referred to as cND1', was obtained. The zeta potential of the nanoparticles in the acid-doped nanodispersion was measured and confirmed to be positive with a charge of +52.4 mV.
[0431] The hydrodynamic diameter of the nanoparticles obtained in the acid-doped cND1′ was determined by DLS, and it was found that the D N The hydrodynamic diameters of the nanoparticles of 50 and ND1 are similar, as shown in Table 3.
[0432] Example 4: Preparation of positively charged core-shell nanoparticles in the absence of acid
[0433] 9.9 g of double distilled water was placed in a 20 ml glass vial. 0.1 g of the nanodispersion ND3 obtained in Example 2 was added, and the contents of the vial were shaken by hand for 10 seconds until a uniform mixture was obtained, referred to as cND3. The zeta potential of the mixture was measured and was +43 mV. The particle size distribution of the nanoparticles thus obtained was measured by DLS, and it was found that the D N 50 D of ND3-like nanoparticles N 50, as shown in Table 3.
[0434] Example 5: Preparation of positively charged core-shell nanoparticles by acid-doping of diluted samples
[0435] 9 g of double distilled water was placed in a 20 ml glass vial. 1 g of the nanodispersion cND3 obtained in Example 4 was added and the contents of the vial were shaken by hand for 10 seconds until a uniform mixture was obtained, referred to as cND3'. The zeta potential of the mixture was measured and the result was -9.9 mV. The mixture differed from the mixture described in Example 4 in that 10 times less ND3 was contained in the same total weight of aqueous carrier. The 10-fold diluted nanodispersion prepared in the present case showed a relatively low charge, with a charge of -9.9 mV, compared to the charge of +43 mV in the previous case.
[0436] Then 1 drop of acetic acid was added to the relatively diluted mixture to obtain a pH of 5.5, and the vial was shaken by hand for about 10 seconds until an acid-doped nanodispersion containing positively charged core-shell PCL / DMDA nanoparticles, referred to as cND3', was obtained. The zeta potential of the acid-doped nanodispersion cND3' was measured and confirmed to be positive, with a charge of +7.8 mV. The hydrodynamic diameter of the resulting nanoparticles was determined and found to be D N 50 is similar to the hydrodynamic diameter of ND3 nanoparticles, as shown in Table 3.
[0437] Example 6: Preparation of core-shell nanoparticles in an acidic polar support
[0438] 2g PCL-14, 2g DMDA and 6g B was placed in a 20 ml glass vial. The vial contents were sonicated at about 70°C for 2 minutes until a clear CSSC / fatty amine premix was obtained.
[0439] In another 20 ml glass bottle, 8 g of glycerol and 1 g of 3 wt% HCl solution were mixed to obtain a solution of pH 3. 1 g of the hot CSSC / fatty amine premix prepared above was added to the acidic liquid carrier and the contents of the vial were sonicated for 30 seconds to obtain a nanoemulsion. The nanoemulsion was allowed to cool to room temperature until a nanodispersion was obtained.
[0440] The zeta potential of the nanodispersion was measured and found to be +72.8 mV, this charge being the result of dilution of the sample in water.Thus, instead of the two-step process as described previously, positively charged nanoparticles are readily obtained after sonication in an acidic polar carrier.
[0441] The nanodispersion thus obtained (ND7) is listed in Table 4A. Other nanodispersions were prepared according to similar methods, all of which could be charged in the presence of water, each containing different components in different amounts and prepared under different conditions, as specified in Tables 4A-4C, and the parameters measured after diluting samples of some nanodispersions to 1:100 in deionized water, the values obtained are also given in the table below. The pH values of nanodispersions ND15 and ND16 were obtained by adding about one drop of acetic acid to their respective aqueous phases.
[0442] Table 4A
[0443] In addition to measuring the zeta potential of the nanodispersions, the effect of the acid in the polar liquid carrier was monitored by measuring the change in pH during the preparation of the nanodispersions. For ND7, when the acidic glycerol solution at pH 3 was mixed with the CSSC / fatty amine mixture, the pH increased to 6, indicating that the hydrogen ions of the liquid carrier were eliminated, which is believed to have reacted with the amine groups of the fatty amine shell. The pH remained at 6 after cooling and increased to 6.5 after dilution with water, indicating that the amine groups remained protonated, as confirmed by the positive zeta potential.
[0444] Other nanodispersions prepared using various CSSCs of synthetic and natural origin are summarized in Table 4B. The aqueous phase of the nanodispersions reported in the table was acidified (about one drop of acetic acid was added for ND17-ND23 and a specific amount of acetic acid was added for ND24 and ND25).
[0445] Table 4B
[0446] The core-shell nanoelements of ND24 and ND25 were isolated and subjected to thermorheological analysis as reported in Table 2B.
[0447] Nanodispersions prepared using non-biodegradable thermoplastic polymers are summarized in Table 4C. The pH values of the nanodispersions reported in the table were obtained by adding approximately one drop of acetic acid to their aqueous phase.
[0448] Table 4C
[0449] Example 7: Preparation of core-shell nanoparticles containing an acid in the core
[0450] In the following examples, the pH of the nanodispersion was adjusted from within the core of the core-shell, as opposed to forming the nanoemulsion by combining the core-shell with an acidified polar carrier as previously described (eg, in Example 6).
[0451] 2g PCL-14, 2g O 020Special and 6g B was placed in a 20 ml glass vial. 0.01 g of anhydrous acetic acid was added and the vial contents were sonicated at about 70°C for 2 minutes until a clear CSSC / fatty amine / acid premix was obtained.
[0452] In a separate 20 ml glass vial, 9 g of water was placed, 1 g of the hot CSSC / fatty amine / acid premix prepared above was added and the contents of the vial were sonicated at about 80° C. for 1 minute to obtain a nanoemulsion. The nanoemulsion was allowed to cool to room temperature until a nanodispersion was obtained.
[0453] The pH was measured and found to be 5. The zeta potential was measured in a sample of the nanodispersion diluted 1:100 with deionized water and found to be +54.1 mV, indicating that the nanoparticles were positively charged, presumably due to leaching of acetic acid from the core of the nanoparticles into the polar support, thereby protonating the amine head in the shell of the nanoparticles. N The measurements of 50 and PDI were also the same, 35.3 nm and 0.198 nm, respectively.
[0454] Example 8: Preparation of core-shell nanoparticles containing CSSC miscible active agents in the core
[0455] 2g PCL-14 and 0.1g benzoyl peroxide as CSSC miscible active agent were placed in a 20ml glass vial. 2g O 020 Special and 5.9g B, and sonicate the vial contents at about 70° C. for 2 minutes until a clear CSSC / fatty amine / active agent premix is obtained.
[0456] In a separate 20 ml glass vial, 9 g of water was placed and acidified to pH 4 by adding a drop of acetic acid. 1 g of the hot CSSC / fatty amine / active agent premix prepared above was added to the acidic liquid carrier and the contents of the vial were sonicated at about 80° C. for 1 minute to obtain a nanoemulsion. The nanoemulsion was allowed to cool to room temperature until a nanodispersion was obtained.
[0457] The nanodispersion thus obtained (ND29) is reported in Table 5. Other nanodispersions were prepared according to similar methods, all of which could be charged in the presence of water, each containing a different CSSC miscibility and water-insoluble active agent (pharmaceutical or pesticide) as specified in the table.
[0458] Zeta potential, D N 50 and PDI, and the values are shown in Table 5.
[0459] Table 5
[0460] It can be seen that ND35 and ND36 contain no dedicated non-volatile liquid. It is believed that the CSSC miscible active agents neem oil and castor oil are contained in ND35 and ND36 respectively in a rather high amount of three times the weight of CSSC, additionally for plasticizing the premix containing CSSC.
[0461] Example 9: Preparation of core-shell nanoparticles coated with water-soluble active agents
[0462] 1 g of collagen peptide powder and 2.1 g of water were placed in a 20 ml glass vial and mixed at room temperature until completely dissolved.
[0463] In a separate 20 ml vial, 6.9 g of the core-shell nanodispersion ND11 obtained in Example 6 was placed and a collagen solution of water-soluble active agent molecules for forming a second shell was added. The contents of the vial were shaken by hand for 10 seconds until a uniform mixture was obtained. The composition of the collagen-coated nanoelement thus obtained (collagen-ND11) is reported in Table 6, which also provides the composition of the nanoelement coated with LMW hyaluronic acid (LMW HA) similarly prepared (LMW HA-ND11). A reference composition comprising uncoated nanoelement (uncoated-cND11) was also prepared, which contained 3.1 g of water without any carrier-soluble active agent.
[0464] Based on ND6 and ND14, three additional nanodispersions (referred to as LMW HA-ND6 and LMW HA-ND14, respectively) were prepared, to which LMW HA was added to reach the concentrations reported in Table 6. The LMW HA-ND6 and LMW HA-ND14 samples were prepared in which the LMW HA solution was mixed with the ND6 or ND14 composition by ultrasound. For comparison, another sample of LMW HA-ND6 with the same component concentrations was prepared by manually mixing the LMW HA solution and the ND6 composition.
[0465] These compositions are also listed in Table 6, where the different components and amounts are listed. The values reported in the table correspond to the concentration of each component expressed in wt.% of the total weight of the nanodispersion. N 50 and zeta potential values are also shown in Table 6.
[0466] Table 6
[0467] From the change in zeta potential, it can be seen that the addition of active agent to the previously prepared core-shell nanoparticles reduces the expected charge on the newly formed outer surface of the nanoparticles, supporting modification at this interface with the liquid carrier, thus indicating the formation of a second shell composed of active agent. For example, although the nanodispersion of uncoated nanoelement ND14 has a zeta potential of +56.0 mV (according to Table 4A of Example 6), it can be seen that coating these nanoelement with LMW HA reduces their zeta potential to +34.9 mV.
[0468] For reference, the zeta potential of 0.1 g of collagen peptide dispersed in 9.9 g of distilled water was found to be -7.7 mV, indicating that there was a satisfactory Δζ between the zeta potential of the collagen used to coat the nanoparticles and the zeta potential of the nanoparticles thus coated, which allowed the collagen to attach to the surface of the nanoparticles that previously included only the first shell. The zeta potential of a similarly prepared LMW HA aqueous solution was measured and found to be -17 mV, resulting in an even higher Δζ compared to the zeta potential observed in the preparation of the collagen-coated nanoparticle composition.
[0469] The speed with which the carrier soluble active agent forming the second shell mixes with the "uncoated" core-shell having only a first shell of positively chargeable amines is believed to contribute to the form of core-multishell nanoparticles that can be obtained.
[0470] Fig. 5A CryoTEM analysis of a first sample of the composition LMW HA-ND6 is shown, which was obtained by high shear mixing (i.e., ultrasonication) of LMW HA with core-shell nanoelements of ND6. In the figure, a core 410 including PCL, as shown by black spheres, has a second shell 430 composed of LMW HA. Fig. 5A As seen in FIG. 1 , the second shell may comprise multiple layers of HA, one layer formed upon another.
[0471] Figure 5Bis another image of a second sample LMW HA-ND6 composition taken by CryoTEM, in which LMW HA was manually mixed with the core-shell nanoelement of ND6. In this image, two dark PCL cores 410 can be seen surrounded by a common shell 430', which is also composed of a LMW HA layer, forming a larger nanoelement. It is believed that manual mixing may be too slow / too low energy, and the shell of the active agent formed on the core aggregates and fuses into such larger particles. Therefore, it is suggested that high-energy mixing (e.g., high shear) is more favorable than low-energy mixing methods for forming a second shell surrounding a single core, and this core-multi-shell nanoelement thus has a particle size distribution comparable to the size of a single core-shell, and is more easily maintained within a size range suitable for transdermal delivery.
[0472] Similarly, the ND12 nanoparticles prepared in Example 6 were coated with various water-soluble active agents, and uncoated ND12 compositions were also prepared and used as references. The ND12-based compositions, including their respective components and their concentrations, are summarized in Table 7, and the concentrations of each component are provided in wt% of the total weight of the nanodispersion. The D N 50 and zeta potential values are also shown in Table 7.
[0473] Table 7
[0474] Example 10: Conductivity Measurement
[0475] To further demonstrate that the water-soluble active agent is adsorbed onto the surface of the core-shell nanoparticles, the conductivity of various ND12-based composition samples was measured using a conductivity meter and is expressed in microSiemens (μS) in Table 8.
[0476] The rationale for the study relies on the expectation that if two substances are mixed, each independently having a conductivity as an electrolyte in a specific medium, the conductivity of the mixture is the sum of the relative contributions of the substances only if the substances remain separated. In other words, if the conductivity of a mixture of substances is not the sum of the individual conductivities of its components, it can be assumed that the substances interact with each other.
[0477] In the context of the present invention, it is assumed that molecules of a water-soluble active agent are able to attach to the core-shell nanoparticles so that when core-shell nanoparticles having a conductivity A at a given concentration in a medium are mixed with an active agent having a conductivity B at a given concentration in essentially the same medium, the conductivity of the mixture should be lower than the combined conductivity A+B.
[0478] Samples of various water-soluble active agents were prepared in a carrier that was a liquid mixture substantially similar to the liquid mixture used to prepare the ND12 nanoparticles and their coated forms. The conductivity of the active agent alone, the core-shell nanoparticles before coating with the second shell active agent, and the active agent coated nanoparticles were measured and all are reported in Table 8.
[0479] Table 8
[0480] As can be seen from the table above, the conductivity of the uncoated nanoparticles containing only a first shell formed from the hydrophilic portion of the fatty amine is substantially similar as expected for similar samples of core-shell nanoparticles in similar carriers without any specific externally applied active agent.
[0481] In contrast, the conductivity of each active agent alone or the core-shell nanoparticles coated therewith depends on the active agent under consideration (e.g., LMW HA, vitamin C, collagen, and elastin). It is noteworthy that the conductivity of all active agent coated nanoparticle samples showed a conductivity lower than the sum of the following conductivities: the conductivity of the core-shell nanoparticles in the carrier (A) and the conductivity of the active agent in substantially the same carrier (B). These results support that the method of the present invention is capable of preparing core-shell nanoparticles having a core made of CSSC material, a first shell made of fatty amine, and a second shell made of a water-soluble active agent and interacting with the first shell.
[0482] Example 11: Patch Test Protocol for Skin Irritation Analysis
[0483] The irritation effects, if any, of topical compositions according to the present teachings, such as those prepared in Examples 2-9, can be tested by applying the formulation to be tested via a patch to the skin of human volunteers.
[0484] Each volunteer placed a small plastic cavity (e.g., 0.64 cm 2 ) is applied with a predetermined volume of the composition to be tested (e.g. 0.02 ml) in a filter screen, wherein the filter screen is in contact with the skin of the volunteer in a predetermined body area (e.g. back). The patch is attached to the skin area by a hypoallergenic nonwoven tape, and the test formulation is kept in contact with the skin for 48 hours.
[0485] The appearance of the treated area is assessed before application of the topical composition and 30 minutes after patch removal. An empty patch lacking any composition can be used as a negative control.
[0486] Skin reactions (erythema, dryness, and edema) were scored throughout the test according to the following predefined scoring scale:
[0487] erythema
[0488] 0 = no evidence of erythema; 0.5 = minimal or questionable erythema; 1 = mild redness, blotchy and diffuse; 2 = moderate, uniform redness; 3 = strong, uniform redness; 4 = intense redness
[0489] Dryness (flaking)
[0490] 0 = no signs of flaking; 0.5 = dry and not flaking; appears smooth and taut; 1 = fine / slight flaking; 2 = moderate flaking; 3 = severe flaking with large patches
[0491] Edema
[0492] - = no edema; + = edema present
[0493] The results obtained with any composition tested were compared with those obtained on a control area (natural skin surface under a blank sheet), and the compositions were classified as: non-irritating, very slightly irritating, moderately irritating, irritating, or severely irritating, depending on their combined effects on the expected skin reactions described above.
[0494] Example 12: Penetration of the composition into biological tissues
[0495] The distribution of nanoelements of the compositions of the invention in various skin layers was tested ex vivo by applying core-shell and core-multi-shell (including a second active agent forming the shell) nanoelements to the skin of pig ears, the core of the tested compositions including a fluorescent dye (Nile Red) to allow histological monitoring.
[0496] Tested composition :
[0497] The following test and control compositions were prepared and used as shown in Table 9.
[0498] Table 9 Tested composition Test repetitions (1) Saline without fluorescent labeling 2 (2) ND14 modified to contain Nile Red in the PCL core 6 (3) LMW HA-ND14 modified to contain Nile Red in the PCL core 6
[0499] As described in Example 6, during the preparation of the CSSC / fatty amine premix, test compositions (2) and (3) were prepared by adding 2 mg of Nile Red fluorescent marker, and all test compositions were stored in sealed containers at room temperature until use.
[0500] Test steps :
[0501] The compositions were tested on three freshly harvested pig ears collected on the same day and kept fresh and cooled until use. The ears were washed with excess saline solution and wiped dry. They were then fixed during the study by sticking them inside out to a glass surface facing down. Each ear was marked on its outside with 6 circles of approximately 1 cm in diameter.
[0502] Each sample was applied to the skin near the center of the marked circle at 25 microliters, with each composition tested being applied in two or more separate circles. The ears with the applied test samples were then placed in an oven and incubated at 32°C for a period of 20 hours to simulate the body temperature of a pig.
[0503] After this incubation, the ears were punched with a metal punch of about 5 mm in diameter to extract a tissue sample of each circle on which a different composition was applied. Each punched skin sample was placed in a 50 ml plastic cup and immediately topped with 5 ml of a 4% paraformaldehyde solution, used as a fixative to preserve the tissue sample and reduce leaching of the dye. The skin samples were kept in the paraformaldehyde solution at 4° C. for at least 48 hours for complete fixation.
[0504] Tissue collection, fixation, and slide preparation :
[0505] The tissue samples were trimmed, each tissue sample was cut into two halves longitudinally, and each half cylinder was placed in an embedding cassette. The first half of each sample was processed for paraffin embedding by immersing each sample in various reagents (formaldehyde, then water, then various fractions of ethanol, and finally xylene) at a temperature of 37-45°C for 2-10 minutes to remove traces of paraformaldehyde and any other contaminants. Subsequently, the sample was immersed in paraffin 3 times at a temperature of 65°C for 5-10 minutes each time. The second half of each sample was processed in an optimal cutting temperature (OCT) block according to standard procedures.
[0506] Sections of each treated sample were prepared using a cryostat and placed on glass slides, with the thickness of paraffin sections and OCT sections being 4 μm and 10 μm, respectively.
[0507] Analysis and Results :
[0508] The presence and intensity of the markers in the above tissue sections were evaluated by experts using a fluorescence microscope at objective magnifications of X10 and X20.
[0509] The sample group treated with the fluorescently labeled core-shell nanoelement-containing composition ND14 showed positive cells, i.e., labeled with the fluorescent marker, in four of the six tissue samples tested. Fig. 6A , a histological picture of a cross section of one of the tissue samples, which was processed by paraffin embedding and photographed by a microscope camera at a magnification of x10, is presented. Fig. 6A In FIG. 6 , penetration of the composition into the epidermis 62 is shown as bright areas, indicating the presence of the fluorescent marker in this skin layer.
[0510] The sample group treated with the fluorescently labeled composition LMW HA-ND14 containing core-multishell nanoelements including an HA shell also showed positive cells in four of the six tested samples. Figure 6B An exemplary image taken at x10 magnification of a paraffin-embedded sample is provided, showing fluorescent labeling of the entire epidermis 62, as well as labeling of a portion of the superficial dermis 64.
[0511] It can be seen that with the composition ND14 (see Fig. 6A ) compared to the composition LMW HA-ND14 penetrated deeper into the skin (see Figure 6B This is expected, considering that the positive charge of composition ND14, which is higher than the positive charge of composition LMW HA-ND14 masked by the HA layer (as shown by the charges listed in Tables 4A and 6, respectively), would retard penetration into the negatively charged skin.
[0512] Figure 6C The images shown in the figure correspond to the Fig. 6A The sample treated with the fluorescently labeled composition ND14 shown, however, was processed in the OCT module and the image was taken at a magnification of x20. In this cross section, it can be seen that the core-shell nanoelement also shows transcellular penetration in addition to the epidermis 62 penetration. The fluorescent label is visible in the intracellular matrix of the keratinocyte 66, where the black circular area is the nucleus of the keratinocyte (not penetrated by the label).
[0513] Fig.6D A sample image of a cross section from a control group treated with saline and embedded in paraffin is shown, which shows very low fluorescence in the skin layer, which is believed to be due to autofluorescence expressed by the skin tissue itself. Fig. 6A , 6B This phenomenon is indicated by lower fluorescence levels compared to 10C or 6C.
[0514] It is important to emphasize that these findings can be clearly attributed to the behavior of the nanoelements of the tested compositions and not to the independent penetration of the fluorescent Nile Red marker. This was established in control experiments in which samples contained: i) the marker in water; or ii) the marker in a solution containing water and ND14 surfactant; respectively applied to the marked circles on the skin of pig ears. The tested compositions were studied as described above. For any control composition lacking nanoelements, no penetration of the fluorescent marker was observed, indicating that the marker itself, or even surrounded by the surfactant, could not penetrate into the skin. Thus, this ex vivo experiment demonstrates, among other factors, that a) the skin compositions of the present invention and the core-shell nanoelements contained therein can act within the skin layers above and below the skin to which they are applied and are therefore suitable for topical transdermal use; b) the skin compositions of the present invention are capable of transdermal penetration of CSSC materials having a molecular weight significantly greater than the generally recognized size limit of about 0.5 kDa, the CSSC used in the tested ND14-related compositions being a polycaprolactone polymer having an average MW of about 14 kDa; and c) the skin compositions of the present invention are also capable of transdermal delivery of active agents having a molecular weight that is expected to prevent skin penetration, the active agent used in the tested ND14-related compositions being a LMW hyaluronic acid having an average MW of about 3 kDa.
[0515] Example 13: Effect of the composition on facial skin appearance
[0516] The cosmetic effects of topical compositions according to the present teachings can be tested on the skin of healthy human volunteers by applying the formulation to be tested to the facial skin. The volunteers have no dermatological problems, irritated skin, blemishes or such marks that might compromise the study at the test site. The samples may include:
[0517] a) a skin composition comprising a nanodispersion of core-shell nanoparticles at a predetermined concentration in a polar carrier, which composition may have any desired charge and / or viscosity (e.g., it may be prepared according to Examples 2-7);
[0518] b) a skin composition comprising a nanodispersion of core-shell nanoparticles at a predetermined concentration, which may further contain a desired cosmetic active agent in the core (e.g., which may be prepared according to Example 8);
[0519] c) a skin composition comprising a nanodispersion of core-multi-shell nanoparticles at a predetermined concentration, which may further contain a desired cosmetic carrier-soluble active agent in the second shell (e.g., which may be prepared according to Example 9);
[0520] d) a control skin composition comprising a nanodispersion of core nanoparticles lacking any shell at a predetermined concentration in a polar carrier, the reference core corresponding to the core of the sample being tested (e.g., composition 2.2 in Example 2 of co-owned WO 2022 / 243899, wherein the core consists of PCL-14 and B is made; and
[0521] e) A placebo composition comprising any polar carrier of the test sample but without the core-shell nanoparticles.
[0522] The clinical study was conducted in a double-blind manner, with at least ten volunteers randomly assigned to each of the studies (i.e., half of each composition containing core-shell nanoparticles and half of each placebo composition), with the concentration of nanoparticles being the same in the non-placebo group. All groups applied 1 ml of their respective composition twice a day (morning and evening) by gently dabbing on the facial skin.
[0523] Facial skin parameters
[0524] Wrinkle Count:
[0525] The effects of various compositions on facial skin wrinkles can be determined using Canlfield's VISIA system (Canfield Scientific, USA), which consists of a VISIA imaging chamber and VISIA software for capturing and storing facial images using standard illumination, cross-polarized flash, and UV flash.
[0526] Measurements were taken from the target area before the first application (baseline), after one month (T1), two months (T2) and three months (T3) of twice-daily application. The results at T1, T2 and T3 time points for each volunteer were compared with the baseline values obtained initially and the results of the placebo group at the same time points.
[0527] The software automatically isolates or "masks" specific areas of the face captured in the image, and then performs an extensive analysis of these areas to evaluate skin features, such as wrinkles. The data provided by the VISIA system is displayed as "Feature Counts," which provides a count of the number of discrete instances of the features being evaluated (e.g., wrinkles and fine lines), regardless of the size or intensity of each instance. These values can be expressed as wrinkles counted on the left and right sides of the face ("All Wrinkles"), or as an average of wrinkles counted on each of the two facial sides ("Average Wrinkles").
[0528] As explained in Example 6 regarding composition 2.2 and WO 2022 / 243899 Figure 4The results shown in, as well as the pictures provided in Figures 7A and 7B and explained in Example 10, can be provided as a control experiment. In the present disclosure, the average wrinkle count of the skin composition containing only the nanoparticles of the core (i.e., the above-mentioned composition D) is reduced compared to the wrinkle count of the placebo composition (i.e., the wrinkle count of the placebo composition E). Similar results are expected for the compositions of the present invention including at least a similar core, and it is believed that the shell changes the charge of the nanoelement without affecting the intrinsic activity of the core, only affecting its expected efficacy based on charge-dependent delivery.
[0529] elasticity:
[0530] The effect of the composition of the present invention on skin elasticity can be treated with Dermal Torque (DTM310) (manufactured by Dia-Stron, UK) test, whereby a mechanical probe having a diameter appropriate to the depth of the skin layer to be analyzed applies a predetermined torque on a selected area of the surface of the skin on the face of a subject for a predetermined length of time ("torque on"), followed by a "torque off" period, in which the force is quickly released and the skin attempts to recover the distortion created by the torsional force. The angular rotation of the torque disk is measured by this process and provided as a ratio of the "torque on" to the "torque off" period.
[0531] Facial skin hydration:
[0532] The effect of the compositions of the present invention on skin hydration can be measured to confirm that changes in wrinkle count and / or elasticity can indeed be attributed to the specific collagen stimulating activity of the composition rather than changes in hydration levels of the skin surface.
[0533] Skin hydration analysis can be performed using the measurement of stratum corneum capacitance The measurement was performed using a CM 825 (manufactured by Courage+Khazaka Electronic GmbH, Germany) using a probe capacitor to achieve an electric scattered field that penetrates the first layer of the stratum corneum (10-20 μm). The results are reported in arbitrary units.
[0534] For the tested compositions and for the placebo used as control, the capacitance change due to hydration of the skin surface was measured before application of the composition (baseline) and compared with the value measured one month after application.
[0535] As explained in Example 8 of WO 2022 / 243899, the composition containing a CSSC core (including PCL-14) and useful as composition d) in this study showed a very slight reduction in hydration levels compared to the placebo. Similarly, neither the core-shell nanoparticle composition nor the control composition is expected to significantly affect skin hydration levels. After continuous application of the composition of the present invention, changes in hydration levels are not expected, with such values reaching saturation relatively quickly and fluctuating only due to climatic conditions. These expected results would indicate that the effect of the tested composition on reducing the number of wrinkles and / or increasing skin elasticity can be attributed specifically to the core-shell nanoelements, rather than to the effect of the liquid phase on skin properties.
[0536] Living collagen production within facial skin:
[0537] In order to confirm that the efficacy of the composition of the invention is derived in particular from the core-shell nanoelements, its ability to be delivered transdermally and its ability to achieve its biological effect of stimulating neosynthesis, the collagen content in the facial skin can be measured before and after application of the composition.
[0538] The measurement can be performed using the DermaLab Combo (produced by Dencortex Technology, Denmark), a skin analysis device that is used by passing an ultrasound probe capable of high-frequency and high-resolution analysis over a target area of the face. The output includes an image of varying color and intensity showing spots where collagen is present, with the intensity corresponding to the spots of collagen recorded in arbitrary units.
[0539] The evaluation is performed after administration of the test composition to the volunteers according to the method described above, in comparison with the corresponding placebo composition.
[0540] As in Example 9 of WO 2022 / 243899 and Figure 5B As shown, the collagen levels of subjects treated with the composition containing a CSSC core (including PCL-14) and which can be used as composition d) in this study increased significantly compared to the levels before this treatment. Similar results are expected for the compositions of the present invention, which include at least a similar core in addition to the shell and / or cosmetic active agent they may contain.
[0541] The results of the above parameters (wrinkle count, elasticity, facial skin hydration and in vivo collagen production in facial skin) can be averaged for all volunteers in the same group, and the results of different groups at different time points for each parameter can be compared. A reduction of at least 10%, at least 15% or at least 20% in each of the above parameters in any group at a given time point compared to the group receiving placebo at the same time point is considered satisfactory.
[0542] Example 14: Effect of the composition on wound healing
[0543] The following study was conducted to determine the efficacy of a composition according to the present teachings on wound healing in pigs by applying it topically to wounds on the skin of pigs for 15 days, during which time the wounds were observed and wound healing assessed.
[0544] Research System
[0545] The study followed the industry guidance “Chronic skin ulcers and burns – Development of therapeutic products” regarding preclinical models and ISO 10993-6 for histological evaluation.
[0546] Three healthy male pigs (Landrace X-Large White Crossbred, Denmark) were used in this study, each weighing 13 to 17 kg. They were ear-tagged and kept in a stainless steel-walled enclosure in a controlled environment with a temperature of 17-24°C, a relative humidity (RH) of 30-70%, a 12:12 hour light: dark cycle and 15 air changes / hour. They were provided with a commercial pig diet and free access to fresh drinking water during the acclimatization period and throughout the study. The study was started after 5 days of acclimatization.
[0547] Wound formation surgery
[0548] The acclimatized pigs were anesthetized with an isoflurane / oxygen mixture delivered by a mask, and the animals were kept under anesthesia during surgery. Six 2 cm × 2 cm complete skin and fascia incisions were made at 6 different locations on the back of each pig (half of each side), using a separate set of sterile surgical tools for each incision. Each incision was given a unique identification number, processed as described in detail in the following section, and then covered with a sterile transparent film dressing 3M TM Tegaderm TM cover.
[0549] After surgery and administration of the first treatment dose, the pigs were returned to their pens for recovery and observation. For 4 consecutive days, they received 0.5 ml of antibiotics (10% Marbofloxacin, manufactured by Vetoquino USA as commercially available) and 0.5 ml of analgesic (Metamizole, manufactured by Vetoquino in the United States Commercially available), administered via intramuscular (IM) route in the neck of the animals.
[0550] Tested composition and its application
[0551] The composition to be tested was applied immediately after the surgical wound was formed, which was defined as the first dose on the first study day. The experimental groups and dosing regimens included in this study are listed in Table 10. Before use in this study, all test compositions were sterilized, G1-G2 were exposed to 25-40KGy gamma radiation, and G3 was sterilized by autoclaving.
[0552] Table 10
[0553] Before applying the tested composition, as described for the initial surgery and the first dose, the pigs were anesthetized with a 3% isoflurane / 97% oxygen mixture. While connecting anesthesia, each pig was placed on the ground with its abdomen (prone position), the dressing was removed, and the entire wound area was cleaned with saline. Each of the three tested compositions was dripped into a separate wound, one on each side of the animal's back, so that each composition was applied twice to each animal. Each wound was then covered with a new transparent sterile dressing. Throughout the study, for the same composition, the same skin test site was used in each application of each animal. The skin test site is different between animals, for example, if the tested composition of the G1 group is applied to an incision near the neck of the first pig, its application on the second pig occurs on a farther incision closer to the pig's tail. The change of the skin test site between different pigs allows the wound healing results of the same composition to be obtained at different skin sites.
[0554] Observation and inspection
[0555] General clinical signs were recorded once a day during the acclimation and treatment periods. Animal body weights were measured at the beginning of acclimation, on study day 1 (before surgery), on study day 7, on study day 10, and at the end of the study (day 15). Animals gained weight naturally during the study, indicating that no wound and its treatment affected their appetite.
[0556] Once a day, when the animals were under anesthesia and the dressings were removed, representative photos of the wounds were taken using a dedicated camera and 3D scanner (SilkuetteStar of Aranz Medical, New Zealand) suitable for wound and skin assessment. Wound inspections and changes were also recorded at this time. The wounds were then treated as planned, covered with new sterile dressings, and the animals were returned to their enclosures for recovery.
[0557] Prior to daily application of the test composition, wounds were assessed using the scoring detailed in Table 11.
[0558] Table 11
[0559] First, it is generally noted that no bad odors were perceived and no wound infections were observed throughout the study period with any of the treatment groups. This observation was reinforced by the lack of exudate in the wounds of all groups. It is noteworthy that as early as day 3, the wounds treated by the G1 group began to show a gradual formation of a layer of the composition that accumulated steadily in the open area of the wound. Since this layer could not be washed away with periodic saline flushing, it is believed that the compositions of the present invention can effectively remain on the wound surface, on which they can form a protective coating.
[0560] For erythema, mild redness was observed in the periwound area from day 3 to about day 8 of the study, with a peak average of about 1.2 on day 6 for both the G2 and G3 control groups. On the same day, the wounds of the G1 group treated with the composition of the invention showed an average erythema score of only 0.17. Slight swelling was observed between days 4 and 7, but the swelling completely disappeared from day 8 onwards for all treatment groups. The wounds of the G1 group showed their highest swelling on day 4, and even then, their average edema score was only 0.67. Granulation tissue filling of the wound bed was observed from day 8 of the study, and scabs were first observed on day 7. The wounds of the G1 group showed an average scab score of 0.67 on the day of the first occurrence, while the G2 and G3 control groups showed no scabs or an average score of only 0.17, respectively. Finally, the wound area of each day and group was averaged, and the measurements from day 2 onwards were normalized to day 1, setting the display to 100% for wound area or 0% for wound closure. It should be noted that although the incision formed in the skin is intended to form an approximately 4 cm circumference with a circumference of approximately 8 cm 2 wound, but the natural stretching of the skin around the excision area resulted in a circumference of approximately 9 cm with a circumference of approximately 12 cm 2 The wounds in the G1 group closed steadily over time, with an average daily decrease in wound area of about 5%, so that at the end of the study the average area of the G1 wound was about 30% of its original size. 2 Full thickness excisional wounds with an initial size of 100 mm and a depth of 3 mm to 6 mm, depending on the location of the wound, achieved approximately 70% closure of the wounds within the 15-day study duration.
[0561] Termination and histological analysis
[0562] At the end of the study, animals were euthanized with sodium pentobarbital (>100 mg / kg intraperitoneal) and samples were taken for histological testing. The entire wound area of each incision was harvested from each animal and fixed in 4% formalin for histological analysis. The tissue was labeled with the wound identification number and the animal number. From the formalin-fixed tissue, 5 mm thick sections were cut from the center of each wound, processed and embedded in paraffin for hematoxylin-eosin (H&E) staining. Each slide can be scanned using a high-resolution digital scanner so that the H&E stained tissue can be analyzed in detail and the treatment groups can be compared. Histopathological microscopic analysis of H&E slides can evaluate any of the following parameters (according to ISO10993-6, and to the extent applicable): 1. Extent of wound closure; 2. Extent of epithelial regeneration; 3. Amount of necrotic tissue; 4. Bleeding; 5. Fibrin; 6. Severity of inflammation; 7. Amount of granulation and fibrous tissue; 8. Fatty infiltration; 9. Neovascularization; 10. Presence of bacteria or evidence of bacterial infection; 11. Amount of test item wound matrix remnants; 12. Tissue integration; 13. Cyst cavities.
[0563] Example 15: Use of the composition for transdermal delivery of active agents
[0564] The following pharmacokinetic studies may be performed to determine the effects of compositions according to the present teachings on the delivery of active agents to the blood of living animals. The active agent may be CSSC miscible and disposed in the core of the nanoshell nanoelement of the invention, such as in the composition of Example 8, or if water miscible, may be disposed in a surrounding second shell, such as in the composition of Example 9. Tadalafil, such as found in the core of the nanoelement of ND30, may be measured, for example, by liquid chromatography with tandem mass spectrometry (LC-MS-MS), and may therefore be suitable.
[0565] The study can be conducted with one or two arms. In the main part of the study, a single effective dose of a composition containing an active agent can be applied to the shaved back of a study animal (e.g., mouse) under anesthesia. The mice can be divided into several groups and blood is drawn at predetermined time points (e.g., 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 8 hours, 12 hours, and 24 hours after administration), with each group (usually 3 mice per group) participating in no more than 3 samplings. The blood samples can be further processed as needed to be able to measure the level of the active agent. Skin sampling at predetermined time points can also be used for histological analysis.
[0566] In the second and optional branch of this study, a reference composition comprising the same active agent at the same dose (although conventionally prepared (i.e., not in the form of core-shell nanoelement of the present invention)) can be administered by any suitable route other than transdermal administration as compared to the first branch of this study. For illustration, the reference composition can be administered orally by gavage. The animals are then bled at the same predetermined time point after ingestion, and the level of the active agent in the blood sample is measured.
[0567] In addition to the features of the above disclosure that are particularly claimed in the appended claims, features that are regarded as inventive in their own right are set forth in the following clauses to provide a reasonable basis for the eventual filing of one or more divisional patent applications.
[0568] Terms
[0569] 1. A skin composition comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements are composed of:
[0570] a) a core comprising a water-insoluble, biodegradable collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; and
[0571] b) a shell surrounding the core, the shell comprising a water-insoluble fatty amine non-covalently bonded to the CSSC;
[0572] wherein the core-shell nanoparticles are capable of carrying a positive charge in water; and
[0573] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
[0574] 2. The skin composition according to clause 1, wherein the CSSC is characterized by at least one, at least two or at least three of the following properties:
[0575] i. The CSSC is insoluble in polar carriers;
[0576] ii. The CSSC has a first melting temperature of at most 300°C, at most 250°C, at most 200°C, at most 180°C, at most 150°C, or at most 120°C TM , at least one of a first softening temperature (Ts) and a first glass transition temperature (Tg);
[0577] iii. the CSSC has a first Tm or Ts of at least 20°C, at least 30°C, at least 40°C, at least 50°C or at least 60°C;
[0578] iv. the CSSC has a first Tg of -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 25°C or higher, or 50°C or higher;
[0579] v. the CSSC has at least one of a first Tm, Ts, and Tg between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 180°C, or between 50°C and 150°C;
[0580] vi. the CSSC has a molecular weight of 0.7 kDa or more, 0.8 kDa or more, 0.9 kDa or more, 1 kDa or more, 2 kDa or more, or 5 kDa or more;
[0581] vii. the CSSC has a molecular weight of 500 kDa or less, 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less; and
[0582] viii. The molecular weight of the CSSC is between 0.6 kDa and 500 kDa, between 0.7 kDa and 300 kDa, between 0.8 kDa and 200 kDa, between 1 kDa and 100 kDa, or between 2 kDa and 80 kDa.
[0583] 3. The skin composition according to clause 1 or clause 2, wherein the CSSC is selected from:
[0584] (I) a polymer selected from the group of polymer families consisting of aliphatic polyesters, polyhydroxyalkanoates, poly(olefin dicarboxylates), polycarbonates, aliphatic-aromatic copolyesters, isomers thereof, copolymers thereof, and combinations thereof; and
[0585] (II) A quinone selected from the group consisting of coenzyme Q10.
[0586] 4. The skin composition according to any one of clauses 1 to 3, wherein the core further comprises at least one of a non-volatile liquid and a water-insoluble active agent.
[0587] 5. The skin composition according to item 4, wherein the non-volatile liquid is selected from the group consisting of monofunctional or polyfunctional aliphatic esters, fatty esters, cyclic organic esters, fatty acids, terpenes, aromatic alcohols, aromatic ethers, aldehydes and combinations thereof.
[0588] 6. A skin composition according to any one of clauses 1 to 5, wherein the CSSC has at least one of a second Tm, Tg or Ts that is lower than the corresponding first Tm, Tg or Ts of the CSSC, and at least one of the second Tm, Tg and Ts of the plasticized CSSC is in the range of 0°C to 290°C, 10°C to 250°C, 20°C to 200°C, 30°C to 190°C, 40°C to 180°C or 50°C to 170°C.
[0589] 7. The skin composition according to any one of clauses 1 to 6, wherein the water-insoluble fatty amine is a primary, secondary, tertiary or quaternary C8-C 22 A linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic, alkyl or aryl amine or a combination thereof.
[0590] 8. The skin composition according to any one of clauses 1 to 7, wherein the natural form of CSSC has a first viscosity, and the CSSC in the skin composition has a second viscosity lower than the first viscosity, at least one of the first viscosity and the second viscosity being stable at a temperature of 50° C. and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or less, 10 6 mPa·s or less, 10 5 mPa·s or less, 10 4 mPa·s or less or 10 3 mPa·s or less.
[0591] 9. A skin composition according to any one of clauses 1 to 8, wherein the polar carrier has a boiling temperature (Tbc) between 45°C and 350°C, between 70°C and 300°C, between 85°C and 250°C or between 90°C and 250°C, and the polar carrier is optionally selected from the group consisting of water, glycols, glycerin and combinations thereof.
[0592] 10. The skin composition according to any one of clauses 1 to 9, further comprising at least one surfactant which is an emulsifier or a hydrotrope.
[0593] 11. The skin composition according to any one of clauses 1 to 10, wherein the core-shell nanoelements have a charge of +5 mV or more, +10 mV or more, +20 mV or more, +30 mV or more, or +40 mV or more in water.
[0594] 12. The skin composition according to any one of clauses 1 to 11, further comprising a carrier soluble active agent forming a second shell on the outer surface of the core-shell nanoelements.
[0595] 13. A skin composition according to any one of clauses 1 to 12, wherein at least one of the core-shell nanoelements and the core-shell nanoelements having a second shell made of an active agent has a D of 190 nm or less, 175 nm or less, 150 nm or less, 125 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less and optionally 5 nm or more. N 50.
[0596] 14. The skin composition according to any one of clauses 1 to 13, wherein the core-shell nanoelement has a temperature of 50°C and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or less, 10 6 mPa·s or less or 10 5 Viscosity of mPa·s or less.
[0597] 15. A skin composition comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements are composed of:
[0598] a) a core comprising at least one water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; and
[0599] b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC;
[0600] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and
[0601] The core-shell nanoelement has a temperature of 50°C and a temperature of 10 sec. -1 The shear rate was measured at 10 7 Viscosity of mPa·s or less.
[0602] 16. An agrochemical or industrial composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements consisting of:
[0603] a) a core comprising at least one water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; and
[0604] b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC;
[0605] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and
[0606] The core-shell nanoelement has a temperature of 50°C and a temperature of 10 sec. -1 The shear rate was measured at 10 7 Viscosity of mPa·s or less.
[0607] 17. A composition comprising core-multi-shell nanoelements dispersed in a polar carrier, the core-multi-shell nanoelements consisting of:
[0608] a) a core comprising at least one thermoplastic compound having a molecular weight of 0.6 kDa or more;
[0609] b) a first shell surrounding the core, the first shell comprising a hydrophilic portion of at least one water-insoluble aliphatic compound non-covalently bonded to the thermoplastic compound; and
[0610] c) a second shell surrounding the first shell, the second shell comprising at least one water-soluble active agent, the fatty compound and the water-soluble active agent having opposite charges in the presence of water;
[0611] wherein at least 50% of the total number of the core-multishell nanoelements have an average diameter (e.g., D N 50); and
[0612] wherein the core-multishell nanoelement is heated to 50°C for 10 seconds -1 The shear rate was measured at 10 7 Viscosity of mPa·s or less.
[0613] 18. A composition according to clause 17, wherein the or each water-insoluble fatty compound is capable of being negatively charged in a liquid medium comprising water, and the or each water-soluble active agent is capable of being positively charged in said medium.
[0614] 19. A composition according to clause 18, wherein the or each water-insoluble aliphatic compound capable of being negatively charged is selected from a linear, branched or cyclic saturated or unsaturated aliphatic or aromatic C8-C 22 Fatty acids, C8-C 22 Fatty esters and C8-C 22 Fatty alcohol.
[0615] 20. A composition according to clause 17, wherein the or each water-insoluble fatty compound is positively chargeable in a liquid medium comprising water and the or each water-soluble active agent is negatively chargeable in said medium.
[0616] 21. A composition according to clause 20, wherein the or each positively chargeable water-insoluble aliphatic compound is selected from a linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic C8-C 22 Alkyl or aryl aliphatic amines.
[0617] 22. The composition according to any one of clauses 17 to 21, further comprising one or more water-insoluble active agents disposed in the core of the core-multi-shell nanoelement.
[0618] 23. The composition according to any one of clauses 17 to 22, wherein the core-multishell nanoelement has a -1 The shear rate was measured at 10 7 mPa·s or less, 10 6 mPa·s or less or 10 5 Viscosity of mPa·s or less.
[0619] 24. A composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements consisting of:
[0620] a) a core comprising at least one thermoplastic compound having a molecular weight of 0.6 kDa or more; and
[0621] b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the thermoplastic compound;
[0622] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and
[0623] The core-shell nanoelement has a temperature of 50°C and a temperature of 10 sec. -1 The shear rate was measured at 10 7 Viscosity of mPa·s or less.
[0624] 25. A composition according to any one of clauses 17 to 24, wherein the thermoplastic compound is selected from: i) a biodegradable CSSC as described herein; and ii) a non-biodegradable thermoplastic polymer including polyamides, polyethylenes, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, ethylene-n-butyl acrylate copolymers, polymethyl methacrylate, polypropylenes, polysiloxanes, polystyrenes, polytetrafluoroethylene, polyurethanes, ethylene-vinyl acetate copolymers, polyvinyl chloride, substituted or modified forms thereof, ionomers thereof, and combinations thereof.
[0625] 26. A composition according to any one of clauses 17 to 25, wherein the thermoplastic compound is a biodegradable CSSC and the nanoelements further comprise a non-volatile liquid selected from the group consisting of mineral oils, natural oils, vegetable oils, essential oils, synthetic oils and combinations thereof, the oil having the characteristics as described herein.
[0626] 27. A composition according to any one of clauses 17 to 25, wherein the thermoplastic compound is a non-biodegradable polymer and the nanoelements further comprise a non-volatile liquid selected from the group consisting of mineral oil, natural oil, vegetable oil, essential oil, synthetic oil and combinations thereof, the oil having the characteristics as described herein.
[0627] 28. A composition according to any one of clauses 1 to 27, wherein the core-shell nanoelements are substantially free of VOCs, having a VOC content, if any, of no more than 2% by weight of the nanoelements, or any other value and / or range as described herein and particularly claimed in the appended claims.
[0628] 29. The composition according to any one of clauses 1 to 28, wherein the CSSC or the thermoplastic compound is selected from CoQ10, shellac, rosin, polycaprolactone, polylactic acid, lactic acid-glycolic acid copolymer and butylene succinate-adipate copolymer; the fatty amine is selected from primary, secondary, tertiary or quaternary C8-C 20 a linear, branched or cyclic saturated or unsaturated aliphatic alkylamine; a non-volatile liquid, when present, being an aliphatic or aromatic fatty acid ester; a water-insoluble active agent, when present, selected from bakuchiol, benzoyl peroxide, castor oil, curcumin, neem oil, retinyl palmitate and tadalafil; and a water-soluble active agent, when present, selected from collagen, elastin, hyaluronic acid and vitamin C.
[0629] 30. A composition according to any one of clauses 1 to 29, wherein the core-shell nanoelement optionally comprises at least one active agent, each active agent being independently water-insoluble and disposed in the core, or water-soluble and disposed in the shell of the core-shell nanoelement, the composition being used to prepare a medicament for treating a wound in a living subject, the medicament being topically applied to the wound and / or near the wound.
[0630] 31. A composition according to any one of clauses 1 to 30 comprising an ingredient as described herein and / or prepared as described herein and / or for use as described herein and in particular as claimed in the appended claims.
[0631] 32. A method for preparing a skin composition comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements comprise a collagen synthesis stimulating compound (CSSC), the method comprising the steps of:
[0632] a) Provide CSSC, including:
[0633] i. the CSSC is biodegradable;
[0634] ii. the CSSC is water-insoluble;
[0635] iii. the CSSC has a molecular weight of at least 0.6 kDa;
[0636] iv. the CSSC has at least one of a first melting temperature (Tm), a first softening temperature (Ts), and a first glass transition temperature (Tg) of 300° C. or less; and
[0637] v. The CSSC has a temperature of 50°C and 10 sec. -1 Optionally measured at a shear rate higher than 10 7 First viscosity in mPa·s;
[0638] b) mixing the CSSC with a water-insoluble fatty amine and optionally with a CSSC-miscible non-volatile liquid, the mixing being carried out at a mixing temperature equal to or higher than at least one of a first Tm, Ts and Tg of the CSSC, thereby forming a homogeneous mixture of the optionally plasticized CSSC and the fatty amine, the mixture comprising the CSSC having a second Tm, Ts or Tg lower than the respective first Tm, Ts or Tg, and a second viscosity lower than the first viscosity, at least one of the first viscosity and the second viscosity being less than the first viscosity at 50°C and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or lower;
[0639] c) combining the polar carrier with the mixture obtained in step b); and
[0640] d) nanosizing the combination of step c) by applying shear at a shear temperature equal to or higher than at least one of the first Tm, Ts and Tg of the CSSC or at least one of the second Tm, Ts and Tg of the optionally plasticized CSSC to obtain a nanosuspension, thereby dispersing core-shell nanoelements of the (optionally plasticized) CSSC and the fatty amine in the polar carrier, the nanoelements having an average diameter D of 200 nm or less V 50;
[0641] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
[0642] 33. The method of clause 32, wherein the CSSC is further characterized by at least one, at least two, or at least three of the following characteristics:
[0643] i. The CSSC is insoluble in polar carriers;
[0644] ii. the CSSC has at least one of a first Tm, Ts or Tg of at most 250°C, at most 200°C, at most 180°C, at most 150°C or at most 120°C;
[0645] iii. the CSSC has a first Tm or Ts of at least 20°C, at least 30°C, at least 40°C, at least 50°C or at least 60°C;
[0646] iv. the CSSC has a first Tg of -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 25°C or higher, or 50°C or higher;
[0647] v. the CSSC has at least one of a first Tm, Ts, and Tg between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 180°C, or between 50°C and 150°C;
[0648] vi. the CSSC has a molecular weight of 0.7 kDa or more, 0.8 kDa or more, 0.9 kDa or more, 1 kDa or more, 2 kDa or more, or 5 kDa or more;
[0649] vii. the CSSC has a molecular weight of 500 kDa or less, 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less; and
[0650] viii. The CSSC has a molecular weight between 0.6 kDa and 500 kDa, between 0.7 kDa and 300 kDa, between 0.8 kDa and 200 kDa, between 1 kDa and 100 kDa, or between 5 kDa and 80 kDa.
[0651] 34. A method according to clause 32 or 33, wherein in step b) the CSSC is mixed with a non-said volatile liquid, the non-volatile liquid being added in a concentration ranging from 5 wt % to 350 wt %, from 10 wt % to 200 wt %, from 25 wt % to 150 wt % or from 50 wt % to 125 wt % based on the weight of the CSSC.
[0652] 35. A method according to any one of clauses 32 to 34, wherein the CSSC is mixed with the non-volatile liquid in step b) and at least one of the second Tm, Ts or Tg of the plasticized CSSC is in the range of 0°C to 290°C, 10°C to 250°C, 20°C to 200°C, 30°C to 190°C, 40°C to 180°C or 50°C to 170°C.
[0653] 36. The method according to any one of clauses 32 to 35, wherein in step b) the CSSC is mixed with the non-volatile liquid and at least one of the first viscosity of the CSSC and the second viscosity of the plasticized CSSC is 1:1 at 50°C and 10 sec. -1 The shear rate was measured at 5 × 10 6 mPa·s or less, 10 6 mPa·s or less, 5×10 5 mPa·s or less, 10 5 mPa·s or less, 10 4 mPa·s or less or 10 3 mPa·s or less.
[0654] 37. The method according to any one of clauses 32 to 35, wherein the water-insoluble fatty amine is a primary, secondary, tertiary or quaternary C8-C 22 A linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic, alkyl or aryl amine, or a combination thereof.
[0655] 38. A method according to any one of clauses 32 to 37, comprising step b), and further comprising combining during step b) at least one of:
[0656] i. a polar carrier insoluble surfactant; and
[0657] ii. intermediate emulsifier; and
[0658] iii. Polar carrier insoluble active agent.
[0659] 39. The method according to any one of clauses 32 to 38, wherein the polar liquid carrier further comprises a pH adjuster.
[0660] 40. A method according to any one of clauses 32 to 39, wherein the core-shell nanoparticle has a charge of +5 mV or more, +10 mV or more, +20 mV or more, +30 mV or more or +40 mV or more measured at room temperature in the presence of water.
[0661] 41. The method according to any one of clauses 32 to 40, further comprising adding a polar carrier soluble active agent into the polar carrier during or after step c) or step d), at least a portion of the active agent forming a second shell on the outer surface of the core-shell nanoelement.
[0662] 42. The method according to any one of clauses 32 to 41, further comprising adding at least one of the following during or after step c) or step d):
[0663] i. polar carrier soluble surfactant;
[0664] ii. intermediate emulsifier; and
[0665] iii. Skin penetration enhancers.
[0666] 43. A method according to any one of clauses 32 to 42, wherein the polar carrier has a boiling point Tbc at nano-sized pressure, and the fatty amine and optional non-volatile liquid have a boiling point Tbc at mixed pressure. a and Tb l , and the fatty amine has a degradation point under the pressure of mixing, the temperature of nano-sizing is lower than Tbc, and the temperature of mixing is lower than Tb a , fatty amine degradation point and optionally below Tb l .
[0667] 44. A method of preparing a composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements comprising a thermoplastic compound, the method comprising the steps of:
[0668] a) providing a thermoplastic compound, wherein:
[0669] i. The thermoplastic compound is water-insoluble;
[0670] ii. said thermoplastic compound having a molecular weight of at least 0.6 kDa;
[0671] iii. the thermoplastic compound has at least one of a first melting temperature (Tm), a first softening temperature (Ts), and a first glass transition temperature (Tg) of 300°C or less; and
[0672] iv. The thermoplastic compound has a temperature of 50°C and 10 sec. -1 Optionally measured at a shear rate higher than 10 7 First viscosity in mPa·s;
[0673] b) mixing the thermoplastic compound with a water-insoluble fatty amine and optionally with a non-volatile liquid miscible with the thermoplastic compound, the mixing being carried out at a mixing temperature equal to or higher than at least one of a first Tm, Ts and Tg of the thermoplastic compound, thereby forming a homogeneous mixture of the optionally plasticized thermoplastic compound and the fatty amine, the mixture comprising the thermoplastic compound having a second Tm, Ts or Tg lower than the corresponding first Tm, Ts or Tg and a second viscosity lower than the first viscosity, at least one of the first viscosity and the second viscosity being lower than the first viscosity at 50° C. and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or lower;
[0674] c) combining said polar carrier with said mixture obtained in step b); and
[0675] d) nanosizing the combination of step c) by applying shear at a shear temperature equal to or higher than at least one of the first Tm, Ts and Tg of the thermoplastic compound or at least one of the second Tm, Ts and Tg of the optionally plasticized thermoplastic compound to obtain a nanosuspension, thereby dispersing core-shell nanoelements of the (optionally plasticized) thermoplastic compound and the fatty amine in the polar carrier;
[0676] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and
[0677] The core-shell nanoelement has 10 7 Viscosity of mPa·s or less.
[0678] 45. A method according to clause 44, wherein the thermoplastic compound is selected from: i) a biodegradable CSSC as disclosed herein; and ii) a non-biodegradable thermoplastic polymer selected from polyamide, polyethylene, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-n-butyl acrylate copolymer, polymethyl methacrylate, polypropylene, polysiloxane, polystyrene, polytetrafluoroethylene, polyurethane, ethylene-vinyl acetate copolymer, polyvinyl chloride, substituted or modified forms thereof, ionomers thereof, and combinations thereof.
[0679] 46. A method according to clause 44 or 45, wherein the thermoplastic compound is a biodegradable CSSC, the method comprising mixing the thermoplastic compound with a non-volatile liquid selected from the group consisting of mineral oils, natural oils, vegetable oils, essential oils, synthetic oils and combinations thereof, the oil having the characteristics as described herein.
[0680] 47. A method according to clause 44 or 45, wherein the thermoplastic compound is a non-biodegradable thermoplastic polymer, the method comprising mixing the thermoplastic compound with a non-volatile liquid selected from the group consisting of mineral oils, natural oils, vegetable oils, essential oils, synthetic oils and combinations thereof, the oil having the characteristics as described herein.
[0681] 48. A method according to any one of clauses 32 to 47, wherein the core-shell nanoelements are substantially free of VOCs, having a VOC content of no more than 2% by weight of the nanoelements, if any, or any other value and / or range as described herein and particularly claimed in the appended claims.
[0682] 49. A method according to any one of clauses 32 to 48 for preparing core-shell nanoelements suitable for use in a dermatological cosmetic composition, dermatological pharmaceutical composition, agrochemical composition or industrial composition.
[0683] 50. A method according to any one of clauses 32 to 49, comprising the steps as described herein, carried out with the ingredients (and concentrations thereof) as described herein and especially claimed in the appended claims.
[0684] 51. Use of a skin composition for improving the appearance and / or health of the skin, the skin composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements consisting of:
[0685] a) a core comprising a biodegradable, water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; and
[0686] b) a shell surrounding the core, the shell comprising a water-insoluble fatty amine non-covalently bonded to the CSSC;
[0687] wherein the core-shell nanoelement is capable of carrying a positive charge in water; and
[0688] wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
[0689] 52. The use according to clause 51, wherein the composition for skin application is a composition for skin application according to any one of clauses 1 to 14.
[0690] 53. The use according to clause 51 or clause 52, wherein the skin composition is a cosmetic composition having at least one effect selected from the group consisting of anti-decomposition of collagen, elastin or glycosaminoglycans, promotion of neosynthesis of collagen, elastin or glycosaminoglycans, treatment of signs of skin aging, anti-wrinkles and fine lines, anti-drying of the skin, anti-skin sagging, anti-thinning of the skin, anti-dullness of the skin and anti-lack of skin elasticity and / or tension.
[0691] 54. The use according to clause 51 or 52, wherein the skin composition is a pharmaceutical composition having at least one effect on the skin treated therewith...
Claims
1. A composition comprising core-shell nanoelements dispersed in a polar carrier, wherein the core-shell nanoelements are composed of: a) a core comprising at least one water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kDa or more; as well as b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC; wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and The core-shell nanoelement has a temperature of 50°C and a temperature of 10 sec. -1 The shear rate was measured at 10 7 Viscosity of mPa·s or less.
2. The composition of claim 1, wherein the core further comprises at least one of: a non-volatile liquid, a water-insoluble active agent, and a pH adjuster; each miscible with the CSSC.
3. The composition of claim 2, wherein the non-volatile liquid is selected from the group consisting of monofunctional or polyfunctional aliphatic esters, fatty esters, cyclic organic esters, aromatic esters, fatty acids, terpenes, aromatic alcohols, aromatic ethers, aldehydes, and combinations thereof; and the non-volatile liquid is insoluble in the polar carrier.
4. The composition according to any one of claims 1 to 3, wherein the CSSC and / or the core-shell nanoelement are each independently characterized by at least one, at least two or at least three of the following properties: i. The CSSC and / or the core-shell nanoelement is insoluble in the polar carrier; ii. the CSSC and / or the core-shell nanoelement is biodegradable and / or biocompatible; iii. the CSSC has at least one of a first melting temperature (Tm), a first softening temperature (Ts), and a first glass transition temperature (Tg) of at most 300°C, at most 250°C, at most 200°C, at most 180°C, at most 150°C, or at most 120°C; iv. the core-shell nanoelement has at most 300°C, at most 250°C, at most 200°C, at most 180°C, at most 150°C or at most 120°C of a second melting temperature (Tm), a second softening temperature (Ts) and a second glass transition temperature (Tg); v. the CSSC and / or the core-shell nanoelement each have at least one of a first Tm and a second Tm of at least 0°C, at least 10°C, at least 20°C, at least 30°C, at least 40°C, at least 50°C, or at least 60°C, respectively; vi. the CSSC and / or the core-shell nanoelement each have at least one of a first Tm and a second Tm between 0°C and 300°C, between 10°C and 300°C, between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 180°C, or between 50°C and 150°C; vii. the CSSC and / or the core-shell nanoelement each have at least one of a first Tg, a first Ts, a second Tg, and a second Ts of -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 25°C or higher, or 50°C or higher; viii. the CSSC and / or the core-shell nanoelement each have at least one of a first Tg, a first Ts, a second Tg, and a second Ts between -75°C and 300°C, between -50°C and 250°C, between -25°C and 200°C, between 0°C and 180°C, between 20°C and 180°C, or between 30°C and 150°C; ix. The core-shell nanoelement has a temperature of 50°C and 10 sec. -1 The shear rate was measured at 5 × 10 6 mPa·s or less, 10 6 mPa·s or less, 5×10 5 mPa·s or less, 10 5 mPa·s or less, 5×10 4 mPa·s or less, 10 4 mPa·s or less, 5×10 3 mPa·s or less or 10 3 Viscosity of mPa·s or less; x. the CSSC has a molecular weight of 0.7 kDa or more, 0.8 kDa or more, 0.9 kDa or more, 1 kDa or more, 2 kDa or more, or 5 kDa or more; xi. the CSSC has a molecular weight of 500 kDa or less, 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less; as well as xii. The CSSC has a molecular weight between 0.6 kDa and 500 kDa, between 0.7 kDa and 300 kDa, between 0.8 kDa and 200 kDa, between 1 kDa and 100 kDa, or between 2 kDa and 80 kDa.
5. The composition according to any one of claims 1 to 4, wherein the CSSC is selected from: (I) a polymer selected from the group of polymer families comprising aliphatic polyesters, polyhydroxyalkanoates, poly(olefin dicarboxylates), polycarbonates, aliphatic-aromatic copolyesters, polysaccharides, lignin, isomers thereof, copolymers thereof, and combinations thereof; (II) a naturally polymerizable CSSC selected from the group consisting of resins, gums and gum-resins; and (III) A quinone selected from the group consisting of coenzyme Q10.
6. The composition according to any one of claims 1 to 5, wherein the water-insoluble fatty amine is a primary, secondary, tertiary or quaternary C8-C 22 A linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic, alkyl or aryl amine or a combination thereof.
7. The composition according to any one of claims 1 to 6, wherein the polar carrier has a boiling temperature (Tb) between 45°C and 350°C, between 70°C and 300°C, between 85°C and 250°C, or between 90°C and 250°C. c ), wherein the polar carrier is optionally selected from the group consisting of water, glycols, glycerol and combinations thereof.
8. The composition according to any one of claims 1 to 7, further comprising at least one surfactant which is an emulsifier or a hydrotrope.
9. The composition according to any one of claims 1 to 8, wherein the core-shell nanoelement is capable of carrying an electric charge in the presence of water, the electric charge measured at room temperature being selected from: A) a positive charge of +5 mV or more, +10 mV or more, +20 mV or more, +30 mV or more, or +40 mV or more; and B) a negative charge between -60 mV and -5 mV, between -50 mV and -5 mV, between -40 mV and -5 mV, between -30 mV and -5 mV, or between -20 mV and -5 mV.
10. The composition according to any one of claims 1 to 9, further comprising a carrier soluble active agent forming a second shell on the outer surface of the core-shell nanoelement.
11. A composition according to any one of claims 2 to 10, wherein the active agent is selected from: a) selected from the group consisting of: Cosmetic agents from the group of anti-aging, anti-acne, antioxidant, bleaching and tanning agents; b) an agent selected from the group consisting of: ADHD-relieving agents, analgesics, anesthetics, anthelmintics, anti-addiction withdrawal agents, anti-anginal agents, anti-arthritic agents, antibacterial agents, antidepressants, antiemetics, antifungal agents, anti-inflammatory agents, antiparasitic agents, antirheumatic drugs, antiepileptic drugs, antiviral drugs, blood pressure regulators, contraceptives, hair growth promoters or inhibitors, glaucoma relievers, hormones, thyroid regulators, neuroprotectants, and neurotoxicity protectants; and c) agricultural chemicals and / or industrial products selected from the group consisting of acaricides, algaecides, animal repellents, anthelmintics, moth repellents, avicides, bactericides, chemosterilants, fertilizers, fungicides, herbicides, insect pheromones, anthelmintics, insecticides, molluscicides, nematicides, nitrification inhibitors, ovicides, plant growth activators, rodenticides, termites and virucides.
12. A composition according to any one of claims 1 to 11, wherein the core-shell nanoelement, in the absence or presence of a second shell made of a carrier-soluble active agent, has a D of 190 nm or less, 175 nm or less, 150 nm or less, 125 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less. N 50; and optionally a D of 5 nm or more N 50.
13. The composition of any one of claims 1 to 12, wherein the core-shell nanoelements contain less than 2 wt%, less than 1.5 wt%, or less than 1 wt% VOCs based on the weight of the nanoelements.
14. The composition according to any one of claims 1 to 13, wherein the CSSC is selected from CoQ10, shellac, rosin, polycaprolactone, polylactic acid, lactic acid-glycolic acid copolymer and butylene succinate-butylene adipate copolymer; the fatty amine is selected from primary, secondary, tertiary or quaternary C8-C 20 aliphatic alkylamine, linear, branched or cyclic, saturated or unsaturated; and a nonvolatile liquid, when present, an aliphatic or aromatic fatty acid ester.
15. A method for preparing a composition comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements comprising a collagen synthesis stimulating compound (CSSC) in their core, the method comprising the following steps: a) providing at least one CSSC, wherein the or each CSSC: i. is water-insoluble; ii. having a molecular weight of at least 0.6 kDa; iii. having at least one of a first melting temperature (Tm), a first softening temperature (Ts), and a first glass transition temperature (Tg) of 300°C or less; and iv. With 50℃ and 10sec -1 Optionally measured at a shear rate higher than 10 7 First viscosity in mPa·s; b) mixing the at least one CSSC with at least one water-insoluble fatty amine miscible with the CSSC, the mixing being carried out at a mixing temperature equal to or higher than at least one of a first Tm, Ts and Tg of the CSSC, thereby forming a homogeneous mixture comprising the fatty amine and the optionally plasticized CSSC, the mixture having: A- a second Tm, Ts or Tg, which is optionally at least 5°C, at least 10°C, at least 15°C, at least 20°C, at least 25°C, at least 30°C, at least 35°C, at least 40°C, at least 45°C or at least 50°C lower than the corresponding first Tm, Ts or Tg of the CSSC; and B-optionally a second viscosity lower than the first viscosity, at least one of the first viscosity and the second viscosity being -1 The shear rate was measured at 10 7 mPa·s or less; c) combining a polar carrier with the homogeneous mixture obtained in step b); and d) nanosizing the combination of step c) by applying shear at a shear temperature equal to or higher than at least one of the first and second Tm, Ts and Tg to obtain a nanosuspension of core-shell nanoelements dispersed in a polar carrier; wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50).
16. The method of claim 15, wherein the at least one CSSC is further characterized by at least one, at least two, or at least three of the following characteristics: i. the CSSC is insoluble in the polar carrier; ii. the CSSC has at least one of a first Tm, Ts or Tg of at most 250°C, at most 200°C, at most 180°C, at most 150°C or at most 120°C; iii. the CSSC has a first Tm of at least 0°C, at least 10°C, at least 20°C, at least 30°C, at least 40°C, at least 50°C, or at least 60°C; iv. the CSSC has a first Tm between 0°C and 300°C, between 10°C and 300°C, between 20°C and 300°C, between 20°C and 250°C, between 20°C and 200°C, between 30°C and 180°C, between 40°C and 180°C, or between 50°C and 150°C; v. the CSSC has at least one of a first Tg and a first Ts of -75°C or higher, -50°C or higher, -25°C or higher, 0°C or higher, 25°C or higher, or 50°C or higher; vi. the CSSC has at least one of a first Tg and a first Ts between -75°C and 300°C, between -50°C and 250°C, between -25°C and 200°C, between 0°C and 180°C, between 20°C and 180°C, or between 30°C and 150°C; vii. the CSSC has a molecular weight of 0.7 kDa or more, 0.8 kDa or more, 0.9 kDa or more, 1 kDa or more, 2 kDa or more, or 5 kDa or more; viii. the CSSC has a molecular weight of 500 kDa or less, 300 kDa or less, 200 kDa or less, 100 kDa or less, 80 kDa or less, 50 kDa or less, 25 kDa or less, or 15 kDa or less; ix. the CSSC has a molecular weight between 0.6 kDa and 500 kDa, between 0.7 kDa and 300 kDa, between 0.8 kDa and 200 kDa, between 1 kDa and 100 kDa, or between 5 kDa and 80 kDa; x. The CSSC has a temperature of 50°C and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or less, 5x10 6 mPa·s or less, 10 6 mPa·s or less, 5x10 5 mPa·s or less, 10 5 mPa·s or less, 5x10 4 mPa·s or less, 10 4 mPa·s or less, 5x10 3 mPa·s or less, or 10 3 a first viscosity of mPa·s or less; and xi. The CSSC is biodegradable and / or biocompatible.
17. The method according to claim 15 or 16, wherein in step b), a non-volatile liquid miscible with CSSC is mixed with the CSSC and the fatty amine, and the non-volatile liquid is added in a concentration ranging from 5wt% to 350wt%, 10wt% to 200wt%, 25wt% to 150wt%, 25wt% to 100wt% or 50wt% to 125wt% based on the weight of the CSSC.
18. The process according to any one of claims 15 to 17, wherein in step b) a non-volatile liquid miscible with the CSSC is mixed with the CSSC and the fatty amine, and wherein the homogeneous mixture thus obtained satisfies at least one of the following properties: I) has a second Tm in the range of 0°C to 290°C, 10°C to 250°C, 20°C to 200°C, 30°C to 190°C, 40°C to 180°C, or 50°C to 170°C; II) has at least one of a second Tg and a second Ts in the range of -20°C to 290°C, -10°C to 290°C, 0°C to 290°C, 10°C to 250°C, 20°C to 200°C, 30°C to 190°C, 40°C to 180°C, or 50°C to 170°C; and III) has a temperature of 50°C and 10 sec. -1 The shear rate was measured at 10 7 mPa·s or less, 5x10 6 mPa·s or less, 10 6 mPa·s or less, 5x10 5 mPa·s or less, 10 5 mPa·s or less, 5x10 4 mPa·s or less, 10 4 mPa·s or less, 5x10 3 mPa·s or less, or 10 3 The second viscosity is mPa·s or less.
19. The method according to any one of claims 15 to 18, wherein the water-insoluble fatty amine miscible with the CSSC is a primary, secondary, tertiary or quaternary C8-C 22 A linear, branched or cyclic, saturated or unsaturated, aliphatic or aromatic, alkyl or aryl amine or a combination thereof.
20. The method according to any one of claims 15 to 19, further comprising combining during step b) at least one material miscible with the CSSC, the material being selected from the group comprising: i. polar carrier insoluble surfactant; ii. Intermediate emulsifier; iii. polar carrier insoluble active agent; and iv. pH adjuster.
21. The method according to any one of claims 15 to 20, further comprising adding a polar carrier-soluble active agent to the polar carrier during or after step c) or step d), at least a portion of the active agent forming a second shell on the outer surface of the core-shell nanoelement.
22. The method according to any one of claims 15 to 21, further comprising adding to the polar carrier during or after step c) or step d) at least one material soluble in the polar carrier, the material being selected from the group consisting of: i. Surfactants; ii. Intermediate emulsifier; iii. Skin penetration enhancers; and iv. pH adjuster.
23. The method according to any one of claims 15 to 22, further comprising optionally adding a pH adjuster to the polar carrier in an amount suitable for imparting a charge to the core-shell nanoparticles, such that the charge of the core-shell nanoparticles measured at room temperature is selected from: A) a positive charge of +5 mV or more, +10 mV or more, +20 mV or more, +30 mV or more, or +40 mV or more; B) a negative charge between -60 mV and -5 mV, between -50 mV and -5 mV, between -40 mV and -5 mV, between -30 mV and -5 mV, or between -20 mV and -5 mV; and C) Nearly neutral charge between -5mV and +5mV.
24. The method according to any one of claims 15 to 23, wherein the polar carrier has a boiling point Tb at nanometer-sized pressure. c , and the fatty amine and the optional non-volatile liquid have a boiling point Tb at the pressure of the mixture a and Tb l , and the fatty amine has a degradation point under the pressure of the mixture, and the temperature of the nano-sizing is lower than Tb c , and the mixed temperature is lower than Tb a , the fatty amine degradation point and optionally below Tb l .
25. The method of any one of claims 15 to 24, wherein no volatile organic compounds (VOCs) are added to the CSSC in step b) such that the core-shell nanoelements contain less than 2 wt%, less than 1.5 wt%, or less than 1 wt% VOCs based on the weight of the nanoelements.
26. Use of a composition for external application to a surface to be treated therewith, comprising core-shell nanoelements dispersed in a polar carrier, the core-shell nanoelements consisting of: a) a core comprising at least one water-insoluble collagen synthesis stimulating compound (CSSC) having a molecular weight of 0.6 kilodaltons (kDa) or more; and b) a shell surrounding the core, the shell comprising at least one water-insoluble fatty amine non-covalently bonded to the CSSC; wherein at least 50% of the total number of the core-shell nanoelements have an average diameter (e.g., D N 50); and The core-shell nanoelement has 10 7 Viscosity of mPa·s or less.
27. The use according to claim 26, wherein the composition is according to any one of claims 1 to 14; and / or is prepared by the method of any one of claims 15-25.
28. The use according to claim 26 or 27 for preparing a cosmetic product, wherein the surface is the skin of a living subject and the composition is a cosmetic composition for achieving a cosmetic effect of improving the appearance of the skin, the effect comprising at least one of anti-collagen, elastin or glycosaminoglycan decomposition, promoting new synthesis of collagen, elastin or glycosaminoglycan, treating signs of skin aging, anti-wrinkles and fine lines, anti-skin dryness, anti-skin sagging, anti-skin thinning, anti-dull skin, anti-uneven skin pigmentation, anti-lack of skin elasticity and / or tension, and skin bleaching or tanning.
29. The use according to claim 26 or 27 for the preparation of a veterinary product or a medicament, wherein the surface is the skin of a living subject and the composition is a pharmaceutical composition for achieving a pharmaceutical effect selected from: A-improving skin health and / or appearance, the effects including treating skin damage, restoring skin integrity, promoting wound healing, alleviating or treating at least one of local skin inflammation, skin irritation, skin infection, rash, skin pain, skin burns, skin swelling and / or skin allergy; and promoting or inhibiting hair growth; and B-delay, alleviate, prevent or treat a transdermally treatable disease, the effect being selected from the group consisting of ADHD-relieving effect, analgesic effect, anthelmintic effect, anti-addiction withdrawal effect, anti-angina effect, anti-arthritis effect, anti-depressant effect, anti-vomiting effect, anti-rheumatic effect, anti-epileptic effect, blood pressure regulating effect, contraceptive effect, glaucoma relieving effect, hormone replacement effect, neuroprotective effect, thyroid regulating effect and protective effect against neurotoxicity.
30. Use according to claim 26 or 27 for the preparation of a veterinary product or a medicament, wherein the surface is the skin of a living subject and the composition is a pharmaceutical composition for wound healing.
31. Use according to claim 26 or 27 for preparing an agrochemical and / or industrial product, wherein the surface is an inert object, a surface of a plant or a pest or soil or water in which a plant grows or a pest is present, and wherein the composition is an agrochemical composition for achieving an agrochemical effect, the effect being one or more of acaricides, algaecides, insect repellents, moth repellents, avicides, bactericides, chemosterilants, fertilizers, fungicides, herbicides, insecticides including ovicides, anthelmintics, insect pheromones, molluscicides, nematicides, nitrification inhibitors, insecticides, pest repellents, plant growth promoters, rodenticides, soil fertilizers, termiticides, virucides and plant wound protectants.
32. A method for treating an object or a plant or animal subject, the method comprising applying to or around a target surface of the object or subject a composition according to any one of claims 1 to 14; and / or a composition prepared by the method of any one of claims 15 to 25; and / or a composition for use according to any one of claims 26 to 31, the composition being: A) a skin composition in the form of a cream, foam, gel, lotion or ointment, the target surface is the skin of a human or non-human animal subject, and the application is by applying the skin composition to the skin, or by attaching a dressing comprising the skin composition to the skin; B) an agrochemical composition in the form of a solution, emulsion, powder, granule, pellet or aerosol, the target surface is soil or water where plants grow or pests exist and the surfaces of plants and pests, and the application is by spreading, dispersing or spraying the agrochemical composition on the surface to be treated; C) An industrial composition in the form of a paint, paste, varnish, lacquer, spray or powder, the target surface being an inert object, the application being by spreading, spraying or dispersing the industrial composition on the inert surface.
Citation Information
Patent Citations
Skin care compositions comprising NANO-elements of collagen-synthesis stimulating compounds and methods of preparing the same
WO2022243899A1